L’efficacité du droit OHADA dans un contexte de convergence, concurrence et harmonisation des systèmes juridiques - Sangare, Salif (Université de Montréal, 2026)
Cette étude entend contribuer au développement économique des États d’Afrique subsaharienne francophone, notamment ceux membres de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA). En effet, les États qui constituent l’espace communautaire avaient déjà chacun dans leur sein des dispositions chargées de régir les activités économiques. Cependant, avec le temps, la disparité des normes régissant ces activités est apparue comme un frein à l’émergence économique de ces États. C’est dans ce cadre qu’ils ont décidé, lors de la signature du 17 octobre 1993 instituant l’OHADA, de mettre en place un droit commun des affaires en mesure de faciliter leur intégration juridique en promouvant le développement économique. Ce droit se veut « harmonisé, moderne et simple ». Si l’organisation a, à ce jour, adopté onze Actes uniformes couvrant plusieurs pans du droit des affaires en vue de réaliser la croissance économique prévue dans le Traité, il est important de souligner que le droit issu de l’OHADA souffre d’une certaine lourdeur liée à son enracinement non africain. Aussi, l’harmonisation du départ considérée comme le fer de lance de l’Organisation s’est matérialisée sur le terrain par une uniformisation du droit des États membres dans une société traversée par le multiculturalisme. Cette situation peut être de nature à contraindre les mœurs par le droit. On peut également ajouter à cela, le fait que le droit issu de l’OHADA est marqué par le sceau du mimétisme juridique en ce qu’il ne prenne pas en compte le secteur informel qui occupe une place très importante dans les relations d’affaires. Enfin, puisque l’enchâssement de la loi dans l’identité culturelle est l’une des conditions déterminantes de son efficacité, les précurseurs du droit OHADA auraient tout à gagner en faisant ressortir le droit OHADA des valeurs des sociétés africaines, sinon, le développement économique tant recherché de l’Afrique n’aura pas lieu. This study aims to contribute to the economic development of French-speaking sub-Saharan African countries, particularly those that are members of the Organization for the Harmonization of Business Law in Africa (OHADA). Indeed, the states that make up the community already had provisions in place to govern economic activities. However, over time, the disparity in the standards governing these activities has emerged as an obstacle to the economic emergence of these states. It was in this context that, when signing the agreement establishing OHADA on October 17, 1993, they decided to put in place a common business law capable of facilitating their legal integration by promoting economic development. This law aims to be “harmonized, modern, and simple.” While the organization has, to date, adopted eleven Uniform Acts covering several areas of business law with a view to achieving the economic growth envisaged in the Treaty, it is important to note that OHADA law suffers from a certain cumbersomeness due to its non- African roots. Thus, the harmonization that was initially considered to be the Organization's spearhead has materialized in practice as a standardization of the laws of member states in a society marked by multiculturalism. This situation may be such as to constrain customs through the law. To this can be added the fact that OHADA law is marked by legal mimicry in that it does not take into account the informal sector, which plays a very important role in business relations. Finally, since the embedding of law in cultural identity is one of the determining conditions for its effectiveness, the precursors of OHADA law would have everything to gain by highlighting the values of African societies in OHADA law; otherwise, the much sought-after economic development of Africa will not take place.
Keywords: Acte uniforme; African societies; Cultural diversity; Diversité culturelle; Droit OHADA; Développement économique; Economic development; Efficacité; Efficiency; Harmonisation; Harmonization; Intégration juridique; Legal integration; OHADA law; Sociétés africaines; Standardization; Uniform Act; Uniformisation

Les obstacles à l’intégration sous régionale en Afrique Centrale : Une analyse des contraintes politiques et des défis sécuritaires en zone CEMAC - Maina Kampete, Lady (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
L’intégration sous-régionale constitue un objectif majeur pour les États d’Afrique centrale réunis au sein de la Communauté économique et monétaire de l’Afrique centrale (CEMAC). Malgré l’adoption de nombreux instruments juridiques et politiques visant à favoriser la libre circulation des personnes, des biens et des services, les résultats demeurent limités. Cet article analyse les contraintes politiques et sécuritaires qui entravent le processus d’intégration régionale dans la zone CEMAC. À partir d’une analyse institutionnelle et politique, il met en évidence la prééminence persistante des logiques souverainistes des États membres, la faiblesse de la gouvernance communautaire ainsi que l’impact des défis sécuritaires sur la gestion des frontières et la mobilité régionale. L’étude montre que l’attachement des États à leurs prérogatives nationales, combiné à l’insuffisance des mécanismes de sanction et à la multiplication des contrôles administratifs aux frontières, contribue à fragiliser l’effectivité du droit communautaire. Par ailleurs, les crises sécuritaires régionales et les tensions politico-sécuritaires entre États membres accentuent la fragmentation de l’espace régional et limitent les dynamiques d’intégration. Notre article conclut que le renforcement des institutions communautaires, l’harmonisation effective des normes et l’amélioration de la coopération sécuritaire apparaissent comme des conditions indispensables à la consolidation du processus d’intégration en Afrique centrale. Regional integration has long been considered a key instrument for economic development and political cooperation in Central Africa. Within this framework, the Economic and Monetary Community of Central Africa (CEMAC) was established to promote economic convergence, market integration, and the free movement of people and goods among its member states. However, despite the adoption of several legal and institutional frameworks aimed at facilitating regional integration, the outcomes remain limited. This article examines the political and security constraints that hinder regional integration within the CEMAC area. Using an institutional and political analysis, it highlights the persistence of strong sovereignist logics among member states, the weaknesses of regional governance, and the impact of security challenges on border management and regional mobility. The study shows that the strong attachment of states to national sovereignty, combined with the limited enforcement capacity of community institutions and the absence of effective sanction mechanisms, undermines the effective implementation of community law. In addition, security crises and political tensions within the region contribute to the fragmentation of the regional space and restrict the mobility of people and goods.The findings suggest that strengthening community institutions, improving the enforcement of regional regulations, and enhancing security cooperation among member states are essential conditions for achieving effective regional integration in Central Africa.
Keywords: Afrique centrale; CEMAC; Central Africa; Free Movement; Gouvernance; Governance; Intégration régionale; Libre circulation; Regional Integration; Security; Souveraineté; Sovereignty; Sécurité

La pertinence de la contribution normative de la ZLECAF à la floraison des PME camerounaises - Zanga Etoundi, Antoinette Carine (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Cette réflexion sur la contribution normative de la ZLECAF à la floraison des PME au Cameroun a pu être établie d’une part en prenant en compte la pertinence avérée et effective de la contribution de la ZLECAF à l’épanouissement des PME. En mobilisant la méthode juridique et d’autres complémentaires (historique et comparative), il s’est agi de mettre en exergue le rôle de cette institution dans la redéfinition du cadre juridique du libre-échange en Afrique. L’établissement et la régulation des échanges libres entre les Etats parties à l’accord, sonne comme une nouveauté à travers la contextualisation qui en découle. La prise en compte des spécificités africaines dans le commerce interétatique se positionne comme une cure de jouvence à la bonne marche du commerce international africain. Il s’est également agi de faire valoir le redimensionnement de la contribution du genre dans le monde de l’entrepreneuriat en Afrique et particulièrement au Cameroun. L’accord stipule un nécessaire équilibre des genres en la matière, renforçant ce faisant la vocation des PME à être plus productives et mieux intégrantes. This reflection on the normative contribution of the AfCFTA to the flourishing of SMEs in Cameroon was established, firstly, by considering the proven and effective relevance of the AfCFTA's contribution to SME development. By employing legal methods and other complementary approaches (historical and comparative), the aim was to highlight the role of this institution in redefining the legal framework of free trade in Africa. The establishment and regulation of free trade between the States Parties to the agreement is a novelty, given the resulting contextualization. Taking into account African specificities in interstate trade is seen as a revitalization of the smooth functioning of African international trade. It was also important to emphasize the increased role of gender in the world of entrepreneurship in Africa, and particularly in Cameroon. The agreement stipulates a necessary gender balance in this area, thereby reinforcing the role of SMEs in becoming more productive and more inclusive.
Keywords: AfCFTA; Contribution normative; Echanges inter étatiques; Entreprenariat féminin; Intergovernmental trade; Normative contribution; PME; SME; Women's entrepreneurship; ZLECAf

Le contentieux disciplinaire : Plaidoyer pour une harmonisation du droit disciplinaire dans les prisons de la zone CEMAC - O'Bounou, Eric (Université de Pau et des Pays de l'Adour, 2025)
En février 1995 la situation des prisonniers connait une ouverture vers une prison de droit suite à un revirement de jurisprudence consacré par l'arrêt ''Marie''. Cette décision fixe le cadre de l'érection d'un procès en droit, autorisant le juge à connaitre des recours formulés par les détenus contre l'administration pénitentiaire. Le contentieux disciplinaire pénitentiaire augure alors une nouvelle discipline qui va enrichir la matière pénitentiaire. Plusieurs années après l'établissement de cette jurisprudence, les pays de l'Afrique centrale en général et de la zone CEMAC en particulier, qui ont adopté en copie collée les règles du droit administratif français et son contentieux, tournent le dos à la pénétration du principe de légalité en milieu carcéral, laissant ainsi les mesures intérieures imposées une dictature dans les établissements pénitentiaires de cet espace. Pour que le droit trouve enfin une place au sein de l'univers carcéral, le plaidoyer pour une harmonisation du droit disciplinaire, nous offre une ouverture pour garantir une protection des droits des détenus par l'instauration des règles qui gouvernent l'accès à une procès équitable. In February 1995, the situation of prisoners saw an opening towards a rights-based prison following a change in case law established by the 'Marie' ruling. This decision sets the framework for the establishment of a legal process, allowing judges to hear appeals made by inmates against the prison administration. The disciplinary litigation in prisons heralds a new discipline that will enrich the field of incarceration. Several years after the establishment of this case law, countries in Central Africa in general, and the CEMAC zone in particular, which have adopted a copy of French administrative law and its disputes, turn their backs on the penetration of the principle of legality within the prison environment, thus allowing internal measures to impose a dictatorship within the penitentiary establishments of this area. For law to finally find a place within the prison universe, advocacy for the harmonization of law.
Issue: 2025PAUU2013
Keywords: CEMAC; Communauté Economique et Monétaire de l'Afrique Centrale; Contentieux; Disciplinary; Discipline; Harmonisation; Harmonization; Litigation; Prison; Prisons; Prisons (discipline); Prisons (droit)

L’avis consultatif des cours de justice CEMAC et CAE : couleur et marqueur d’une construction silencieuse du droit communautaire - Nkili Mbida, Eugène Pascal Parfait (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
La présente analyse est une forme d’endoscopie de la soft law communautaire. Parcourir ses profondeurs est révélateur de ce que l’avis consultatif émis par les Cours de justice CEMAC et CAE participe d’une silencieuse construction du Droit communautaire. Par sa subtile obligatoriété, il rappelle la mission d’application et d’interprétation des Traités et des textes subséquents, confiée aux Cours de justice par les « maîtres des Traités ». L’avis consultatif, démineur de contentieux, est un gage de sécurité juridique. Il évite l’émiettement du Droit communautaire tiraillé dans le conflit inhérent aux rapports de systèmes juridiques qu’il essaie de réguler au fil des saisines pertinentes des juges d’Arusha et de N’Djaména, dans son rôle le plus à tort marginalisé. This analysis is an endoscopy of Community soft law. Delving into its depths reveals that the advisory opinion issued by the CEMAC and East African Courts of justice is part of a silent construction of Community law. Through its subtle obligatory nature, it recalls the jurisdiction over the application and interpretation of Treaties and subsequent texts, entrusted to the Courts of Justice by the “masters of Treaties”. As minesweeper of disputes, the advisory opinion is a guarantee of legality. It avoids the fragmentation of Community law, torn in the conflict inherent in the relationships between legal systems that it attempts to regulate through the relevant petitions addressed to the judges of Arusha and N’Djamena, in its most wrongly marginalized role.
Keywords: Advisor opinion; Advisory function; Avis consultatif; Community law; Cours de justice; Court of justice; Droit communautaire; Fonction consultative

La dénonciation des traités en droit international africain - Kassabo, Léon Dié (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
La dénonciation des traités en droit international africain soulève des enjeux juridiques importants. Elle s’inscrit dans le cadre de la Convention de Vienne sur le droit des traités de 1969, qui régit les conditions de retrait d’un traité, notamment à travers ses articles 54 et 56. Ceux-ci prévoient que la dénonciation est possible soit conformément aux dispositions du traité, soit avec le consentement de toutes les parties, ou encore si la nature du traité le permet, moyennant un préavis raisonnable. En Afrique, plusieurs États ont récemment exercé leur droit de retrait, notamment vis-à-vis d’engagements relatifs aux droits de l’homme. Un exemple marquant est la dénonciation du traité de la CEDEAO par les Etats de l’AES sur le fondement juridique de l’article 91 dudit traité. Ces pratiques suscitent des débats sur leur conformité au droit international, en particulier quant à la protection des droits acquis et à la sécurité juridique. Elles traduisent une tension entre le respect de la souveraineté étatique et les obligations internationales, soulevant des inquiétudes quant à la fragilisation des mécanismes africains de protection des droits humains. Dès lors, la question de la dénonciation des traités interpelle sur la nécessité de garantir un équilibre entre les intérêts étatiques et la pérennité des institutions juridiques régionales.
Keywords: Dénonciation; Engagements internationaux; Souveraineté; Sécurité juridique; Traités

L'environnement dans le traité révisé de la CEEAC : une prise en compte mitigée - Meli Fotie, Anthony (International Multilingual Journal of Science and Technology, 2025)
Née à une époque où la protection de l’environnement constituait un leitmotiv sur la scène internationale, il a fallu plus de trois décennies à la CEEAC pour inscrire expressément cette protection dans son texte fondamental notamment son Traité révisé. Nonobstant cet exploit, des manquements sont observables. D’une part, le Traité considère la protection de l’environnement comme un moyen de l’intégration économique et non comme un objectif à part entière de la communauté. D’autre part, l’environnement est appréhendé de manière sectorielle dans le Traité pourtant, la tendance doit être la globalisation de l’environnement par l’inclusion de celui-ci dans tous les politiques sociaux économiques de la communauté tel que se revendique aujourd’hui le développement durable. A l’épreuve, la CEEAC se doit dans son Traité de rendre à l’environnement toute l’attention et l’importance qui lui sont reconnues aujourd’hui. Born at a time when environmental protection was a leitmotif on the international scene, it took more than three decades dor ECCAS to expressly include this protection in its fundamental text, particularly its Revised Treaty. Notwithstanding this feat, shortcomings are observable. On the one hand, the Treaty considers environment protection as a means of economic integration and not as a separate objective of the community. On the other hand, the environment is understood in a sectoral manner in the Treaty, however, the trend most most be the globalization of the environment through the inclusion of it in all, the social and economic policies of the community such as sustainable development is now being promoted. Under the test, the ECCAS must in its Treaty give to the environment all the attention and importance that is recognized for it today.
Keywords: CEEAC; ECCAS; Environment (protection); Environnement (protection); Revised Treaty; Traité révisé

Directive portant harmonisation de l'imposition des revenus et des bénéfices dans les Etats membres de la CEMAC - Communauté Economique et Monétaire de l'Afrique Centrale (2025)

La armonización del derecho contractual internacional por medio de los restatements internacionales. - Carreño Bernal, Emmanuel Guillermo (Revista Boliviana de Derecho, 2025)
El artículo analiza cómo el crecimiento del comercio internacional ha resaltado la necesidad de marcos jurídicos armonizados para regular relaciones contractuales de carácter internacional. Los Restatements Internacionales han surgido como una herramienta clave para consolidar principios jurídicos comunes. Además, el estudio revisa los esfuerzos de organismos globales y regionales como UNIDROIT y OHADAC, así como iniciativas académicas como los Principios LANDO y los Principios de Derecho Contractual Asiático. The article analyzes how the growth of international trade has highlighted the need for harmonized legal frameworks to regulate international contractual relations. International Restatements have emerged as a key tool for consolidating common legal principles. Additionally, the study reviews the efforts of global and regional organizations such as UNIDROIT and OHADAC, as well as academic initiatives like the LANDO Principles and the Asian Contract Law Principles.
Keywords: Armonización jurídica; Contratación transfronteriza; Cross-border contracting; International principles; International restatements; Legal harmonization; Principios internacionales; Restatements internacionales

La Cour Africaine des Droits de l’Homme : la liberté de circulation des étrangers et l’intégration africaine. Observations rétrospectives sur l’arrêt Ikili Rashidi contre République-Unie de Tanzanie du 28 mars 2019 - Moyen, Léandre SergeI (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2024)
La Cour africaine était sollicitée pour répondre à la question de savoir si les ressortissants des États africains peuvent avoir droit, au même titre que les nationaux d’un État, à une égale protection en ce qui concerne la liberté de circulation et de séjour, c’est-à-dire de choisir librement leur résidence sur le territoire d’un État membre de l’Union africaine et signataire de la Charte africaine des droits de l’homme, même quand la régularité de leur séjour n’est pas formellement établie. Cette question fait directement référence à la problématique de l’intégration africaine, et en s’inscrivant dans la perspective intégrationniste, il était possible d’y répondre par l’affirmative. Au regard de l’idéal politique panafricain de l’unité politique affirmé pas le traité constitutif de l’Union africaine, la Cour pouvait interpréter la Charte africaine des droits de l’homme ou la Déclaration universelle des droits de l’homme comme autorisant les ressortissants des États africains à établir leur résidence où ils le souhaitent sur n’importe quel territoire d’un État membre de l’Union. Mais l’absence d’une citoyenneté africaine a conduit la Cour à lire l’article 3 de la Charte africaine dans le sens opposé. Ce faisant, elle entérine le renforcement des législations nationales, qui se sont inspirées des législations européennes très restrictives à l’égard de l’entrée et du séjour des étrangers sur le territoire de l’Union européenne. Elle s’est abstenue de créer du droit substantiel, alors qu’elle avait toute latitude pour le faire, à l’instar de la Cour européenne qui limite volontiers le pouvoir souverain des États en matière de protection des droits fondamentaux des personnes. Cette attitude prudente s’est confirmée dans l’appréciation des règles du procès équitable, où la Cour fait un usage modéré des pouvoirs que lui confèrent les articles 56 alinéas 5 et 6 de la Charte africaine et 40 § 6 du Règlement de la Cour, bien que le cadre conventionnel soit plastique. En définitive, la Cour africaine n’a pas été conçue pour accompagner l’unité politique africaine ; elle n’est pas l’instrument de mise en œuvre de la politique d’intégration africaine, et la décision Ikili Rashidi montre à coup sûr les limites de l’office du juge panafricain dans la protection des droits et libertés des citoyens. Il est impératif que les États s’orientent vers l’institution du contrôle de constitutionnalité des lois à l’échelle fédérale, ce qui semble être la seule alternative permettant la mise en place d’une justice réellement souveraine au service de l’intégration.
Keywords: Cour africaine des droits de l’homme; Dignité humaine; Droits fondamentaux de la personne; Etranger; Expulsion; Intérêt supérieur de l’enfant; Justice (administration); Liberté de circulation; Procès équitable; Vie familiale; Vie privée

The Challenges of Adoption of Eco Single Currency among ECOWAS Member-States - Anele, Livinus; Anuga, Joseph (African Journal of Politics and Administrative Studies, 2024)
The Economic Community of West African States, ECOWAS, had an agreement to adopt the Eco as its single currency for the fifteen member-states of the West African Sub-regional organization. This major objective has failed to materialize after a long period of time. This paper, therefore seeks to highlight the major challenges confronting the Eco currency project. Data were collected from secondary sources, using content analysis. The paper of discusses the challenges facing the proposed Eco single currency in West Africa, discusses the theoretical framework of monetary integration using Mundell’s factors of Mobility Theory and Mundell’s Optimum Currency Area Theory applied. Based on the findings, Some of the challenges facing the proposed Eco currency in ECOWAS include lack of political will, influence of France on its former territories in West Africa, membership of multiple regional blocs by member states of ECOWAS and fear of domination of the smaller states in the bigger ones. Other challenges include; security and political challenges, inadequate legal instruments to enforce treaty obligations, inadequate modern infrastructure among others. To make this proposed Eco currency a success, the paper suggests that West Africa Monetary Zone member states must take concrete action by showing political will towards the creation of Eco currency area in West Africa. There should be clearly spelt out benefits and costs accruing to each member state in the proposed Eco community currency area. All member states of ECOWAS must be treated as equal partners.
Keywords: Adoption; Anglophone-Francophone; Development; ECOWAS; Eco single currency

From red tape to red carpet: the Unidroit Cape Town Convention and MAC Protocol’s Adventure in Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2024)
This article examines the implementation of the Mining, Agricultural and Construction (MAC) Equipment Protocol under the Cape Town Convention in Africa, focusing on enhancing economic growth and sustainable development through improved access to financing for high-value mobile equipment. Africa’s economic development is significantly hindered by inadequate infrastructure, which escalates transaction costs and limits access to international markets. Investment in modern infrastructure, particularly in the mining, agricultural, and construction sectors, is typically expensive for many businesses in the African region. The MAC Protocol aims to address these challenges by providing a uniform legal framework that supports the financing of MAC equipment. The Convention and the MAC Protocol facilitate access to affordable capital and reduce risks for financiers who take international interests in MAC equipment, promoting economic activities in Africa. The article highlights the legal protections offered by the MAC Protocol, ensuring rights against third-party claims and enhancing the enforceability of international interests. The adoption of the MAC Protocol by African States could significantly impact their ability to meet the United Nations Sustainable Development Goals by making modern, cost-efficient equipment more accessible, thus boosting productivity and economic diversification. The article advocates for adopting the MAC Protocol, emphasizing its potential to enhance foreign investment in the mining, agriculture, and construction sectors, stimulating economic development in Africa. This strategic move will propel African countries towards greater economic resilience and integration into the global economy. The article also critically analyses and illustrates the several declaration mechanisms available to countries adopting the MAC Protocol, accompanied by a guidance note to sensitize lawmakers when signing and/or ratifying or acceding to the Cape Town Convention and the MAC Protocol.

La libre circulation des personnes dans l'espace CEDEAO-UEMOA - Zouho, Bagnon César (Université de Strasbourg, 2024)
Intervenant sur le même espace régional, les deux principales organisations de l’Afrique de l’ouest à savoir la Communauté Economique Des Etats d’Afrique de l’Ouest (CEDEAO) et l’Union Economique et Monétaire Ouest Africaine (UEMOA) partagent l’objectif de parvenir à la libre circulation des personnes. Pourtant, il est constamment relevé que les droits qui devraient faciliter cette mobilité sont loin d’être mis en œuvre et qu’un contraste subsiste entre l’objectif de parvenir à la réalisation effective du principe de la libre circulation des personnes et les pratiques qui traduisent un exercice limite de cette liberté. La présente étude a trait aux problématiques en lien avec la question migratoire en Afrique de l’ouest, rend compte de l’adéquation apparente du régime adopte par la CEDEAO et l’UEMOA a l’effet de doter le principe de la libre circulation des personnes d’une véritable assise juridique. Il apparait ainsi que la qualité de cet ensemble de normes découle aussi bien de la diversification des bénéficiaires que de la cohérence de son contenu. Toutefois, l’analyse des modalités de réalisation du régime mis en place révèle des imperfections tenant aussi bien à la construction incomplète, qu’à l’application ineffective du droit de la libre circulation des personnes dans l’espace CEDEAO -UEMOA. Au demeurant la présence de facteurs extra-juridiques découlant des divergences et incohérences observées dans les positions des acteurs notamment les Etats, les organisations régionales et les peuples ouest-africains, laisse entrevoir la persistance d’obstacles d’ordre pratique qui compromettent l’atteinte des objectifs. Il s’ensuit que la libre circulation des personnes dans l’espace CEDEAO -UEMOA doit être considéré comme un processus dynamique dont l’évolution dépend de la capacite de l’ensemble des acteurs à réinventer des réponses adaptées a la spécificité des problématiques et contexte ouest-africains.
Keywords: Afrique occidentale; Borders; CEDEAO; Communauté économique des États de l'Afrique de l'Ouest; ECOWAS; Etats; Free movement of people; Frontières; Intégration régionale; Libre circulation des personnes; Regional integration; States; Travailleur; UEMOA; Union économique et monétaire Ouest africaine; Visa; Worker

The efficient enforcement challenge of secured transactions law reforms in civil law systems: self-help repossession, strict foreclosure, and other methods for the acceleration of enforcement of security interests - Tajti (Thaythy), Tibor (Uniform Law Review, 2024)
Although the forging of an efficient system for enforcement of security interest is one of the central expectations of secured transaction law reforms in civil law systems, the results hardly give reason for satisfaction. As the reforms tend to be supported and influenced by various international organizations’ projects (especially the World Bank, the European Bank for Reconstruction and Development, the International Institute for the Unification of Private Law, and the United Nations Commission on International Trade Law), most out-of-court methods of enforcement of security interests have played a central role. Yet due to civil law’s general hostility towards self-help as such, either the introduction of the concept has been rejected or the local limited-reach kin have been merely ‘paper tigers’. Similarly, although security interests on several types of collateral (accounts, investment property) or on the workhorse of the English financial system—the floating charge—have also been enforced extrajudicially (save the exceptions), little attention has been attributed to these enforcement modalities. The same applies to strict foreclosure in civil law systems still being prohibited, or restricted, and thus rarely resorted to, due to the inherited hostility towards the doctrine of lex commissoria. Rethinking local laws on preliminary and temporary court orders to match them with such globally known ex parte preliminary measures as the English Mareva Injunction or the French Saisie Conservatoire, which allow creditors to swiftly freeze debtors’ assets and thus substitute self-help repossession, has also been given short shrift. The enforcement segment, consequently, remains the Achilles’ heel of secured transaction law reforms in civil law systems. This article desires to contribute to reform literature by addressing these deficiencies and by offering tested, fully or partially fitting, functional equivalents of self-help repossession.

States and Regional International Organizations - Zouapet, Apollin Koagne (International Organizations Law Review, 2024)
Beyond the thorny, even insoluble question of the definition of a region and the definition of the criteria that should make it possible to apprehend the polymorphism of rio s, the raison d’être of these organizations, their mode of operation and their activities are at the heart of the debate on “international governance”. For many authors, the advent of RIO s has often been seen as a challenge to the state monopoly in the international legal order and a redefinition of the relationship between these particular organizations and states. It is this relational dynamic between the States and the RIO s that this contribution aims to describe and analyse. The aim is to examine the originality and specificity of the relationship between the RIO s and the States, compared to the latter’s relationship with the ‘classic/universal’ ios, which would reveal something about the very nature of regional organizations.
PDF: https://brill.com/downloadpdf/view/journals/iolr/21/1/article-p147_008.pdf
Keywords: Cooperation; Instrumentalism; Integration; Regionalism; Supranationalism; Universalism

The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On - Heyns, Christof; Viljoen, Frans Jacobus; Murray, Rachel (Brill, 2024)
This collection of chapters tracks and explains the impact of the nine core United Nations human rights treaties in 20 selected countries, four from each of the five UN regions. Researchers based in each of these countries were responsible for the chapters, in which they assess the influence of the treaties and treaty body recommendations on legislation, policies, court decisions and practices. By covering the 20 years between July 1999 and June 2019, this book updates a study done 20 years ago.
PDF: https://brill.com/downloadpdf/edcollbook-oa/title/38945.pdf
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives

The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal - Kane, Ibrahima (The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On, 2024)
"Chapter 16 The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal" published on 09 Feb 2024 by Brill | Nijhoff.
Section: The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives; Social Sciences

Uniform Law: Legal Responses to Globalisation - Basedow, Jürgen; Max-Planck-Institut für Ausländisches und Internationales Privatrecht (Hamburg, Germany) (Mohr Siebeck, 2024)
International conference proceedings
Keywords: COMMERCIAL LAW; Economic Analysis; PRIVATE INTERNATIONAL LAW; Uniform law

L’OHADA et les ressources naturelles - Dieudonné, Barnabas (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Les ressources naturelles occupent une place prépondérante dans le commerce international. L’Afrique en est riche. Par contre, le problème de leur gestion se fait sentir sur le continent au point que des chercheurs ont évoqué la « malédiction des ressources naturelles ». Le droit de l’OHADA ne les a pris en compte que timidement. Cette insuffisance de règlementation dans le droit communautaire a des incidences tant sur le commerce de ces produits dans l’espace OHADA que sur la jouissance de certains droits humains. Les tentatives de règlementation de certains aspects de ce secteur d’activité de la part d’autres organisations internationales et de certains États montrent la nécessité de les intégrer correctement dans le corpus juridique de l’OHADA. Un Acte Uniforme serait susceptible d’atténuer, au sein des États parties, la « malédiction des ressources naturelles » aussi bien que les atteintes aux droits de la personne résultant de leur exploitation comme le droit à un environnement sain et les droits économiques et sociaux.
Keywords: Acte uniforme; Droits humains; Ressources naturelles; Règlementation

Les mesures provisoires devant la Commission et la Cour africaines des droits de l'homme et des peuples - Fall, Marie (Université de Genève, 2024)
La protection provisoire devant la Commission et la Cour africaines des droits de l’homme et des peuples est l’un des domaines du système africain de protection des droits et des peuples jusque-là loin d’être défriché de manière exhaustive. Pourtant, la mise en œuvre du dispositif des mesures provisoires dans le contexte africain remonte à l’établissement de la Commission africaine. Cette thèse propose de scruter le régime juridique exact des mesures provisoires et les contours de la pratique. La thèse ici défendue est que malgré les difficultés que peut poser le régime des mesures provisoires, la Commission et la Cour africaines en font un mécanisme au service de la protection effective des droits fondamentaux des requérants. Toutefois, la concrétisation de cette finalité est compromise par le taux élevé d’inexécution de ces mesures en raison des insuffisances dont souffre la procédure devant ces organes auxquelles s’ajoute la mauvaise volonté des États parties. Cette thèse formule ainsi des solutions qui permettent à la Cour et à la Commission d’exploiter le potentiel du régime des mesures provisoires comme instrument au service de la garantie effective des droits fondamentaux des individus protégés par la CADHP.
Keywords: CADHP; Intégration régionale

Measuring the Effects of Post-Convention Activities at the HCCH - Zhang, Ke (McGill University, 2024)
https://escholarship.mcgill.ca/concern/theses/cn69m944k
Keywords: HCCH; Hague Conference on Private International Law

Nigeria’s Contribution to Africa’s Regional Integration: Assessment of its recent Performance - Garba, Dimas (African Journal of Politics and Administrative Studies, 2023)
This paper investigates the recent performance of Nigeria towards Africa’s regional integration as a major power in Africa. The main objective of the research is to determine the extent of Nigeria’s commitment to the realization of the African Union’s vision of becoming a fully integrated, prosperous and peaceful Africa; and a dynamic force at the global level. Since her independence in 1960, Nigeria has been widely acknowledged as a leading power in Africa (The Giant of Africa) by several studies because of its preponderant political, economic and militarily power; influence; and benevolent contributions regarding to the liberation and progress of Africa. However, there are hardly substantive assessments of its recent performance towards Africa’s integration. The study adopts the Hegemonic Stability Theory; and descriptive analysis method to analyze data obtained from secondary sources. Analysis of the 2016 and 2019 Regional Integration Index (ARII) reports covering the period from 2010-2019 reveals that Nigeria has performed poorly towards the continent’s integration among its peers, both at the continental and sub-regional levels. The paper concludes that Nigeria’s poor performance would significantly slow the acceleration of Africa’s integration; and the country risks losing its leadership position in Africa to its rivals, especially South Africa. It recommends that the Nigerian government should take deliberate steps in formulating and implementing policies that would improve its performance across the five dimensions of the regional integration; and it should strengthen its commitment to consolidate its leadership position in Africa, and motivate smaller countries to contribute their best.

The Challenges of Regional Integration and Effective Implementation of African Continental Free Trade Area (AfCFTA) Policy in Africa - Garba, Dimas; Wancelous, Avong (African Journal of Politics and Administrative Studies, 2023)
The paper is an investigation of the challenges of regional integration in Africa and their effects on the implementation of the African Continental Free Trade Area (AfCFTA) policy. The major objective of the paper is to proffer solutions to the challenges for the effective actualization of the policy. The assumptions of the neo-liberal theory were used to support the AfCFTA initiative to promote economic growth and development in Africa. The data used to advance the argument were obtained from secondary sources of data collection. The study finds that language barrier, multiple currencies, porosity of borders, foreign interference, political instability and insecurity, poor human development, over-lapping of membership of sub-regional organizations, poor state of infrastructure, and state-centric nature of integration initiatives are some of the core challenges hindering the effective execution of the AfCFTA policy. The study recommends that the African Union (AU) should intensify effort at realizing a single currency policy for Africa; design comprehensive regional security architecture to include high technological surveillance, joint air and ground border patrol among member states of Regional Economic Communities (RECs) to address trans-border crimes and insecurity. There should also be institutionalization of counterpart funding among AU member-states for infrastructural development; and encouragement of private and civil society participation in the integration initiative, among others. In concludes that if the challenges identified are not effectively addressed, it will be very difficult for the AU to successfully realize the objectives of the AfCFTA policy.
Keywords: AfCFTA Policy; Africa; Challenges; Implementation; Regional integration

L'attractivité du droit OHADA - Akonumbo, Atangcho Nji; Monkam, Cyrille; Pironon, Valérie (Institut de Recherche en Droit Privé, 2023)

L’application du droit communautaire dans l’ordre juridique interne des Etats membres : cas de l’Union Économique et Monétaire Ouest Africaine - Camara, Gabriel; Coulibaly, Karamoko (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Le présent article traite de la problématique de l’application du droit communautaire dans l’ordre juridique interne des Etats Ouest Africains. Conscient des enjeux politiques et économiques, les états Ouest africains ont senti la nécessité d’aller vers la mise en place d’un arsenal juridique communautaire. Au-delà de cette volonté affichée, l’applicabilité des normes de L’UEMOA et de CEDEAO reste encore un défi dans l’ordre interne. This article deals with the problem of the application of community law in the internal legal order of West African States. Aware of political and economic issues. West African states felt the need to move towards establishing a community legal arsenal. Beyond this stated desire, the applicability of UEMOA and ECOWAS standards still remains a challenge in the internal order.
Keywords: Community law; Droit communautaire; Legal order; Ordre juridique; UEMOA; WAEMU

La justice à l’aune de l’intégration : cas de l’OHADA-UEMOA CEDEAO - Diallo, Hamadi; Fofana, Modibo Mohamed (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Les institutions de l’UEMOA, CEDEAO et de l’OHADA réagissent pour l’essentiel, de la même façon quand il est question de la nécessité de coordonner leurs efforts de développement en soumettant, totalement ou partiellement la gestion de leurs domaines de compétences et de leurs outils de travail à un « cadre de politiques communes, harmonisées et cohabitant ». L’atteinte de ces objectifs passe nécessairement par un partage de domaine de compétences entre les deux organisations. C’est à ce niveau que surgit la problématique des risques de conflits car ces organisations n’ont procédé à aucun partage de compétences. Il est évident que ces organisations entreront en conflit soit sur leurs domaines matériels ou encore au niveau juridictionnel rapporté ainsi aux compétences des trois cours de justice. Ces conflits sont donc perçus, soit au plan du droit matériel, qu’il soit originaire ou dérivé, soit au niveau des compétences de ces juridictions communautaires sur les matières communautaires. Voilà les problèmes autour duquel cet article tente d’analysé.
Keywords: CEDEAO; Droit communautaire; Intégration régionale; OHADA; UEMOA

O processo de constitucionalização dos estados africanos de expressão portuguesa: caminho para um pluralismo jurídico de procedimento - Roda, Arménio Alberto Rodrigues da (Universidade Federal da Bahia, 2023)
Os Estado africanos gozam de uma peculiaridade de possuírem caraterísticas culturalmente heterogêneas, o que acaba tendo um reflexo direto na composição das ordens normativas, as quais compreendem a mesma estrutura híbrida. Com o processo colonial, foram introduzidas na África famílias jurídicas do common Law e civil Law, que foram mantidas no período pós independência, resultando, desse modo, num conflito intersistêmico entre o direito estatal positivista e os direitos africanos – e, em alguns Estados, direito islâmico (Sharia). Diante dessa relação truculenta, a presente pesquisa propõe, em primeiro lugar, o reconhecimento do pluralismo jurídico procedimental e processual, de forma a amenizar esse conflito entre ambas as ordens, no qual o direito positivo arroga-se hegemônico e monista, limitando as manifestações dos direitos consuetudinários. Frisa-se de antemão que essa pesquisa se cinge especialmente aos países africanos de expressão portuguesa, dos quais a Constituição jurídica reconhece formalmente o pluralismo jurídico, todavia na perspectiva meramente substantiva, ou seja, sem métodos claros para efetivação do pluralismo jurídico, seja no âmbito institucional ou na dimensão processual, capaz de integrar os tribunais comunitários e as autoridades tradicionais num ambiente funcionalmente dialógico e plural. Ademais, a pesquisa buscou analisar a forma de funcionamento dos tribunais comunitários que exprimem a manifestação concreta do pluralismo jurídico, tendo sido analisados países como Moçambique, Cabo Verde, Guiné-Bissau e, de forma módica, Angola. Foram descritas as vantagens dos tribunais comunitários para o acesso à justiça e as suas limitações inerentes a certos direitos e certas garantias fundamentais que correm risco de serem violados, como o devido processo, negação da igualdade formal das mulheres e direitos das crianças. Para tal, foi proposta a possibilidade de fiscalização desses tribunais e participação de juízes profissionais em casos de grande magnitude. Sem embargos, cabe mencionar que foi trazida à discussão o paradigma pós positivista como um mecanismo de superação do positivismo puro, admitindo uma correção do direito pela moral, no sentido proposto por Robert Alexy (2009) e com nuances argumentativas compatíveis com a realidade africana, apresentado no terceiro capítulo em que se discuti a questão da crise do positivismo no continente africano. Frisa-se também que foi agregado a esse trabalho uma argumentação voltada à possibilidade de constitucionalização de Ubuntu como um princípio constitucional, parte dos direitos africanos, constituindo um mecanismo de incorporação e codificação plural dos valores africanos nos leques das normas estatais. Além do que já foi dito, foi analisada a questão ligada à efetividade dos direitos fundamentais, sobretudo os direitos das mulheres, tendo enaltecido a viabilidade de um constitucionalismo feminista, que pugna pela justiça de gênero na África, especialmente nas questões concernentes aos direitos reprodutivos e ao acesso às mesmas oportunidades. Por fim, descreveu-se o modelo das cortes constitucionais e o seu papel para a garantia e promoção dos direitos fundamentais. African states have the peculiarity of having culturally heterogeneous characteristics, which ends up having a direct impact on the composition of their legais systems, which comprise the same hybrid structure. With the colonial process, common law and civil law legal families were introduced in Africa, which were maintained in the post-independence period, thus resulting in an intersystemic conflict between positivist state law and African rights - and, in some states, Islamic law (Sharia). Faced with this truculent relationship, this research proposes, firstly, recognising procedural and procedural legal pluralism, in order to ease this conflict between the two orders, in which positive law claims to be hegemonic and monistic, limiting the manifestations of customary rights. It should be noted beforehand that this research is particularly focused on Portuguese-speaking African countries, whose legal constitution formally recognises legal pluralism, but from a purely substantive perspective, i.e. without clear methods for making legal pluralism effective, either in the institutional sphere or in the procedural dimension, capable of integrating community courts and traditional authorities in a functionally dialogical and plural environment. In addition, the research sought to analyse the way in which community courts that express the concrete manifestation of legal pluralism operate, having analysed countries such as Mozambique, Cape Verde, Guinea-Bissau and, in a modest way, Angola. The advantages of community courts for access to justice were described, as well as their inherent limitations with regard to certain fundamental rights and guarantees that are at risk of being violated, such as due process, denial of formal equality for women and children's rights. To this end, the possibility of supervising these courts and involving professional judges in cases of great magnitude was proposed. It is worth mentioning that the post-positivist paradigm was brought into the discussion as a mechanism for overcoming pure positivism, admitting a correction of the law by morality, in the sense proposed by Robert Alexy (2009) and with argumentative nuances compatible with the African reality, presented in the third chapter in which the issue of the crisis of positivism on the African continent is discussed. It should also be noted that this work includes an argument for the possibility of constitutionalising Ubuntu as a constitutional principle, part of African rights, constituting a mechanism for the incorporation and plural codification of African values into state norms. In addition to what has already been said, the issue of the effectiveness of fundamental rights, especially women's rights, was analysed, highlighting the viability of a feminist constitutionalism that strives for gender justice in Africa, especially on issues concerning reproductive rights and access to the same opportunities. Finally, the model of constitutional courts and their role in guaranteeing and promoting fundamental rights were described.
Keywords: Community courts; Constitucionalismo - África; Direitos humanos; Human rights; Justiça tradicional; O processo histórico do constitucionalismo africano; Pluralismo jurídico; Pluralismo jurídico procedimental; Procedural legal pluralism; Traditional justice; Tribunais comunitários

The Position of General Principles of Law in the Interpretation of Treaties - Hajjar, Mahmoud; Zamani, Seyed Ghasem (Public Law Researsh, 2023)
The interpretation of treaties is particularly important in the field of treaty law, as in most cases it is not possible to apply treaties without their interpretation. In addition to the text and context of the treaty, the relevant rules of international law, including the general principles of law, can play an important role in the interpretation of treaties. A treaty is a creation of the international legal system, and its interpretation and implementation should be carried out within the context of the legal system that governs it. The main question to which this research intends to answer is: What is the position of general principles of law in the interpretation of treaties? It seems that the use of general principles of law in the interpretation of treaties can reduce the potential fragmentation of international law and promote its coherence. In this research, by using library sources, international documents and international judicial decisions and arbitration awards and using a descriptive-analytical method, the position of general principles of law in the interpretation of treaties will be examined.
Keywords: Article 31 (3) (C) of the Convention of the Law of Treaties; General Principles of Law; International Jurisprudence; Interpretation of Treaties; Systemic Integration

Le droit applicable sur le chèque dans l’espace de l’Union économique et monétaire Ouest africaine (UEMOA) - Coulibaly, Souleymane S; Gakou, Kissima (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
L’Union Economique et Monétaire Ouest Africaine (UEMOA), en tant qu’organisation internationale, a été consacrée dans la Zone Franc en vue d’atteindre des objectifs de développement économiques et sociaux. Dans le but de créer entre eux une Union Economique d’une part, et un espace juridique uniforme d’autre part, les auteurs respectifs des traités de Dakar, a institué des communautés supra nationales dotées d’attributions propres et de pouvoirs réels découlant du transfert de souveraineté de leurs États membres. Il est évident que l’intégration juridique est un support non négligeable de l’intégration économique. The West African Economic and Monetary Union (UEMOA), as an international organization, was established in the Franc Zone with a view to achieving economic and social development objectives. With the aim of creating between them an Economic Union on the one hand, and a uniform legal space on the other hand, the respective authors of the Dakar treaties, established supranational communities endowed with their own attributions and real powers arising from the transfer of sovereignty of their member states. It is obvious that legal integration is a significant support for economic integration.
Keywords: Chèque (droit); UEMOA; WAEMU

La règlementation de la circulation des armes légères dans la CEDEAO - Sissoko, Abdoulaye; Timbine, Hamidou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Il ne saurait y avoir une force sans l’union ou la communion d’où l’adage « l’union fait la force », et l’intégration est le moyen le plus adéquat et parfait pour atteindre cet objectif. L’intégration se définit comme la fusion de certaines compétences étatiques dans un organe super étatique ou supranational et le droit de l’intégration est l’ensemble des règles juridiques qui régissent les organisations d’intégration régionale. La Communauté Economique des Etats de l’Afrique de l’Ouest (CEDEAO) étant un organisme d’intégration régional, est une organisation intergouvernementale ouest-africaine créée par le traité de Lagos du 28 mai 1975, lequel a été révisé par celui d’Abuja de 1993. C’est la principale structure destinée à coordonner les actions des pays de l’Afrique de l’Ouest. Son but principal fixé est de promouvoir la coopération et l’intégration avec pour objectif assigné de créer une union économique et monétaire ouest-africaine. Dans un monde où la paix est une « valeur suprême, le mythe fondateur d’une société internationale organisée » et ou le développement des foyers de tension s’opère de manière contagieuse, la lutte contre la prolifération des armes légères apparait comme une impérieuse nécessité.
Keywords: Arme légère (circulation); CEDEAO; Droit communautaire; ECOWAS; Regulation; Réglementation; Weapon

La rénovation des cadres juridiques de gouvernance foncière dans les pays en développement : étude de cas croisée du Niger, d'Haïti et de l'Afrique du Sud - Pennec, Jérôme (Université de Bretagne Occidentale, 2023)
Le travail de recherche examine les processus d’élaboration et de mise en œuvre de nouveaux cadres juridiques de gouvernance foncière dans les pays en développement. Par le biais de trois pays d’étude de contextes juridiques, historiques et culturels très différents, à savoir le Niger, Haïti et l’Afrique du Sud, l’analyse met en évidence que les réformes foncières dans les pays en développement sont confrontées à certaines problématiques juridiques et difficultés de mise en œuvre communes. Elle démontre les limites des modèles classiques et techniques de gouvernance foncière, ainsi que les failles du cadre international et l’influence de l’aide internationale en la matière. Elle souligne également l’importance de prendre en considération les multiples pratiques sociales en lien avec l’accès et l’usage des terres, qui dépassent largement la seule notion classique de propriété. Sur la base de ce constat, la thèse établit que la prise en compte des pluralités juridiques est un élément clé pour envisager la rénovation des cadres juridiques du foncier, mais que cette étape à elle seule n’est pas suffisante pour créer un système efficient de gouvernance foncière. Il apparaît ainsi nécessaire de penser l’organisation de ces pluralités au sein d’un véritable système pluraliste ordonné. L’analyse évoque les éléments concrets de mise en application de ce concept à des échelles nationales. This paper examines the design and implementation processes of new legal frameworks for land tenure in developing countries. In the light of three case studies with different legal, historical and cultural contexts – namely Niger, Haïti and South Africa – the study shows that they all face the same legal and implementation challenges while carrying out such reforms. The study highlights the limitations of classical and technical land tenure governance models as well as the weaknesses of the international framework and the influence of international assistance on this subject. Moreover, it demonstrates the need to consider the different social practices of land access and use, which go beyond the sole notion of land property. Building on this assessment, the study shows that the examination of legal pluralim is fundamental to consider the reform of land tenure’s legal frameworks, even though this step is not sufficient to create an efficient system for land tenure governance. It seems thus necessary to think the organization of these pluralities within a truly pluralist and ordered system. The study puts forward concrete, hands-on elements for implementing this concept at national levels.
Keywords: Afrique du Sud; Developing countries; Gouvernance foncière; Haïti; Land reform; Legal pluralism; Niger; Pays en développement; Pluralisme juridique; Réforme agraire; South Africa

La répartition des compétences entre la CEMAC et ses États membres - Allamaye Golbey, Levi (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2023)
The Uniform Act relating to the law of commercial companies and of economic interest groups contains numerous references to the concept of act, without the legislator being able to specify its meaning. This legislative silence is the pretext for the doctrine to give this notion several perceptions, without any of them being able to give its full dimension in isolation. Beyond this polysemy, it is revealed through the notion of act, a plurality of purposes that the legislator intends to assign to it in company law, by making it an instrument at the service of the partners and third parties. In relations between partners, the concept of act ensures an objective of regulating relations when the legislator requires, both in the phases of incorporation and of the functioning of the company, that the acts be coated with the seal of authenticity and that they are carried out according to the required standards. The OHADA legislator also invokes the concept of acts when it comes to ensuring the third party who comes to deal with the company or its members the protection of his interests. From this point of view, the prerequisite required for such an act to achieve this objective is compliance with certain conditions. Otherwise, when we analyze the regime for the resumption of acts performed during the period constituting the commercial company and certain situations, we are reinforced in this idea of protection assigned to the concept of act.

Genre et gouvernance dans l’émergence de la CEEAC - Alima Tolo, Marie-Micheline (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
La présente contribution trouve son fondement sur l’hypothèse selon laquelle pour atteindre l’émergence escomptée en 2025 et rendre ses économies plus résilientes et plus attractives, les États de la Communauté Économique des États de l’Afrique Centrale (CEEAC) doivent prendre en compte le genre. Il ne s’agit pas de conjuguer avec le tout-venant pour une participation numérique, mais de composer avec des citoyens outillés, conscients de leur rôle et des enjeux qui nécessitent leur action. Cette réflexion explore ainsi de manière conjointe les pans de la gouvernance et de l’économie, qui constituent les piliers du développement. Elle met au cœur de son mouvement la formation de toutes les composantes de la population, l’accent étant davantage mis sur les femmes, véritable capital qui tend à être mal exploité, car confinées dans un espace où elles ne laissent pas éclore l’étendue de leurs talents. La réalité est que, la marginalisation et l’ostracisme constituent des goulots d’étranglement dans une dynamique évolutionniste et ne sauraient de ce fait servir les intérêts des Etats engagés. Ces réalités réductrices de l’efficacité tous azimuts sont non conformes à l’esprit d’émergence dans le sens qu’ils musellent considérablement les ressources capables d’impulser une réelle dynamique développementaliste en les rendant inopérantes. D’où l’urgence d’une approche inclusive.
Keywords: Emergence; Entrepreneuriat; Entrepreneurship; Gender; Genre; Gouvernance; Governance; Inclusion

Coopération et intégration sous régionale : l’Afrique Centrale au tribunal de la raison - Boulingui Moussavou, Alain (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
Cette analyse discute les questions de coopérations et d’intégrations que connaît l’Afrique centrale à l’aune du transhumanisme. La coopération et l’intégration visent la compréhension interétatique en vue de renforcer la solidarité et la fraternité. Pour faciliter cette coopération et les intégrations, les responsables politiques de l’Afrique centrale et des grands lacs qui partagent une destinée commune vont, pour leur progrès social, économique et politique, se munir d’organisations sensées faciliter l’intégration. Cependant, force est de constater que la mise en pratique des mécanismes d’intégration contraste avec la dynamique de coopération politique.
Keywords: Afrique centrale; Coopération; Développement; Institutions; Intégration

La problématique de la question migratoire dans les espaces CEDEAO et CEMAC - Cissé, Salif (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
Cet article abordera les causes profondes des migrations forcées dans les espaces CEDEAO et CEMAC. Les conflits, l’insécurité, la dégradation de l’environnement et la pauvreté constituent des causes profondes des migrations de masse et des déplacements forcés en dans les espaces CEDEAO et CEMAC. L’inégalité mondiale, le manque d’emploi et de travail décent, la pauvreté, les conflits, les inégalités entre les sexes et la discrimination, le terrorisme et les pressions climatiques continuent de pousser les gens à rechercher une vie meilleure à l’étranger. Les flux mixtes composés de différents types de migrants et de demandeurs d’asile qui utilisent les mêmes voies et moyens de migration, sont revus à la hausse.
Keywords: CAEMC; CEDEAO; CEMAC; ECOWAS; Inégalité mondiale; Migrant; Migration

Les Communautés économiques régionales, améliorent-elles le commerce intrarégional dans le cadre de la ZLECAf ? - El Bekri, Hafsa (Revue Interventions économiques, 2023)
Cet article examine l’impact des facteurs de proximité sur l’intensité commerciale intra africaine. Dans le cadre des modèles reposant sur une approche ex post, notre contribution concerne l’usage d’un modèle de gravité avec la prise en compte des distances géographiques et économiques. Nos résultats montrent que les niveaux d’intégration commerciale contrastés au sein des CER risquent d’accentuer l’asymétrie d’intégration continentale, ils révèlent que la distance économique impacte positivement et significativement l’intensité des échanges et suggèrent le renforcement de l’intégration via les chaines de valeur régionales. This article examines the impact of proximity factors on intra-African trade intensity. Our contribution consists of the use of a gravity model with the consideration of geographical and economic distances. Our results show that the contrasting levels of trade integration within the RECs are likely to accentuate the asymmetry of continental integration, they reveal that economic distance has a positive and significant impact on the intensity of trade and suggest the strengthening of integration through regional value chains.
Keywords: AfCFTA; Afrique; Bilateral intensities; Commerce intra-régional; Communautés économiques régionales; Facteurs de proximité; Intra-African trade; Modèle de gravité; Proximity factors; Regional integration

Pour la constitutionnalisation des ordres juridiques communautaires en Afrique de l’ouest francophone : le cas de l’ordre juridique UEMOA - Essenouwa, Kodjo Tognissé (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
La constitutionnalisation des ordres juridiques communautaires s’affiche comme une alternative crédible aux conflits des normes inter-systémiques dans l’espace juridique ouest-africain francophone. L’hypothèse a l’avantage de faire intégrer les normes communautaires au bloc de constitutionnalité et, ce faisant, constitue l’opportunité de faire du juge constitutionnel non seulement un garant potentiel de l’application du droit communautaire mais aussi un interlocuteur probable des Cours de justice communautaire. Heureusement, il existe dans le constitutionnalisme d’Afrique de l’Ouest francophone des moyens juridiques de sa concrétisation.
Keywords: Community legal order; Constitutionalization; Constitutionnalisation; Norm; Norme; Ordre juridique communautaire

L’Organisation pour l’harmonisation en Afrique du droit des affaires en quête de règles uniformes de droit international privé : état des lieux et perspectives - Marque, Étienne (Les Cahiers de droit, 2023)
L’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) s’est depuis peu engagée sur la voie de l’uniformisation des règles de droit international privé de ses États membres. Une telle entreprise est sans précédent pour cette organisation. Pour la première fois en trois décennies d’existence, le domaine de l’uniformisation ne sera en effet pas celui de l’arbitrage ou du droit substantiel des affaires, mais celui du traitement des relations d’affaires ayant des éléments de rattachement avec plusieurs ordres juridiques. Ce projet d’acte uniforme est bienvenu à plus d’un titre. Il comblerait d’abord un déficit patent de règles de droit international privé dans un espace qui intègre pourtant 17 États, et qui est donc propice aux relations d’affaires internationales. En oeuvrant désormais à l’articulation des lois et des juridictions nationales de ses États membres, le droit OHADA prendrait de surcroît le contre-pied de son approche traditionnelle qui consistait jusqu’alors à les neutraliser. Plus qu’un nouvel acte uniforme, ce projet constitue donc un important changement d’orientation pour l’OHADA.

Recueil de textes communautaires sur la libre circulation et le droit d'établissement - Union Economique et Monétaire Ouest Africaine (UEMOA, 2023)

Bilan de l’OHADA et pertinence actuelle de ses objectifs - Djeufo Tsafack, Jimmy Achille (International Multilingual Journal of Science and Technology, 2022)
Près de trois décennies après sa création, l’OHADA justifie d’une expérience qui mérite d’être mise à contribution dans l’élan d’évaluation de son bilan et de la pertinence de ses objectifs basiques eu égard à la configuration actuelle des affaires dans le monde. L’organisation a en effet suscité beaucoup d’espoir, notamment pour le développement économique des États d’Afrique subsaharienne qui sont par ailleurs majoritairement des États membres. Face à la crise économique criarde, les initiateurs de l’OHADA ont cru bon de mettre en place des instruments juridiques et judiciaires à même d’attirer les investisseurs et booster le développement économique de l’Afrique. Le présent article de doctrine se propose dans une approche juridique et empirique, de faire un bilan de l’OHADA tout en questionnant la compatibilité de ses objectifs face aux mutations contemporaines du droit des affaires impliquant une vision beaucoup plus globale que communautaire, L’analyse part d’une identification des types d’objectifs qui sont tantôt juridiques et tantôt économiques pour nuancer la réflexion afin d’aboutir au constat selon lequel, même si des avancées considérables sont notables dans la poursuite des objectifs juridiques, il reste que, plus globalement, sur l’objectif général d’impulsion du développement économique des états membres, plusieurs lacunes doivent être franchies. En conclusion nous avons proposé des solutions juridiques pour une meilleure consolidation de l’espace judiciaire OHADA et une prise en compte plus importante des considérations extra financières afin d’adapter les objectifs de l’organisation à la configuration actuelle de l’économie globale et une implication plus importante des multinationales étrangères dans la construction infrastructurelle et économique des états membres. Toutes ces solutions juridiques et empirique permettront à coup sûr d’impacter beaucoup plus significativement le développement économique des états membres.

The application of knowledge stylised facts in West Africa Economic and Monetary Union (WAEMU) - Amanzou, Nogbou Andetchi Aubin; Ballo, Zie; Troupa, Sery Guy Flavien (Journal of Innovation and Entrepreneurship, 2022)
Sub-Saharan Africa has one of the dynamic economies in the world. Unfortunately, the performance achieve has not led to a reduction of social issues. So, the government are making massive investment to overcome social issues. This massive public investment highlights the exogenous nature of the current economic growth. So, a change of the strategy in the economic management of sub-Saharan Africa is required. One solution remains the change of economic paradigm: the transition from exogenous economic with decreased return to endogenous economic with increased return. The theoretical explanation of such arguments are supported by New Growth Theory. However, the implementation of the new theory required compliance to a set of indicators known as stylized facts. In 2009, Romer and Jones have developed a list of stylized corresponding to the need of New Growth Theory. The stylized facts of the West African Economic and Monetary Union (WAEMU) have been compared to the standard facts of Romer and Jones in order to apply the recommendations of New Growth Theory in this area. To reach that aim, the stylized facts have been described and analysed with econometric panel model. As result, we find that the description of the stylized facts in WAEMU fitted perfectly with that of Romer and Jones for the same period. Unfortunately, when using data, institution don’t work as expected by Romer and Jones. This study strengthens the argument for the implementation of economic policy based on the valorisation of knowledge economic in WAEMU.
Keywords: Africa; D83; Economic development; Economic growth; Knowledge economic; Macroeconomic Analyses; N17; O11; O17; O40

La complexité d’intégration des Etats africains en droit international privé - Masaba Yamba, Delphin (International Journal of Social Sciences and Scientific Studies, 2022)
Il sied de préciser que cette réflexion a eu pour mérite, le plaidoyer pour l’intégration des Etats africains qui passerait forcement par les règles de droit international privé au travers le moyen de l’harmonisation des celles-ci. Cela permettrait de retenir un rattachement simple pour chaque règle de conflit notamment les cas des statuts personnel et réel dont la complexité n’est pas à démontrer, celui-ci (le rattachement) doit répondre d’une localisation scientifique du rapport de droit c’est-à-dire neutre et objective. Le rattachement doit nécessairement se traduire sous la forme des liens les plus étroits pour répondre du principe de proximité qui dirige toute idée de localisation spatiale. En sus, sa détermination sera nécessairement concrète afin de répondre du réalisme de chaque situation internationale. Afin de bannir tout risque d’arbitraire et d’insécurité juridique, chaque catégorie de rattachement devra être dotée d’un faisceau d’indices propres à la nature du rapport de droit en cause et sur la base duquel le juge pourra déterminer quantitativement la loi compétente. Ainsi, l’intégration des Etats sera possible et il sera envisageable d’aspirer à un système universel ou continental à l’avenir.
Keywords: Droit international privé; Intégration

Texte introductif. Regards croisés sur « l’espace économique francophone » - Meszaros, Thomas; Dang, Hong Khanh (Revue internationale des francophonies, 2022)
La Conférence des chefs d'État et de gouvernement des pays ayant en commun l’usage du français à Québec en 1987 évoque pour la première fois un « espace économique francophone » ou une « francophonie économique ». Ces formules renvoient à la dimension économique de la langue française dans la mondialisation, au poids que constituent l’ensemble des personnes qui parlent le français dans le monde (francophonie) et les États qui sont membres de l’OIF (Francophonie). Depuis cette date, la nécessi...

Pour une uniformisation du droit des affaires dans l’espace économique francophone d'Afrique : que peut la francophonie ? - Hilim, Tchamyèlaba (Revue internationale des francophonies, 2022)
Un droit uniforme « unique » des affaires pour un espace économique « unique » construit autour d’une langue unique sur un continent « unique » : l’Afrique. Tel est l’objectif « unique » qui peut être assigné à la Francophonie. La quête est noble mais la route est longue et sinueuse pour parvenir à faire conjuguer les efforts d’intégration économique et juridique. La Francophonie qui a déjà fait ses preuves, dans le processus de construction de l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA), peut encore contribuer à l’uniformisation du droit des affaires en Afrique. Pour avoir contribué à la naissance de l’OHADA, notamment lors de la signature du traité fondateur dans l’environnement du sommet de la Francophonie tenu à Maurice le 17 octobre 1993 et à travers la signature du traité révisé, en marge du Sommet de la Francophonie à Québec le 17 octobre 2008, la Francophonie est un allié historique. Toutefois, pour y parvenir, il ne faudrait pas perdre de vue les limites d’un système dépendant essentiellement d’une langue « unique », dans une Afrique « unique » par sa diversité linguistique, juridique, économique, politique et culturelle. De même, l’action de la Francophonie centrée sur la construction d’un marché commun dans l’espace francophone africain semble occulter le volet juridique. Or, le développement économique recherché pour l’espace économique francophone de demain doit pouvoir, pour son efficacité et même sa survie, s’appuyer sur un cadre juridique matériel applicable aux activités économiques de l’espace. Dans un tel contexte où le cadre juridique commun des affaires se heurte encore à l’hérésie de certains États qui rechignent à s’associer et où le droit matériel des affaires est encore balkanisé à travers une multiplicité de regroupements régionaux ou sous-régionaux qui se partagent des pans entiers du droit des affaires, une synergie des actions s’impose. C’est là tout le défi de l’uniformisation du droit des affaires en Afrique que la Francophonie devrait aider à relever. La présente réflexion, qui s’aligne dans cette dynamique, se veut une feuille de route de l'uniformisation complète du droit des affaires en Afrique en général et en Afrique francophone en particulier.
Keywords: Adherence; Adhésion; Business law; Droit des affaires; Extension; Francophonie; Standardization; Uniformisation

Integração regional africana : panorama, avanços e desafios - Assis, Caroline Chagas de; Ribeiro, Renata Albuquerque; Garcia, Ana Saggioro (Boletim de Economia e Política Internacional, 2022)
O regionalismo é a forma pela qual os Estados-nação procuram solucionar questões políticas e econômicas no nível regional, tradicionalmente vinculadas à promoção do livre-comércio e à superação de conflitos interestatais. Para os países menos desenvolvidos, o regionalismo é percebido como um mecanismo estratégico de desenvolvimento. Diante dos processos de independência, as iniciativas de integração africanas começaram a ser pensadas e fundadas de forma concomitante à formação dos Estados-nação no decorrer do século XX. Isso faz da integração do continente africano um processo particular. Este trabalho faz uma análise do desenho institucional e do grau de institucionalização das principais organizações regionais africanas, enfatizando seus objetivos e seu papel para a integração continental e oferecendo um histórico de criação dos mecanismos de integração que culminaram na formação da União Africana (UA), a principal organização de integração do continente. Aborda, ainda, a institucionalização dos dois principais e mais recentes mecanismos de desenvolvimento da UA, a Agenda 2063 e a Área Continental de Livre-Comércio Africana (African Continental Free Trade Area – AfCFTA) e apresenta uma análise institucional das oito comunidades econômicas regionais (CERs) reconhecidas pela UA, as quais atuam junto à organização de forma colaborativa, a fim de promover uma integração ampla. Por fim, realiza uma síntese com apontamentos sobre as principais dificuldades, desafios e avanços dessa complexa estrutura de integração regional.
Keywords: AfCFTA; Integração regional; Organizações internacionais; União Africana

L'intégration régionale africaine et ses problèmes - Kabanda Mashini, Mashini; Makolo Makopo, Célestin (International Journal of Social Sciences and Scientific Studies, 2022)
L’intégration économique est un facteur déclencheur du développement des Etats membres d’une communauté économique. Apres l’indépendance des pays africains, la volonté de créer une structure d’intégration régionale a caractérisé, plusieurs acteurs africains parmi lesquels ; KHRAME KRUME …, c’est cette volonté, qui justifie la prolifération des organisations internationales africaines à caractère d’intégration. On peut citer ici ; l’UEMOA, CIMA, OHADA, CEMAC…, Cependant, plusieurs problèmes bloquent l’émergence de cette intégration économique, surtout au niveau régional. Ces problèmes sont entre autre ; l’attachement des Etats à leurs souverainetés, la diversité linguistiques, héritage de la colonisation. Voilà pourquoi, dans le cadre de cette recherche nous proposons, que les Etats membres de l’Union africaine puissent céder, plusieurs attributs de leurs souverainetés au profit d’une organisation d’intégration globale comme le cas avec, l’Union Européenne. Cette solution débouchera, à l’ouverture des barrières douanières des Etats membres, ce qui va donner lieu, à la zone de libre-échange continentale, comme est la volonté actuelle de l’Union Africaine, Union douanière, Union monétaire, jusqu’à l’union économique.
Keywords: Barrières douanières; CEMAC; CIMA; Intégration régionale; OHADA; UEMOA; Zone de libre échange

Le Gouvernement Congolais et la mise en œuvre du droit OHADA en République Démocratique du Congo - Badjela Dengba, Thomas-R. (Mouvements et Enjeux Sociaux, 2022)
La République Démocratique du Congo a adhéré à l’OHADA en date du 11 juillet 2012. Le Traité, les Règlements d’application et les Actes uniformes sont entrés en vigueur le 12 septembre 2012. Il faudra rappeler ici que cette adhésion est consécutive à la loi n° 10/002 du 11 février 2010 autorisant l’adhésion de la RDC au Traité du 17 octobre 1993 relatif à l’harmonisation du droit des affaires en Afrique. A la suite de cette adhésion, plusieurs mesures ont été prises par le Gouvernement de la RDC pour assurer la mise en œuvre de l’OHADA. La présente réflexion passe en revue certaines de ces mesures en vue d’apprécier leurs incidences dans la sécurité juridique et judiciaire de la RDC.

La sécurité juridique dans l’insertion du droit d’origine externe dans les Constitutions des États de la CÉMAC - Mairema, Jacqueline (Revue Africaine des Réflexions Juridiques et Politiques, 2022)
L’analyse de la sécurité juridique dans l’insertion du droit d’origine externe dans les constitutions des États de la CEMAC permet de démontrer l’affirmation de la garantie relative de la sécurité juridique dans les mécanismes d’insertion. Cette garantie est tantôt affirmée, tantôt atténuée. Cela est affirmée à travers la variété d’insertion octroyant des droits aux sujets du droit d’origine externe et quant à la place déterminante du parlement et du juge dans le processus d’insertion. Mais cela demeure atténuée car la non-accessibilité des citoyens au droit d’origine externe ainsi que l’incohérence des exigences d’application du droit d’origine externe constituent une source d’insécurité juridique. En tant que procédure permettant aux normes d’origine externe d’intégrer l’ordonnancement juridique interne tout en leur octroyant une validité, l’insertion du droit d’origine externe constitue une exigence favorable à la sécurité juridique.
Keywords: Droit d’origine externe; Insertion; Monisme; Sécurité juridique

Relationship between International and Domestic Law in the Constitutions of the States of the Economic and Monetary Community of Central Africa - Mairema, Jacqueline (Journal of Law and Criminal Justice, 2022)
The purpose of this paper is to analyze the constitutional provisions relating to the relationship between international law and domestic law of the States of the Economic and Monetary Community of Central Africa reveals an ambivalent conception of the system relationships. This is all the more true since the choice of monism with primacy of international law is affirmed both formally and materially. Even if this variant of monism seems to be tempered by certain constitutional provisions, the treaties have considerable effects in the domestic legal order. Once integrated into the legal order through the modalities of insertion, treaties have a supra-legislative and infra-constitutional rank. However, some constitutions of the States of the Economic and Monetary Community of Central Africa, such as Gabon and Equatorial Guinea, have not enshrined constitutional provisions on the place of treaties in the legal order. The concern to safeguard the supremacy of the constitution and consequently of national sovereignty may justify such a constitutional practice.
Keywords: Droit d’origine externe; Dualism; Insertion; International law; Monism; Monisme; National law; System relationship; Sécurité juridique

Rising from its ruins? The Southern African Development Community (SADC) Tribunal - Shumba, Tapiwa (Law, Democracy and Development, 2022)
The Tribunal of the Southern African Development Community (SADC) was established to ensure adherence to and the proper interpretation of the provisions of the SADC Treaty and its subsidiary instruments, and to adjudicate upon such disputes as might be referred to it. However, since its establishment, it has had a troubled history. After the rulings it made against the Government of Zimbabwe in the landmark Campbell land seizures case, the Tribunal's operations were unceremoniously suspended. This was followed by a process to revise its mandate, one that ultimately condemned it to paralysis and ruin. The new 2014 Protocol on the Tribunal, meant to revise the mandate of the Tribunal to confine it to hearing disputes involving states only, has been criticised as an attempt to undermine the rule of law and human rights in the region. Since the adoption of this 2014 Protocol by the SADC Summit, stakeholders have mobilised regionally to resist its ratification by member states. In particular, lawyers in SADC countries are embarking on legal petitions to reverse the Protocol and promote the revival of the Tribunal in terms of its old mandate. So far, there have been victories in these cases in two influential SADC member states, South Africa and Tanzania. However, it remains important to assess the significance of these developments. As such, the article raises the question: Is the Tribunal rising from its ruins?
Keywords: Regional integration; Rule of law; SADC Tribunal

Nomenclature Tarif Extérieur Commun : Règles générales pour l’interprétation du Système harmonisé - Union Economique et Monétaire Ouest Africaine (UEMOA, 2022)

Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

Mondialisation et harmonisation : vers l’émergence d’un cadre normatif à caractère régional des affaires Africain. Cas Maroc-OHADA - Rabhi, Tauofik (Annales de l’Université d’Alger, 2021)
Partant du constat que le droit est un phénomène social, l’harmonisation des législations apparaît indispensable au développement de zones économiques d’échange comme le sont la Communauté européenne et l'Accord de libre-échange nord-américain. Harmoniser, c’est dégager des directions et des orientations communes, établir des principes et des règles de base communs. En effet, dans un contexte de mondialisation et de globalisation il s’est opérées de grandes mutations économiques contemporaines modifiant ainsi les conditions du développement de certains pays africains, incitant désormais un mouvement d’intégration juridique en fonction des facteurs économiques, politiques, sociaux voire stratégique. Sur le plan économique, il y un rapprochement juridique visant l’harmonisation des législations et une intégration juridique qui s’est manifestée par une ouverture vers l’extérieur adoptant une politique de libéralisme économique. Le Maroc, de part son positionnement géographique a exprimé son désir de faire partie de ce rapprochement juridique on exprimant sa volonté à adhérer à l’OHADA.

Le mimétisme juridique dans le droit de l'OHADA - Leyo, Desmond Vidor (Université Toulouse 1 Capitole, 2021)
Au sens général, le mimétisme s’entend de toute reproduction des gestes, des attitudes d’autrui. En droit, le mimétisme est considéré comme la transposition de certaines règles juridiques d’un Etat vers un autre. Ainsi, l’objectif général de la réalisation de notre recherche vise à étudier en quoi le droit de l’OHADA est dominé par une telle pratique dans l’édiction des Actes uniformes alors que la règle de droit doit être élaborée en fonction des besoins du peuple qu’elle est destinée à régir. La mondialisation de l'économie exige l'harmonisation des droits et des pratiques du droit. Cette exigence constitue pour des pays en développement comme les nôtres une priorité pour créer les conditions favorables à l'instauration d'un espace de sécurité juridique et judiciaire indispensable pour drainer des flux importants d'investissements, car investir est déjà en soi un risque, même s'il est calculé; s'il faut doubler ce risque premier inéluctable de celui d'un système juridique fluctuant, ondoyant et insaisissable, il n'y aura pas beaucoup de possibilités d’attirer des investisseurs. C’est dans cette optique que les Etats de l’Afrique francophone, notamment, ont pensé à juste titre élaborer une législation uniforme et moderne en vue de pallier les insuffisances et la vétusté des multiples législations nationales. En effet, le principal point faible du dispositif mis en place par l’OHADA réside dans son éloignement des réalités socio-économiques et culturelles africaines. Or, il est écrit dans l’esprit des lois que « les lois doivent être tellement propres au peuple pour lequel elles ont été faites, que c’est un très grand hasard si celles d’une nation peuvent convenir à une autre… ».Dans le même sens, le professeur Michelle Alliot affirmait que « le droit d’un pays est lié aux habitudes d’un peuple, à sa mentalité, à ses croyances religieuse, qu’il devrait être impossible d’appliquer aux peuples africains le droit de la France ».Ainsi, à l’examen de l’état de la législation de l’organisation pour l’harmonisation en Afrique du droit des affaires, la plupart des textes étudiés, notamment ses Actes uniformes, montrent que le droit de l’OHADA n’a pas répondu au souci de territorialité, autrement dit, aux réalités sociales des Etats membres. Il permet de constater que le législateur communautaire a transposé de façon « plagiaire » les prescriptions étrangères, notamment françaises, à l’occasion de ses interventions. Ce mimétisme juridique peut être expliqué, entre autres causes très diverses, par le « fait colonial » qui, quoique révolue politiquement, continue d’influencer beaucoup de pays africains dont les lois ne sont pas toujours en harmonie avec leurs réalités socio-économiques. Dans le cadre de l’OHADA, l’étude du mimétisme juridique pose la question relative à d’énormes difficultés que génère ce phénomène compliquant d’autant l’application du droit uniforme dans les pays membres. Malgré de nombreux handicaps ou difficultés qu’il engendre, le mimétisme juridique dans le droit de l’OHADA a une portée qui peut s’avérer très considérable car il est considéré comme une méthode de construction de ce droit. L’objectif de notre thèse est non seulement de montrer ou démontrer l’existence du mimétisme juridique dans l’espace OHADA, les faiblesses ou handicaps qu’il y présente ou qu’il y génère, les atouts qu’il peut y marquer, mais également son devenir ou son avenir en termes de vivacité.
Keywords: CCJA; Cour Commune de Justice et d'Arbitrage; Institutions politiques; Législateur; Pays de l'OHADA

Le système juridique unitaire à l’épreuve du droit coutumier : la nécessité d’une territorialisation du droit - Guémar, Carine (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The unitary legal system vs. customary law: the need of territorialization. The French State is a unitary State as opposed to federal States, in which there is one Constitution providing for provisions applicable throughout the territory of the French Republic. Unity can be found in a legal unity first, in this the unitary Law is the one that does not admit of territorial differenciation. A political and organic unity, since there is only one Parliament, one Government. A social unity eventually, which consists of the admission of a single French people. If the French tradition is based on a centralized system, the implementation of the process of territorial decentralization led to reconsider the uniformity of the Law precisely with the question of territorial differenciation and territorialisation of Law. The present study proposes to return to the consideration by unitary Law of local territories including the overseas territories with the problem of reconciling such a system with customary Law.
Keywords: Customary Law; Overseas territories; Territorial decentralization; Territorialisation of Law; Unitary Law

La rupture du dialogue entre la Cour Constitutionnelle du Bénin et la Cour de Justice de l’UEMOA : retour critique sur une saga juridictionnelle inédite - Dabiré, Cyriaque Téonvièl (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2021)
Par la succession de leurs décisions dans l’affaire Éric DEWEDI, la cour de justice de l’UEMOA et la cour constitutionnelle du Bénin sont entrées dans une logique de rupture, là où la prudence jurisprudentielle était pourtant nécessaire. Par ce conflit juridictionnel inédit, les juges antagonistes ont plus démontré leur volonté de faire prévaloir leur ordre juridique sur celui de l’autre que celle de véritablement résoudre la cause qui leur a été soumise. En conséquence, deux principes inconciliables ont été érigés : le principe de la supraconstitutionnalité du droit communautaire revendiqué par le juge communautaire et le principe de la ‘supracommunautarité’ du droit constitutionnel consacré par le juge constitutionnel béninois. Pourtant, cette remise en cause de la hiérarchie des normes était évitable. Through their decisions on Eric DEWEDI case, the court of justice of West African Economic and Monetary Union and the Constitutional Court of Benin fail to comply with their obligation to judicial prudence. The situation reveals more their intention to make their legal orders prevail on each other than to solve the case. Subsequently, the court of justice affirms the principle of supraconstitutionality of the community law while the constitutional court surprisingly enshrines the principle of infraconstitutionality of the community law. Although, this contradiction was avoidable, following the derogatory clause contained in the community norm.
Keywords: Bénin; Community judge; Constitutional judge; Droit communautaire; Droits fondamentaux; Fundamental rights; Hiérarchie des normes; Infraconstitutionality; Infraconstitutionnalité; Interpretation; Interprétation; Juge communautaire; Juge constitutionnel; Prevalence; Primauté; Supraconstitutionality; Supraconstitutionnalité; UEMOA; WAEMU

L'Intégration juridique et le développement économique : contribution à l'analyse économique du droit OHADA - Diawara, Mamadou (Université Cheikh Anta Diop, 2021)
Keywords: Droit OHADA (analyse économique); Développement économique; Intégration juridique

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

Afri̇ka Ülkeleri̇ Hukuku Düzenlemeleri̇nde İrade Muhtari̇yeti̇ - Dürgen, Betül (Africania, 2021)
Çağdaş hukuk düzenlerinde geniş yankı uyandıran irade muhtariyeti ilkesi, kimi zaman maddi hukuk hükümlerinde sözleşme özgürlüğü olarak kendini belli ederken kimi zaman da milletlerarası özel hukuk alanında taraflara hukuk seçimi imkânı ile gündeme gelmektedir. Bazı ülkelerin sınırlandırdığı ölçüde serbest ekonomik düzenlerine dahi etki eden irade muhtariyeti ilkesi, hukukların yeknesaklaştırıldığı kadarıyla uygulanabilir hale gelmektedir. Çalışmamıza konu olan Afrika kıtası ülkelerinde, hukukun yeknesaklaştırılması gereği bölgede anlaşılmış olup gerekli adımların atıldığı OHADA kanunları ile açığa çıkarılmıştır. Bunun dışında yer yer milletlerarası özel hukukta genel olarak kabul görmüş bağlama noktaları dışına çıkan ülke bazında uygulamaların söz konusu olduğu da görülmektedir. Çalışmamızın amacı irade muhtariyeti prensibinin milletlerarası özel hukuka yansıması olan hukuk seçiminin Afrika’da uygulanabilir olup olmadığını tespit etmektir. Bu tespiti yapmak Afrika ülkelerindeki çeşitli uygulamaların çağdaş düzenlemeler ile karşılaştırılmasını gerektirmiştir
Number: 1
Keywords: OHADA; Party autonomy; applicable law; choosing law; hukuk seçimi; irade muhtariyeti; milletlerarası özel hukuk; private international law; uygulanacak hukuk

L'influence de l'Union européenne sur les processus d'intégration en Afrique de l'Ouest - Sow, Abdoulaye (Université Jean Moulin Lyon 3, 2021)
L'Union européenne exerce une influence active et une influence passive sur les organisations régionales africaines. L'influence active résulte de l’action extérieure de l'UE. L’Union s'emploie, par le biais ses relations conventionnelles, à exporter son modèle et à assurer la promotion de ses valeurs. L'influence passive est, quant à elle, plutôt une influence subie. C'est une influence voulue et désirée par les organisations régionales africaines. Cette influence n’est pas imposée ou exercée, elle découle de la force d'attraction du modèle européen. En effet, l’Union européenne, en dehors de toute politique conventionnelle, est objet de fascination. Ce sont ces deux formes d'influence qu'aborde cette étude. L'objectif central de la recherche est d'interroger les similitudes, mais aussi de questionner la pertinence de la transposition du modèle européen dans un environnement autre que le sien. Les logiques d'intégration n’étant pas identiques, les organisations régionales africaines optent pour un mimétisme juridique et institutionnel limité. The European Union exerts both active and passive influence on African regional organizations. The active influence results from the EU's external action. The EU is working towards, through its conventional relations, to export its model and promote its values. Passive influence, on the other hand, is rather a suffered influence. This is an influence wanted and desired by African regional organizations. This influence is not inflicted, imposed or exerted; it derives from the attraction of the European model. Indeed, the European Union, besides any conventional policy, is object of fascination. It is these two forms of influence that this study addresses. The central objective of the research is to question the similarities, but also to question the relevance of the implementation of the European model in an environment other than its own. Since the logics of integration are not identical, African regional organizations opt for limited legal and institutional mimicry.
Keywords: Active influence; African community law; Attraction; Communauté économique des États de l'Afrique de l'Ouest; Contribution économique et politique; Cooperation; Coopération; Droit; Droit communautaire africain; Droit communautaire européen; Droit de la CEDEAO; Droit de l’UE; Droit de l’UEMOA; Droit européen; ECOWAS law; EU law; Economic and political contribution; European community law; Force de séduction; Grafting and rejection; Greffe et rejet; Imitation; Import; Importation; Influence; Influence active; Influence passive; Institutional and legal mimicry; Mimétisme institutionnel et juridique; Passive influence; Relations extérieures; Reprise; Régionalisme (politique internationale); Seductive strength; Transposition; Union européenne; Upturn; WAEMU law

Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması - Babayev, Ilgar (İstanbul Ticaret Üniversitesi, 2021)
Uluslararası ticaretin gelişimi ve artması dünyadaki bütün devletler tarafından hedeflenen bir amaçtır. Ancak devletlerin ulusal hukuk sistemleri arasındaki farklar bu gelişim için belirli engeller oluşturmaktadır. Bu engelleri aşmak için uluslararası ticaret hukukunun yeknesaklaştırılması, yani aynı uluslararası hukuki işleme uygulanacak iki veya daha çok ulusal hukuk sisteminin farklı kurallarının bir kuralla değiştirilmesi çare olarak görülmektedir. Bu amaçla şimdiye kadar bir çok çalışmalar yapılmış ve bir çok yeknesaklaştırma aracı ortaya konulmuştur. Uluslararası ticaret hukukunun bel kemiğini oluşturan uluslararası ticari sözleşmeler alanında hazırlanmış olan yeknesaklaştırma araçları ise bu bakımdan özellikle önem taşımaktadır. Hukukun yeknesaklaştırılması alanında çalışmalar sürdürülmekle birlikte bu konuya şüpheyle bakanlar ve yeknesaklaştırmanın kendi amacına ulaşamayacağını düşünenler de mevcuttur. Bu yeknesaklaştırma sürecinde ortaya çıkan bir takım sorunlarla ilgilidir. Ancak özellikle de uluslararası ticaret hukuku alanında yapılan yeknesaklaştırma çalışmalarında elde edilen başarılar umut vaat etmektedir. Uluslararası ticari sözleşmeler hukuku alanında yapılmış olan ayrı ayrı yeknesaklaştırma çalışmaları ile ilgili araştırmalar mevcut olsa da, konuyu daha kapsamlı bir şekilde ele alan ve meseleye daha geniş bir perspektiften bakan araştırmaların eksik olduğunu görmekteyiz. Özellikle de Türkiye'de bu tür araştırmalarda bir boşluğun mevcut olduğu hissedilmektedir. Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması amacıyla ortaya konulmuş çalışmaların ve hazırlanmış olan araçların daha kapsamlı bir şekilde araştırılması, onların sağladığı faydaları göstermek, bu alanda ortaya çıkan sorunları belirlemek ve gerekli çözüm önerileri sunmak açısından önem arz etmektedir. Bütün bunları dikkate alarak biz bu araştırmamızda uluslararası ticaret hukukunun yeknesaklaştırılması kavramını, onun önemini ve sağladığı avantajları, yeknesaklaştırmanın gerçekleştirilmesi yöntemlerini, uluslararası ticaret hukukunun yeknesaklaştırılması alanında çalışmalar yapan ve bu sürece katkıda bulunan uluslararası kurumları, uluslararası ticari sözleşmeler alanında yapılmış olan ve şu an yapılmakta olan çalışmaları, bu konuyla ilgili ortaya çıkan sorunları ve bu sorunların ortadan kaldırılması için sunulan çözüm önerilerini incelemeye çalıştık. [...] The development and growth of international trade is an aim targeted by all states in the world. However, the differences between the national legal systems of states pose certain obstacles to this development. To overcome these obstacles, the unification of the international commercial law is considered a remedy, that is, changing the different rules of two or more national legal systems to be applied to the same international legal process with one rule. For this purpose, so far many studies have been done and many unification instruments have been introduced. The unification instruments prepared in the field of the international commercial contracts, which form the backbone of international commercial law, are particularly important in this regard. Although studies on the unification of the law continues, there are also those who are skeptical about this issue and those who think that it cannot achieve its own goal. It concerns a number of problems that arise in the process of unification. However, the successes achieved in the unification studies especially in the field of international commercial law promise hope. Although there are researches on individual unification studies in the field of international commercial contracts law, we see that there is a lack of research that covers the issue more extensively and looks at the issue from a wider perspecitve. Especially, a vacancy in this kind of research is available in Turkey. It is important to investigate the studies and the instruments that have been prepared for the purpose of the unification of the international commercial contracts law, to show their benefits, to identify the problems that arise in this field and to offer necessary solutions. Considering all these, in this research, we tried to examine the concept of the unification of the international commercial law, its importance and advantages, the methods of realization of unification, the international institutions that work in the field of the unification of the international commercial law and contribute to this process, the problems that arise about this issue and the proposed solutions to eliminate these problems.
Keywords: Hukukun Yeknesaklaştırılması; International Commercial Contracts Law; International Commercial Law; International commercial contracts; Lex Mercatoria; Uluslararası Ticaret Hukuku; Uluslararası Ticari Sözleşmeler; Uluslararası Ticari Sözleşmeler Hukuku; Unification Instruments; Unification of Law; Yeknesaklaştırma Araçları

Harmonization (or rather Standardization) of Cooperative Law in the OHADA Zone: What is the Result after Ten Years of Implementation of the Uniform Act? - Tadjudje, Willy (CIRIEC - España. Revista jurídica de economía social y cooperativa, 2021)
The Uniform Act related cooperative societies (UA-COOP) is the main source of cooperative law in all the seventeen States parties to the OHADA founding Treaty. Ten years after its entry into force (2011-2021), the aim of this study is to assess the level of enforcement of this Act. More concretely, the aim is to compare the state of cooperative law at the time of the entry into force of the UA-COOP (2011) with the current situation (in 2021). Such a comparison should make it possible to assess the contribution of the UA-COOP to the development of cooperative law and strengthening of national cooperative movements in the OHADA zone.

Economic Community of West African States at forty-five: a fool at forty-five a fool forever? - Nwosumba, Victor (African Journal of Politics and Administrative Studies, 2020)
Amid COVID-19 pandemic lockdown in the year 2020, Economic Community of West African States hereafter called ECOWAS quietly celebrated its forty-five years of establishment. Widely, much was not heard of or written about the community probably due to the challenges of the pandemic. However, the address of the President of ECOWAS Commission to the staff of ECOWAS institutions on the occasion of the commemoration of the community’s forty-fifth anniversary serves as a reminder that attention should also be given to this regional giant against all odds. Thus, the purpose of this paper is to celebrate ECOWAS at forty-five and then examine whether it is a fool at forty that is proverbially referred to as a fool forever. The paper, through thorough examination of the data collected from secondary sources finds that ECOWAS is still far from achieving its main mandate, its achievements as orchestrated by His Excellency, the President notwithstanding. The paper argues that the postponement of the establishment of ECO, a common currency for the region for the sixth time from 2020 to yet to be announced date, lack of realistic free movement of persons and goods among members and selfish interests of its leaders in the guise of national interest are enough reasons to conceive ECOWAS as a fool at forty-five. With the aid of constructivist theory,it concludes that even if ECOWAS at forty-five is still fooling around it has the chances of not being a fool forever if the leaders should turn a new leaf and pursue the attainment of the community’s mandate before its fiftieth anniversary.

Entrepreneuriat territorial agricole et intégration régionale en zone CEMAC - Djatcho Siefu, Donald; Neba Yah, Cletus; Njocke, Martin (Revue des Études Multidisciplinaires en Sciences Économiques et Sociales, 2020)
L’objectif de cette recherche est de démontrer qu'il est possible de promouvoir l’entrepreneuriat territorial (ET) agricole capitalisant les opportunités de la CEMAC. la méthode hypothético déductive est appliquée au cas de PIDMA. Les résultats prouvent que le PIDMA dispose des capacités de promouvoir un entrepreneuriat territorial agricole capitalisant les opportunités de la CEMAC sous certaines conditions.
Keywords: Chaîne des valeurs; Entrepreneuriat territorial; Intégration régionale; Marchés agricoles

La hiérarchisation entre les normes des organisations internationales africaines de droit public quant à leurs applications - Halirou, Abdoul-Karim (International Multilingual Journal of Science and Technology, 2020)
L’établissement de la hiérarchie entre les normes de l’organisation continentale africaine (UA) et celles des communautés d’intégration régionales et/ou sous régionales (CIRS), ou entre les normes de ces dernières, est tout aussi complexe. Cette complexité est liée à leur spécificité, notamment leur autonomie. En fait, chacune de ces organisations est dotée d’un ordre et d’une personnalité juridiques propres, les permettant d’agir indépendamment des autres. En principe et sous réserve des dispositions de l’article 103 de la charte des Nations Unies, il est quasi impossible d’établir une priorité entre les normes des organisations internationales en générales. Toutefois, cette priorisation peut être possible en cas d’antinomie portant sur la même matière et impliquant l’application d’une norme au détriment d’une autre. À cet effet, la convention de vienne sur le droit des traités a émis, les modalités de cette hiérarchisation. Il en est de même de la doctrine, qui a dégagé d’autres solutions techniques à savoir, la détermination de la priorité d’application à partir des modes d’adoption des normes, mais aussi à partir de la portée desdites normes.
Keywords: African international organizations; Application; Droit public; Hierarchy; Hiérarchisation; Normes; Organisations internationales africaines; Public law; Standards

The Effectiveness of the Harmonization Tool Adopted Under the Ohada Regime - Ceesay, Buba (Social Science Research Network, 2020)
The Organization for the Harmonization of Business Law in Africa, OHADA, is a regional entity whose primary objective is to harmonize the Business Law of its members. It has adopted legislative measures and institutional setups to ensure the realization of this object. This paper critically examined the effectiveness of the harmonization tool adopted under OHADA. The paper first gives a brief overview of OHADA setups, then the advantages and shortcomings of the harmonization tool adopted under the OHADA regime and finally concluded that though OHADA is a major step towards the attainment of harmonization of business law and Integration with the view of fostering development and business activities, its harmonization tool is lacking full efficacy towards the attainment of the objectives of the organization due to prevailing limitations and challenges.
Keywords: SSRN

Le cadre juridique de la libre circulation des biens et des services dans la Communauté économique de l’ASEAN - Chhak, Limcheang (Université Côte d'Azur, 2020)
La recherche a essayé d’affiner les phénomènes juridiques de la libéralisation des biens et des services, dite de première génération, en faveur d’une politique d’intégration économique régionale, sous l’emprise de la mondialisation, afin d’établir la Communauté économique de l’ASEAN. Cependant, la question de l’existence des règles substantielles de droit est sous-estimée au regard des juristes internationaux, et est pertinente pour l’Association ; autrement dit, l’ASEAN se fonde principalement sur le soft-law, ASEAN Way, qui a ralenti effectivement la réalisation de sa politique d’intégration économique. Afin de surmonter de ces défis, cette thèse a opté une approche de droit international public afin d’examiner le mécanisme d’élaboration des règles conventionnelles ainsi que non conventionnelles de cet Association. De plus, le droit international économique est également un choix méthodologique pour ce travail de recherche sur les questions techniques essentielles dans le processus de la création du marché unique de l’ASEAN. En résultat, nous avons découvert que le droit matériel de l’ASEAN est bien existé et continue à développer progressivement au sens propre du droit international. D’ailleurs, les mécanismes institutionnels administratifs ainsi que juridictionnels sont été observés dont leur fonctionnement est impliqué de manière pragmatique pour la mise en œuvre de ces règles matérielles en matière de la libre circulation des biens et services. Malgré que ces règles de droit connaissent les critiques tant à ses effectivité et efficacité à cause de sa caractère souple et non contraignant, l’harmonisation juridique sectorielle est achevée vers la direction de la construction du droit communautaire de l’ASEAN. En conclusion, la régionalisation économique de l’ASEAN se fonde effectivement sur son cadre juridique propre, en basant sur le pluralisme juridique et est conforme au droit international. Research has tried to refine the legal phenomena of the liberalization of goods and services, known as first generation, in favor of a regional economic integration policy under the influence of globalization, in order to establish the ASEAN Economic Community. However, the question of the existence of substantive rules of law is underestimated in the eyes of international lawyers and it is relevant. In other words, ASEAN is mainly based on soft law, namely ASEAN Way, which has effectively slowed down the implementation of its economic integration policy. In order to overcome these challenges, this thesis opted for an approach of public international law in order to examine the mechanism of formation of conventional as well as non-conventional rules of this in ASEAN. In addition, international economic law is also a methodological choice for this research work on essential technical questions in the process of creating the ASEAN Single Market. As a result, we have discovered that ASEAN substantive law does exist and continues to develop gradually in the proper sense of international law. Moreover, the administrative as well as jurisdictional institutional mechanisms have been observed, their operation of which is implicated in a pragmatic manner for the implementation of these material rules regarding the free movement of goods and services. Despite the fact that these rules of law are criticized both for their effectiveness and efficiency because of their flexible and non-binding nature, sectoral legal harmonization is complete towards the direction of the construction of ASEAN Community Law. In conclusion, the economic regionalization of ASEAN is effectively established on its own legal framework, based on legal pluralism and is consistent with international law.
Publication Title: theses.fr

The OHADA Structure as a Possible Model for the Development of a Commercial Law Structure in the Southern African Development Community (SADC) - Leno, Ngaundje Doris (International Journal of Social Sciences and Management Review, 2020)
The Southern African Development Community's (SADC) colonial legacy which introduced foreign legal traditions and the consequences of the diversity heighten the urgency for unified commercial legislation to deal with cross-border disputes.Thus, the issue is whether the Organisation for the Harmonisation of Business Law in Africa (OHADA) structure can serve as a possible model for the development of a uniform commercial law structure in the SADC .Despite the success of the OHADA, the author submits that the OHADA can only serve as a source of inspiration, or roadmap, providing guidance to the SADC drafters.The paper aims at demonstrating that the OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC.The significance of this paper lies in the contributions it makes to the development of a commercial law structure in the SADC.
OpenAlex: https://openalex.org/W3124748692
Keywords: Development; Integration; Model; OHADA; SADC

Desafios da cooperação intra-regional e perspectivas da integração tripartida entre SADC-EAC-COMESA : avaliação das implicações para SADC - Banze, Vasco Alberto (Universidade Federal do Rio Grande do Sul, 2020)
A Integração Tripartida entre Comunidade de Desenvolvimento da África Austral (SADC), Comunidade da África Oriental (EAC) e Mercado Comum de África Oriental e Austral (COMESA) é uma inciativa de Chefes de Estado e de Governos das três Comunidades Económicas Regionais (CERs) em integrar seus separados programas numa única área de livre comércio. A iniciativa enquadra-se no contexto do Plano de Acção de Lagos (1980) e do Tratado de Abuja (1991) que consideram as CERs como pilares para criação da Comunidade Económica Africana (CEA). A Tese tem como principal objectivo analisar os desafios da cooperação intra-regional e perspectivas da integração tripartida entre SADC-EACCOMESA. Com base na pesquisa qualitativa coadjuvada pelas técnicas documental e bibliográfica constatou-se que a construção dos processos de integração regional na SADC e EAC evoluiram de padrões de confrontação para cooperação enquanto a COMESA foi por excelência um espaço priviligiado para cooperação comercial. Ainda assim, as três CERs enfrentam mesmos desafios relacionados com a sobreposição dos Estados membros, proliferação de “esquemas informais” de integração regional, dependência das CERs em relação aos doadoers internacionais, fragmentação de mercados nacional e regional e a prevalência da vontade de Estados membros sobre processos de integração regional. Face a estes desafios, a implementação da integração tripartida gera dúvidas e incertezas.
Accepted: 2020-12-17T04:09:38Z
Keywords: COMESA; Desenvolvimento regional; EAC; Integração regional; SADC; Tripartite integration

Le droit issu de l’Organisation pour l’harmonisation en Afrique du droit des affaires et les sociétés africaines : regard critique sur une illustration du déni de l’essence culturelle du droit - Bepyassi Ouafo, Vicaire (Les Cahiers de droit, 2020)
Le droit originaire du traité de l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA), applicable au sein des sociétés africaines de cet espace, manifeste actuellement des pesanteurs liées à son enracinement culturel non africain. En effet, les sociétés africaines signataires dudit traité ont décidé en 1993 d’élaborer un droit commun des affaires simple, moderne et adapté pour faciliter le développement de leurs économies. Elles ont, à ce jour, adopté dix actes uniformes qui régulent certains domaines des affaires en vue de réaliser la croissance économique prévue dans le traité. Cependant, la démarche empruntée à cet effet est confuse. D’une part, l’option pour l’uniformisation, au mépris de l’harmonisation attendue des phénomènes culturels africains, et, d’autre part, la transposition dans les sociétés africaines des modèles juridiques occidentaux, notamment les pratiques du droit international, amènent à douter de l’inspiration africaine du droit de l’OHADA. Un quart de siècle après, son bilan n’est pas flatteur et ne permet pas de préjuger de la satisfaction des objectifs du traité. En outre, la révision du traité à Québec en 2008 pour un meilleur ancrage culturel africain de ses normes révèle indubitablement l’intérêt d’asseoir l’essence culturelle du droit.

Algeria and the African Union - between security and economic integration: a neofunctionalist and regionalist reading - Lamri, Amel (Canterbuy Christ Church University, 2020)
This thesis investigates the process of integration in the African Union (AU), and the reasons behind the slow progress of the AU to achieve the goal of deeper economic integration. In the research I explore the role of an AU member state in the process of African integration: Algeria. The research scrutinises the development of Algerian foreign policy towards the AU and highlights any changes in the Algerian FP attitudes and the reasons behind these changes. Similarly, the research unveils the reality of the decision-making process in this country, and the different agents that influence it. To achieve the main goals of the research, different theoretical choices were elaborated. This resulted in researching European integration theories; Neofunctionalism was, then, selected to study the Algerian development in the making of its foreign policy in general and towards the African Union specifically. Some concepts within the Neofunctionalist thinking were used including the principle of the shift of loyalties, the socialisation process, the spillover system, and the role of interest groups in the process of integration. Moreover, the theory of Regionalism was used to examine the process of integration in the AU discovering new reasons that led to the slow development of economic integration in Africa. Consequently, the research highlights the current obstacles and challenges that have hindered the process of economic integration in the AU, including the poverty of most of the AU member states, the limited financial budget of the Union and the instability of the majority of African countries. Furthermore, the research unveiled the lack of political will towards AU economic integration plans. Hence, this contribution extends beyond the traditional models of explanation, and discusses the situation in AU member states (in this case Algeria) and points to other factors as well such as the weakness of the lobbyist activities and business groups in Algeria specifically and Africa more generally. The thesis, then, focusses on Algeria’s supportive and active status in the AU security sector, highlighting how Algeria has been successful in pushing its own security and antiterrorism agenda to the AU level, thereby demonstrating that integration into the AU is possible, if it is backed by influential member states, and wider coalitions can be built to promote integration and cooperation.
Permalink: https://repository.canterbury.ac.uk/item/8y60y/algeria-and-the-african-union-between-security-and-economic-integration-a-neofunctionalist-and-regionalist-reading
Keywords: Africa Union; Algeria; Intégration régionale

The role of the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) in facilitating continental integration - Luthuli, Isaac (University of KwaZulu-Natal, 2020)
The dissertation examines the role the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) can play in facilitating the political and economic convergence of the African Union (AU) member states. The developmental challenges facing Africa in spite of its wealth of human and natural resources is poignant. The genesis of this problem can be traced to the history of colonialism and the wave of independence in the continent in the late 1950s. Arguments have been put forward to suggest that one of the most viable ways of promoting Africa’s development is by developing and promoting intra-continental trade which can be possible through continental integration. The specific areas reviewed are regional stability and how intra-regional trade and investment is used to promote economic convergence. Africa's need for political and economic integration at a continental level is further sustained by the assumption that neocolonialism can be blamed for the weakness of structures in African states. Some scholars agree on the idea that regionalisation is often seen to offer a possibility to respond to the challenges of globalization. This impact nevertheless is dependent on the relation between globalisation and regional sentiment. Regional integration implies a form of interdependence among nation-states. Such interdependence leads to an establishment of regional integration arrangements between sovereign states within a geographical space. These agreements are shaped formally and there is a commitment to work together in order to realise political and socio-economic benefits. This study maintains that in order to achieve effective integration of the continent, Nigeria and South Africa as case studies, as continental giants have a key role to play to this end and as members of ECOWAS and SADC respectively. It is argued here that both the SADC and ECOWAS as sub-continental blocks have made some notable and commendable progress in developing policies for trade liberalization and economic integration, this, however, is not enough as such policies are also pertinent at a continental level. The study found that SADC and ECOWAS as regional blocks can play a role in aiding the continent to achieve a trade liberalization to achieve continental economic development.
https://researchspace.ukzn.ac.za/handle/10413/18708
Keywords: African integration; ECOWAS; Economic Development; Economic convergence; Integration; Intra-continental trade; SADC

L’attractivité juridique et économique de l’OHADA - Mbow, Demba (Revue libre de Droit, 2020)

Vereinheitlichung des Wirtschaftsrechts in Afrika durch die OHADA - Monsenepwo Mwakwaye, Justin (Rabels Zeitschrift für ausländisches und internationales Privatrecht, 2020)

La contribution des juridictions communautaires au processus d’intégration sous-régionale en Afrique francophone - Sobze, Serge François (Revue Burkinabè de Droit, 2020)
La jurisprudence des juridictions communautaires contribue à affirmer l’idée selon laquelle le juge communautaire joue un rôle primordial dans la consolidation de la justice de l’intégration en Afrique. Il contribue à travers les fonctions contentieuses, consultatives et quasi-contentieuses à l’enracinement dans les ordres juridiques communautaires, d’une justice d’intégration accessible, efficace et de qualité. L’étude recherche dans la production jurisprudentielle, ce qui découle de la participation des juridictions communautaires, notamment des Cours de justice de la CEMAC et de l’UEMOA à la construction de l’intégration avec pour objectif de vérifier si le droit africain de l’intégration bénéficie de ces organes d’un même apport ou d’un traitement différencié. Il en ressort que les juridictions communautaires considérées jouent un rôle quasi similaire dans la régulation du processus d’intégration sous-régionale. En effet, il se dégage de leur politique jurisprudentielle une convergence des contributions au processus normatif primaire et une ambivalence des contributions au processus normatif dérivé de l’intégration. Par ailleurs, les décisions analysées restent fortement marquées par une asymétrie entre le contentieux socio-économique en plein essor et celui des droits fondamentaux resté en friche. En définitive, à travers une méthode juridique et une technique comparative des pratiques jurisprudentielles des organisations d’intégration, les juridictions communautaires contribuent de façon offensive à l’enracinement de « l’intégration par le droit » en Afrique en général et dans les Communautés sous-régionales envisagées en particulier. The case law of community courts helps to affirm that the community judge plays a key and primary role in consolidating integration justice in Africa. It contributes through its contentious, advisory and quasi-contentious functions to the establishment in community legal orders of accessible, efficient and high-quality integrative justice. These studies are to search in the case-law production, which results from the participation of community jurisdictions, in particular the Courts of Justice of CAEMC (Central African Economic and Monetary Community) and WAEMU (West African Economic and Monetary Union) in the construction of integration with the aim of verifying whether African law of the integration benefits from these bodies from the same contribution or from differentiated treatment. As a result, the community jurisdictions are considering playing an almost similar role in regulating the process of sub-regional integration. Indeed, from their jurisprudential policy emerges a convergence of contributions to the primary normative process and an ambivalence of contributions to the normative process derived from integration. The decisions indeed analyzed remain strongly marked by an asymmetry between the booming socio-economic litigation and that of fundamental rights which has remained unexplored. In conclusion, through a legal method and a comparative technique of the jurisprudential practices of integration organizations, community jurisdictions contribute in an offensive way to the entrenchment of "integration through law" in Africa in general and particularly the sub regional communities.
Keywords: African integration law; Community courts of justice; Community law; Contentieux; Cours de justice communautaires; Droit africain de l’intégration; Droit communautaire; Institutional process; Integration through law; Intégration par le droit; Litigation; Material process; Processus institutionnel; Processus matériel

L'OHADA à la croisée des systèmes juridiques : contribution à l'étude du phénomène d'hybridation du droit - Ngah Noah, Marcel Urbain (Annales africaines : Revue de la Faculté des Sciences Juridiques et Politiques de l'Université Cheikh Anta Diop de Dakar, 2019)
Keywords: Hybridation du droit; Intégration juridique; Système juridique

Contribution à l'étude des nouvelles règles d'intégration au niveau de la CEMAC - Ngolali Ngoulou, Wilfried Rigobert (Université Paris Cité, 2019)
Après l'échec de l'UDEAC et des politiques communes destinées à réaliser l'union douanière entre les États de l'Afrique centrale, ces derniers se sont atteler à remettre en question toutes les politiques d'intégration économique engagées depuis leur accession à la souveraineté internationale. L'analyse des causes de cet échec les a ainsi conduit non à abandonner l'idéal communautaire, mais à relancer ce dernier sur de nouvelles bases. De ce fait, l'objectif de la présente étude est de mettre en lumière les changements et évolutions juridiques, politiques et socio-anthropologiques que connaît la Communauté Économique et Monétaire de l'Afrique Centrale constituant ainsi comme notre problématique, l'a fait ressortir tout au long de ce travail un baromètre efficace de l'analyse du nouveau régionalisme économique entre les pays de l'Afrique centrale. En dépit des multiples politiques sectorielles mise en oeuvre par l'institution commune et dont on ne pourra mesurer la contribution à l'intégration des économies de la sous-région qu'à moyen voire long terme, l'adoption puis la mise en oeuvre de nouvelles règles communes d'intégration régissant le marché commun en construction entre les États membres est une parfaite illustration des nouveaux choix opérés par la sous-région. Notamment ceux consistant à faire du droit comme nous l'avons démontré chapitre après chapitre le moteur essentiel de la réalisation des objectifs communautaires qu'ils se sont assignés. After the failure of the UDEAC and common policies intended to achieve the customs union between the States of Central Africa, these latter are engaged to question all economic policies of integration adopted since their attainment of the international sovereignty. The analysis of causes of this failure led them not to abandon the Community ideal, but to revive it on new bases. In fact, the aim of this study is to put in light the changes and legal, political and socio-anthropological evolutions that meet the Economic and Monetary community of the Central Africa considered like our problematic, has emphasized it throughout this work as an effective barometer of the analysis of the new economic regionalism between the countries of central Africa. In spite of the multiple sectorial policies implemented by the common institution and which one will be able to measure the contribution to the integration of the economies of sub region only in medium or long term, the adoption and then the implementation of common new rules of integration governing the Common Market under setting-up between the Member States is a perfect illustration of the new choices made the sub region. Notably, those consisting in making common law as we have proved it from chapter to chapter the essential driving force of the realization of the Community objectives that they set themselves.
Keywords: 1966-1998; Afrique centrale; BCAS; BEAC; CJCEMAC; Central Africa; Central Africa monetary and economic Union; Common market; Communauté Economique et Monétaire de l'Afrique Centrale; Community tax of integration; Customs and economic union of Central Africa; Economic integration; Institutional reform; Intégration économique; Intégration économique internationale; JCEMCCA; Marché commun; Processus d'intégration CEMAC; Réforme institutionnelle; Taxe communautaire d'intégration; Union douanière et économique de l'Afrique centrale; Union économique et monétaire de l'Afrique centrale; Zone de libre échange; Zone of free trade

La protection communautaire de l'environnement dans le cadre de l'UEMOA : enjeux, portée et perspectives - Savadogo, Yacouba (Université de Limoges, 2019)
L’Union économique et monétaire ouest-africaine (UEMOA), instituée en 1994, est l’une des plus jeunes organisations d’intégration économique en Afrique de l’Ouest. Mise en place à un moment où tous les voyants sur la gestion durable des ressources naturelles sont déjà allumés, elle n’a pourtant pas explicitement consacré la préservation de l’environnement dans son Traité constitutif.Le droit dérivé de l’UEMOA, qui tend à combler les lacunes de son droit primaire, est malheureusement pris en otage par des procédures complexes et longues, maintenant au stade de projets inachevés la plupart des cadres juridiques initiés. Pour se hisser au rang des institutions modernes déterminées à allier économie et écologie, entreprise certes ardue mais indispensable, l’UEMOA devrait réviser son droit primaire pour y inscrire la préservation de l’environnement et le développement durable comme l’un de ses objectifs essentiels. Elle devrait également accélérer l’adoption finale de ses nombreux projets de textes juridiques relatifs à la protection de l’environnement au sein de l’Union. The West African Economic and Monetary Union (UEMOA), established in 1994, is one of the youngest economic integration organizations in West Africa. Set up at a time when all the lights on the sustainable management of natural resources were already on, it has however not explicitly enshrined the preservation of the environment in its Constitutive Treaty.UEMOA’s secondary law, which tends to fill in the gaps in its primary law, is unfortunately held hostage by complex and lengthy procedures. Thus, most of the legal instruments being developed remain at the stage of unfinished drafts. To rise to the rank of modern institutions committed to reconciling economy and ecology, a difficult but necessary undertaking, UEMOA should revise its primary law to include the preservation of the environment and sustainable development as one of its essential objectives. It should also speed up the final adoption of its many draft legal texts on the protection of the environment within the Union.
Keywords: Afrique du Nord-Ouest; Autonomie institutionnelle; Community environmental law; Community justice; Droit; Droit communautaire; Droit primaire; Environnement; Institutional autonomy; Justice communautaire; Primary law

La contribution des techniques juridiques dans la consolidation de l’intégration économique en zones CEMAC et UEMOA - Bipelé Kemfouedio, Jacques (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2019)
L’intégration économique, en tant que processus de développement, vise à fusionner les économies de deux ou plusieurs Etats pour lutter contre la pauvreté et stimuler dans la zone concernée la croissance économique. Pour que cet objectif de croissance soit atteint, le processus d’intégration économique doit reposer sur des bases juridiques solides issues de l’uniformisation ou de l’harmonisation normatives. Ces deux techniques juridiques constituent le point d’ancrage et la clé de succès de tout processus d’intégration économique. C’est conscients de cette situation que les Pères fondateurs de la CEMAC et de l’UEMOA, dans le souci d’instaurer dans leur Communauté ou Union un développement équilibré et durable, ont fait de l’uniformisation et de l’harmonisation, deux techniques juridiques de consolidation de l’intégration économique.

A Comparative Study of ECOWAS and ECCAS towards Implementation of the Abuja Treaty - Nyasembi, Kevin Selassie (University Of Ghana, 2019)
The Abuja Treaty is the blueprint and reference point for continental-level economic integration that was first established in 1991 to see to the creation of an African Economic Community (AEC). The Treaty acknowledges that, the African continent, as a unified unit of countries, wields immense power in the international system, in terms of trade and political influence, and thus it seeks to bring to fruition a highly integrated Africa. This study strives to evaluate the progress made on the implementation of the Treaty Establishing the African Economic Community (AEC) by comparing two regional blocs, the Economic Community of Central African States (ECCAS) and the Economic Community of West African States (ECOWAS), which serve as 2 of 8 building blocks for the realisation of the AEC. Accordingly, the research method used was qualitative and employed a purposive sampling method that draws on the selection of experts in the field of regional integration to shape the outcome of the study. The research findings include the fact that regional integration, on the continent, has progressed positively although it manifests slowly. Additionally, it found that both the ECOWAS and the ECCAS have progressed in terms of the implementation of the stages of the Abuja Treaty, although the former surpasses the latter in this regard. Yet, in spite of their progress, both RECs have faced challenges unique to their regions. ECOWAS for instance faces the problem of inability to completely enforce protocols on free movement of persons. The lack of national implementation of free movement legislation creates avenues for its ineffectiveness. Border checks are commonplace and there is very little standardization of official forms. ECCAS on the other hand faces a problem of overlapping goals and ideas with CEMAC as well as the failure of member states to carry out agreed decisions within their states due to issues such as conflict and instability in the region. On a whole, the study refutes the common idea that the Abuja Treaty has not been implemented at all but only sees its implementation as slow-paced.

La contribution du juge communautaire à la construction du droit des organisations d'intégration en Afrique - Diallo, Mouhamadou (Université Cheikh Anta Diop, 2019)
Keywords: Afrique; Droit communautaire; Droit processuel; Droit substantiel; Intégration; Juge communautaire; Organisations régionales (droit)

Perspectives sur l’indépendance de la justice arbitrale en Afrique subsaharienne. Les influences croisées entre la Cour Commune de Justice et d’Arbitrage (CCJA) et l’East African Community’s Court of Justice (EACJ) - Bahalaokwibuye, Christian Bahati (KAS African Law Study Library, 2019)
Le présent article pose les perspectives sur les influences opportunes et mutuelles des systèmes arbitraux de la CCJA et l’EACJ dans la promotion de l’indépendance des arbitres. İl montre que, tout comme pour l’EAC, l’abitrage figure déjà dans le Traité de l’OHADA comme le mode de règlement des différends en vue d’améliorer le climat des investissements sur les territoires des Etats parties. La CCJA n’est pas un tribunal arb itral. Son intervention est placée en aval, comme juge de contrôle de la sentence bien qu’elle ne se contente pas d’un contrôle minimal. L’EACJ, qui a retenu l’option du cumul des fonctions de ses juges avec celles d’arbtres, pourra aussi, dans la moindre mesure, se contenter d’administrer les arbitrages ouverts conformément à son Règlement d’arbitrage. De ce point de vue, le système EACJ sera en parfait accord avec l’esprit du principe d’indépendance/ impartialité. En cette matière, nous pensons que la pratique de la CCJA ne manquera pas d’inspirer utilement des réformes du système d’arbitrage de l’EACJ, et qui révèle de plus en plus une prise de conscience certaine d'une croissante indépendance de ses arbitres en ayant opté pour la gratuité de l’arbitrage. Comme le Centre d’arbitrage de la CCJA est attaché à la Cour et que cette dernière est dotée d’une autonomie financière, il est temps de prendre des mesures de réduction de coût, non pas totalement analogues à celles de l’EACJ, à travers lesquelles on dispensera, par exemple les ressortissants de l’espace OHADA et les investisseurs étrangers, des frais administratifs de l’arbitrage. Il en résulterait un arbitrage sans influences, alternative crédible à la justice étatique qui affiche la lanterne rouge et facile d’accès aux justiciables impécunieux, qui rendra des sentences impartiales et légitimes.

Mobilités, dynamiques frontalières et intégration sous-régionale en zone CEMAC : le cas des commerçants de Kyé-Ossi - Mongbet, Abêt (Université de Poitiers, 2019)
La libre circulation en zone CEMAC est un long processus en Afrique centrale qui date de cinq décennies. Les pays membres de cette organisation sont toujours en tractation et font face à d'interminables signatures et accords y afférents. Son manque d'effectivité empêche les citoyens tels les Camerounais de migrer dans la sous-région, en l'occurrence vers le Gabon et la Guinée Equatoriale, très réticents à l'ouverture de leurs frontières aux ressortissants de la CEMAC. Ceux-ci justifient leur posture par une situation socioéconomique qu'ils entendent préserver. Le contexte limitatif rend pertinent le développement de stratégies de mobilité pour les acteurs migrants concernés. Des politiques migratoires contraignantes amènent ainsi les migrants venant du Cameroun à concentrer leur présence à la frontière commune à ces trois pays : Kyé-Ossi. Au fil du temps, cette localité de halte prolongée des migrants a connu une expansion spatiale rythmée par une croissance démographique issue principalement de la migration intérieure ; ce phénomène soutenu par le commerce développe et anime la coopération transfrontalière dans cette partie du monde. Du processus d'intégration fortement ralenti, on assiste ainsi à une dynamique frontalière grâce à l'anthropisation des migrants et aux actions étatiques de territorialisation qui accroissent davantage les mouvements humains vers cette frontière. A partir de Kyé-Ossi vont se développer de nouvelles expériences de migration et de mobilité. Grace à la dynamique familiale et de réseaux créée autour de la frontière, Kyé-Ossi devient une nouvelle base pour des mobilités internationales variées : courtes et longues durées vers le Gabon ou la Guinée Equatoriale, réseau pour l'immigration, zone de transit de longue durée pour une immigration ultérieure, réseau de passage et de chaine d'acteurs marchands pour d'autres camerounais à l'intérieur de ces pays. Les trois frontières se retrouvent ainsi habitées par les camerounais, lieux de vie où on observe une différenciation dans leur expression de citoyenneté en tant que Camerounais et ressortissants de la sous-région CEMAC. La démarche adoptée pour mener cette recherche mobilise un corpus méthodologique s'appuyant sur un travail de terrain initié depuis 2014. Il intègre à la fois des observations directes en contexte d'immersion, des administrations de questionnaires et entretiens auprès de cibles diverses. S'y ajoute un travail d'exploitation de supports écrits tels que les documents scientifiques, administratifs et médiatiques, ainsi que des images satellitaires. Les matériaux obtenus permettent d'interroger et d'apprécier les liens mobilités – dynamique sociospatiale dans un cadre pluri-frontalier – intégration sous-régionale. Elle vérifie l'hypothèse d'ouverture des frontières aux mobilités internationales du fait de la continuité territoriale produite par la dynamique frontalière et mobilitaire.
Keywords: CEMAC; Cameroon; Cameroun; Communauté Economique et Monétaire de l'Afrique Centrale; Dynamique sociospatiale frontalière; Equatorial Guinea; Gabon; Guinée équatoriale; Intégration sous-Régionale; Kyé-Ossi (Cameroun); Libre circulation des personnes; Migration; Mobility; Mobilité spatiale; Mobilités; Sociospatial border dynamic; Sub-Regional integration; Territorialité humaine

Bilan et perspectives de l'harmonisation du droit des affaires en Afrique - Diomansy, I. Sissoko (Université Cheikh Anta Diop, 2019)
Keywords: Afrique; Droit des affaires; Harmonisation; OHADA

Le droit des technologies de l’information dans la Communauté économique et monétaire de l’Afrique centrale - Bepyassi Ouafo, Vicaire (Les Cahiers de droit, 2019)
Les questions relatives à la portée économique des technologies de l’information à l’ère du numérique occupent désormais une place importante dans le droit des activités économiques au sein de l’espace de la Communauté économique et monétaire de l’Afrique centrale (CEMAC). En effet, le dispositif juridique encadrant les finalités économiques de l’utilisation des technologies du numérique dans la CEMAC mis en place en 2008 a aussitôt entraîné une modification du droit des affaires de l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) en 2010, dans l’intérêt de concilier les conséquences juridiques de l’économie numérique dans le développement économique. Toutefois, la problématique de la contribution du droit des technologies de l’information au développement économique de la CEMAC mérite d’être soulevée après une décennie d’application. Si la volonté du législateur communautaire de faire des technologies du numérique un levier du développement est perceptible à travers l’institution législative d’un marché numérique dans lequel la garantie des droits et la liberté des activités sont assurées, il faut encore relever sa témérité à travailler pour la sauvegarde de l’économie numérique par des règles particulières protégeant les consommateurs des services électroniques.
Keywords: CEMAC; TIC

L'effectivité des normes du développement durable dans le processus d'intégration en Afrique - Nono, Guy Marcel (Université Laval, 2019)
A priori, l’Union africaine, avec son programme pour le développement de l’Afrique connu sous le nom de NEPAD, peut être considérée comme un « moulin à prières ». Ce, en raison de nombreux documents internationaux adoptés à l’échelle régionale africaine, et de l’étroite marge de manoeuvre qu’a l’Union africaine pour trouver des solutions durables aux crises économiques et sociales qui secouent l’Afrique. Crises ayant des incidences sur l’environnement. En effet, depuis l’avènement de l’Union africaine, le développement durable est devenu dans les textes le principe directeur du processus d’intégration africaine. Cette étude analyse les efforts de l’Union africaine en vue de l’effectivité des normes du développement durable en Afrique, ainsi que la contribution de l’Afrique à l’évolution du droit international. L’analyse de l’effectivité des normes de développement durable à l’échelle régionale africaine s’est faite en deux étapes. Premièrement, on a analysé la positivité des normes africaines de développement durable dans l’ordre juridique africain au regard des standards internationaux en la matière. Deuxièmement, on a analysé la mise en oeuvre régionale des normes africaines de développement durable au regard des prescriptions des standards internationaux en la matière. Audelà de la priorisation de l’économique et du social, la façon dont l’Union africaine concilie les trois piliers du développement durable a été mise en relief. Ce travail contribue à mettre en lumière l’approche juridique de l’Union africaine vis-à-vis du développement durable, et montre comment ce concept se matérialise d’une façon particulière en Afrique. Elle analyse, d’une part, les initiatives de l’Union africaine pour traduire dans les faits les trois piliers du développement durable. Et, d’autre part, les obligations que l’Union africaine impose à ses États membres pour mettre en oeuvre ces piliers. Cette étude est également destinée à favoriser la compréhension de l’évolution de la notion de développement, de droit au développement, de développement durable, et elle met en évidence le lien entre le droit et le développement. Enfin, ce travail contribue à mettre en exergue les avancées du droit international sur la remise en cause de la notion de droit subjectif et la consécration de l’existence des « droits sans sujet » en droit international public, à travers le concept de développement durable.
https://hdl.handle.net/20.500.11794/34966
Keywords: Droit et développement; Droit international économique; Développement durable; Intégration économique; Normes; Union africaine

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification

Spécificités et enjeux de l'Union du Fleuve Mano (UFM) dans les dynamiques d'intégration régionales en Afrique de l'ouest (1959 à 2014) - Keita, Fodé Bangaly (Université Paris 7, 2018)
Après l’accession des pays Ouest-africains à l’indépendance, plusieurs alliances supranationales ont été scellées. Mais, la recherche de l’Union s’est faite dans une certaine contrariété idéologique car, il ya eu des panafricanistes et les chercheurs des Communautés Economiques Régionales parmi les chefs d’Etat. C’est dans ce contexte que trois organismes d’intégration firent leur apparition: il s’agit de l’Union du Fleuve Mano (UFM), la Communauté des Etats de l’Afrique de l’Ouest (CEDEAO) et la Communauté des Etats de l’Afrique de l’Ouest (CEAO), devenue l’UEMOA plus tard. L’UFM a été créé sur la base du voisinage géographique et en tenant compte des liens socioéconomique et culturel séculaires existant entre les peuplements identiques. Son but était de faciliter les transactions commerciales entre les populations se trouvant séparées par le tracé frontalier colonial. Mais, le vrai problème était la question de marchés. Face à la mondialisation, les pays relativement petits en termes de population ont souvent eu du mal à s’insérer dans l’économie mondiale. Ils s’organisaient au sein des ensembles de mise en commun des ressources. Cependant, de 1973 à 2014, l’UFM n’a pas réussi à transformer ses pays membres pour deux raisons : Premièrement, dans sa structure, au lieu de créer une commission régionale, les Etats membres ont mis en place un secrétariat général. Deuxièmement, en raison des crises sociopolitiques, les pays membres de l’UFM ont fait moins de réalisations concrètes. After the accession of the West African countries to independence, several supranational alliances were sealed. But, the search for the Union was done in a certain ideological contrariety because, there were panafricanists and the researchers of the Regional Economic Communities among the heads of state. It is in this context that three integration organizations emerged: the Mano River Union (UFM), the Community of West African States (ECOWAS) and the Community of West African States (ECOWAS). States of West Africa (CEAO), later became WAEMU. The MRU was created on the basis of geographical proximity and taking into account the centuries-old socio-economic and cultural links between identical settlements. Its purpose was to facilitate commercial transactions between populations separated by the colonial frontier. But, the real problem was the question of markets. In the face of globalization, relatively small countries in terms of population have often struggled to integrate into the global economy. They organized themselves in pools of resources. However, from 1973 to 2014, the UFM failed to transform its member countries for two reasons: First, in its structure, instead of creating a regional commission, Member States set up a general secretariat. Secondly, because of the socio-political crises, the MRU member countries have made less concrete achievements.
Keywords: Afrique occidentale; Intégration régionale; Intégration économique; Mano River Union; Regional integration; Union du Fleuve Mano; Économie régionale

L'harmonisation du droit pharmaceutique en Afrique de l’Ouest : le cas de l’UEMOA - Palgo, Diane Horélie (Bourgogne Franche-Comté, 2018)
La protection de la santé par l’instauration d’une sécurité sanitaire dépend largement d’une organisation du marché pharmaceutique et de l’instauration d’un marché pharmaceutique commun. En Afrique de l’Ouest, particulièrement au sein de l’UEMOA, l’absence d’un tel marché facilite l’essor du marché illicite du médicament et empêche une libre circulation des produits de santé entre les États membres. Pourtant, le développement économique implique un système de santé efficace et sécurisé. Progressivement, émerge une prise de conscience des États membres de l’UEMOA de la nécessité de conjuguer leurs efforts pour une meilleure protection de la santé ; l’intégration juridique ainsi recherchée pouvant se réaliser au travers de plusieurs moyens : l’harmonisation, l’unification et l’uniformisation. L’harmonisation est le moyen d’intégration juridique que l’UEMOA a choisi pour mettre en place des normes plus efficaces et plus élaborées. Le rapprochement par harmonisation des réglementations pharmaceutiques devient ainsi un objectif primordial, en vue de l’instauration d’une sécurité sanitaire dans la zone communautaire. Pourtant, cette harmonisation, pour atteindre son objectif d’amélioration des systèmes pharmaceutiques, suppose un cadre juridique élaboré. Un processus d’harmonisation est alors mis en place et concrétisé par l’adoption de plusieurs instruments juridiques communautaires : directives, règlements et décisions. Cependant, l’UEMOA n’est pas la seule organisation sous-régionale qui vise pour objectif l’harmonisation du droit pharmaceutique dans la zone. D’autres organisations régionales et sous-régionales telles que la CEDEAO et l’UA, dont sont membres les États de l’UEMOA, visent également un rapprochement par harmonisation du domaine pharmaceutique. S’ajoutent alors aux difficultés de fonctionnement, au niveau interne et communautaire, des obstacles externes liés à l’appartenance des États de l’UEMOA à ces deux organisations. Ces obstacles vont compromettre l’efficacité du processus d’harmonisation. Il s’ensuit alors une nécessité de revoir le choix de l’instrument juridique de rapprochement, quitte à s’aventurer vers un rapprochement mixte des réglementations pharmaceutiques par une combinaison de deux moyens d’intégration juridique : l’harmonisation et l’unification. Health protection, the setting up of health security highly depend on an organization of the pharmaceutical market by the establishment of a common pharmaceutical market. In West Africa, particularly within WAEMU, the absence of such of market eases the rise in illicit drug market and impedes a free movement of health products between States. Yet, economic development involves an effective and secured health system. WAEMU’s member States awareness is emerging gradually, hence the necessity to join forces for better health protection ; therefore the long-awaited legal integration can be done through several means ; harmonization, unification, standardization. Harmonization is the means of legal integration that WAEMU has chosen to set up more effective and elaborate standards. Reconciliation through the harmonization of pharmaceutical regulations therefore becomes a key objective, with a view to setting up health security within the community zone. Yet, this harmonization, to achieve its objective of improving pharmaceutical systems, implies an elaborate legal framework. A process of harmonization is therefore set up and materialized by the adoption of several community legal instruments : guidances ; regulations, decisions. However, it should be noted that WAEMU is not the only sub-regional organization that has objective the pharmaceutical right harmonization. Other regional and sub-regional organizations such as ECOWAS, AU, of which WAEMU States are member, target also a reconciliation by the harmonization of the pharmaceutical area. In addition to the operating difficulties, at internal and community level, there are some external impediments related to the belonging of WAEMU States to those both organizations. Those obstacles will jeopardize the effectiveness of the harmonization process. Consequently, it is necessary to reconsider the choice of reconciliation legal instruments, even if that means venturing into a mixed reconciliation of pharmaceutical regulations through a combination of two means of legal integrations : harmonization and unification.
Keywords: Afrique occidentale; Droit pharmaceutique; Harmonisation; Harmonization; Health security; Intégration juridique; Legal integration; Lois uniformes (gouvernement fédéral); Pharmaceutical right; Pharmacie; Risques pour la santé; Services de santé; Sécurité sanitaire; UEMOA; Unification; Unification internationale; Union économique et monétaire Ouest africaine; WAEMU

Le triptyque « ouverture commerciale, inégalités de revenus et croissance économique » : étude en donnée de panel pour le Maroc et les pays de la CEDEAO - Riad, Jamal; Lahmar, Anas (International Review of Economics, Management and Law Research, 2018)
Les économistes ont été intéressés abondamment à l’étude du triptyque « ouverture commerciale, croissance économique et inégalités », surtout suite à la montée en puissance des mouvements de la mondialisation. Leurs réflexions ont été basées sur les interactions bilatérales et sur les conclusions tirées des résultats empiriques. Compte tenu des approches de traitement adoptées, les résultats restent étroitement liés aux échantillons observés et aux variables utilisées. Ainsi, le triptyque reste absolument une question ouverte dont l’analyse n’est pas complètement inachevée. Afin de contribuer à ce débat, nous proposons d’étudier le triptyque pour un panel composé du Maroc et les pays de la CEDEAO. Ce choix trouve ses fondements dans les analyses engagées actuellement, sur les enjeux d’adhésion du Maroc à cette communauté.Au niveau méthodologique, notre choix s’est porté sur une approche basée sur l’économétrie des données de Panel et des méthodes d’estimation appropriées, notamment l’estimateur GMM En termes de résultats, l’étude présentée en trois grandes parties, montre que le degré de l’ouverture commerciale joue un rôle important dans la relance économique des pays en développement en synergie avec d’autres facteurs. En outre, les inégalités se révèlent catalyseur de la croissance économique, et n’ont pas empêché les pays étudiés de profiter partiellement de leur ouverture commerciale. De ce fait, l’investissement en développement humain se présente comme une nécessité pour ces pays, afin de tirer profit d’une croissance soutenu et susceptible de répondre aux aspirations sociales et économiques des citoyens.
Keywords: CEDEAO; Croissance économique; ECOWAS; Economic growth; Econométrie de Panel; Inequality; Inégalité; Maroc; Morocco; Ouverture commerciale; Panel Econometrics; Trade Opening

Le développement durable dans les traités régionaux africains d'investissement : cas de la CEDEAO et de la SADC - Koula, Bablésson Mardochée Désiré (Université de Bordeaux, 2018)
L’appréhension du tandem développement durable – traité d’investissement a longtemps été perçue sous l’angle de la contradiction. En effet, bien qu’il existe un consensus sur l’importance des investissements en tant que vecteur du développement durable, les seuls instruments internationaux qui leur sont spécifiquement dédiés [les traités d’investissement] font généralement peu, ou pas, cas de cet objectif ; ceux-ci étant conçus dans le seul but d’assurer une protection élevée des investisseurs et leurs investissements. Toutefois, depuis une décennie, on voit émerger au sein des organisations régionales africaines de nouveaux modèles de traités d’investissement dont l’unique but est de promouvoir les investissements qui soutiennent le développement durable. Ce changement de paradigme, qui prône désormais la compatibilité du régime juridique de l’investissement transnational avec les exigences sociales et environnementales, n’est cependant pas sans soulever des interrogations. Parmi celles-ci se pose la question de savoir comment l’engagement en faveur du développement durable est concrètement traduit dans ces traités régionaux. L’interrogation est capitale, surtout lorsqu’on sait les difficultés qui entourent l’analyse du développement durable, concept et objectif à la fois multidimensionnel et évolutif. À cet égard, l’étude des instruments de la CEDEAO et de la SADC témoigne de la prise en compte du développement durable à un double niveau. D’abord, l’adaptation, à travers l’aménagement des clauses traditionnelles des traités d’investissement (PARTIE I). Ensuite, l’innovation, par l’introduction de dispositions jusque-là inexistantes dans la pratique conventionnelle (PARTIE II). The understanding of the tandem of sustainable development and investment treaty has long been seen in terms of contradiction. Indeed, although there is a consensus on the importance of investments as a vehicle for Sustainable Development, the only international instruments specifically dedicated to them [investment treaties] generally pay little or no attention to this objective; they are designed with the sole aim of ensuring high protection for investors and their investments. Over the past decade, however, new models of investment treaties have emerged in African regional organizations with the sole aim of promoting investments that support sustainable development. However, this paradigm shift, which now advocates the compatibility of the legal regime of transnational investment with social and environmental requirements, raises some questions. Among these is the question of how the commitment to sustainable development is concretely reflected in these regional treaties. The issue is crucial, especially when one considers the difficulties surrounding the analysis of Sustainable Development, a concept and objective that is both multidimensional and evolving. In that regard, the study of ECOWAS and SADC instruments reflected the consideration of Sustainable Development at two levels. First, adaptation, through the amendment of the traditional clauses of investment treaties (Part I). Secondly, innovation, through the introduction of provisions which had not previously existed in Treaty practice (Part II).
Keywords: Africa; Afrique; Communauté économique des États de l'Afrique de l'Ouest; Durable; Développement durable; Investissements; Investments; Regional; Southern African Development Community; Sustainable; Traités; Treaties

The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31341
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

Le constitutionnalisme à l’épreuve de l’intégration dans l’espace CEDEAO : contribution à l’étude de la protection des droits fondamentaux depuis l’« ouverture démocratique » en Afrique - Amadou Adamou, Bachirou (Université de Toulon, 2018)
L’étude du constitutionnalisme dans l’ordre juridique de la Communauté Économique des États de l’Afrique de l’Ouest (CEDEAO), sous le prisme de la protection des droits fondamentaux, paraît particulièrement intéressante tant l’organisation Ouest-africaine a connu une profonde mutation. Au départ économique, la CEDEAO a transcendé sa dimension initiale pour atteindre la supranationalité, seul moyen à l’efficacité avérée qui lui permettra à la fois de se saisir de son ambition communautaire et de ne pas manquer le rendez-vous de la mondialisation. En témoigne la constitutionnalisation sans cesse grandissante de l’ordre juridique communautaire par une méthode prétorienne de protection des droits fondamentaux qui a permis à la Cour de justice de la CEDEAO d’asseoir son autonomie. Pour autant, le constitutionnalisme ne semble pas pénétrer définitivement l’ordre juridique Ouest-africain qui n’est qu’à son stade embryonnaire. Mais, devant les exigences d’un renouveau démocratique africain, il a fallu se tourner résolument vers la création d’un environnement juridique et politique propice à la réalisation du projet d’intégration africaine. Pour mieux définir la conviction communautaire et consacrer définitivement le renouveau du régionalisme, les États membres ont dû abandonner leur ambition théorique irraisonnée, calqué sur le développementalisme, pour garantir au processus d’intégration, les éléments indispensables à la construction de son « identité », notamment son « identité constitutionnelle ». En ce sens, l’évolution normative de la CEDEAO, d’abord initiée par le traité révisé, ensuite par le Protocole sur la démocratie et la bonne gouvernance et enfin le Protocole d’Accra relatif à la Cour de justice, a permis de déterminer le cadre constitutionnel de la Communauté. Ce sont ces évolutions fondatrices de l’ordre juridique communautaire qui ont permis à la fois la juridicisation des droits fondamentaux et l’affirmation d’un constitutionnalisme Ouest-africain. Ces principes de convergence constitutionnelle permettent ainsi de répondre au défi politique et sécuritaire, clef de voûte de la construction d’un espace public communautaire : l’espace CEDEAO. The study of constitutionalism in the legal order of the Economic Community of West African States (ECOWAS), through the lens of the protection of fundamental rights, seems particularly interesting, such that the West African organization has undergone a profound transformation or even metamorphosis. From an economic point of view, ECOWAS has transcended it’s initial dimension to achieve supranationality, the only way to the proven effectiveness that will allow it both to seize it’s community ambition and not miss the meeting of globalization. This is evidenced by the ever-increasing constitutionalization of the Community legal order by a Praetorian method of protecting fundamental rights, which has enable the ECOWAS Court of Justice to establish it’s autonomy. However, constitutionalism does not seem to penetrate definitely the West African legal order which is only in it’s embryonic stage. Nevertheless, in the face of demands of an African democratic renewal, it was necessary to turn resolutely towards the creation of a legal and political environment conducive to the realization of the African integration project. In order to better define the community’s conviction and definitively enshrine the renewal of regionalism, the Member States had to abandon their unreasoned theoretical ambition, based on developmentalism, to guarantee the process of integration, the essential elements for the construction of it’s "identity", in particular it’s "constitutional identity". In that respect, the normative evolution of ECOWAS, first initiated by the Revised Treaty, then by the Protocol on Democracy and Good Governance and finally the Accra Protocol relating to the Court of Justice, has made it possible to determine the constitutional framework of the Community. These are fundamental evolutions which have allowed both the legalization of fundamental rights and the affirmation of West African constitutionalism. These principles of constitutional convergence thus make it possible to respond to the political and security challenges, the keystone of the construction of a public community space: the ECOWAS region.
Keywords: Afrique occidentale; Bonne gouvernance; Communauté économique des États de l'Afrique de l'Ouest; Community law; Constitutional law; Constitutionalism; Constitutionnalisme; Cour de justice de la CEDEAO; Democraty; Droit communautaire; Droit constitutionnel; Droits de l'Homme; Droits fondamentaux; Démocratie; ECOWAS Court of justice; Etat de droit; Fundamental rights; Good gouvernance; Primauté du droit; Rule of law

Os desafios da política de integração regional e a governação multinível na Comunidade Econômica dos Estados da África Ocidental - Coutinho, Kathleen Rocheteau Gomes; Canto, Paulino Oliveira do (Monções: Revista de Relações Internacionais da UFGD, 2018)
Regional integration is a complex process of supranational relations in order to respond to the challenges of the national, regional and international conjuncture. It is understood that in order to respond to the challenges of regionalization in this case, the Economic Community of West African States (ECOWAS) must gradually move to multilevel governance, which therefore plays a crucial role in the development of regional integration policies. Based on the neofunctionalist theory, this paper has as main objective to understand the influence of multilevel governance in the development of regional integration policy in ECOWAS. This article is based on a qualitative analysis, using data collected through documents from secondary sources. This is a comprehensive analysis of multilevel governance and the challenges of regional integration policy in ECOWAS. The results, after a systematic analysis of the available data, show that multilevel governance in ECOWAS began with the structural and regulatory reforms of the Revised Treaty of 1993 and a number of other mechanisms which allowed the sharing of the objectives of the Community with the other institutions, in addition to the Conference of Heads of State and Government and non-state actors.
Keywords: CEDEAO; Comunidade Económica dos Estados da África Ocidental; ECOWAS; Governação Multinível; Multilevel Governance; Neofuncionalismo; Regional Integration Policy

OHADA and the Making of Transnational Commercial Law in Africa - Bashi Rudahindwa, Jonathan (Law and Development Review, 2018)
The Organisation for Harmonisation of Business Law in Africa (OHADA) was established in October 1993 with the ambitious aim of inciting economic development in its Member States. Through the adoption of Uniform Commercial Laws, the organisation is expected to create an enabling environment for business development, thereby providing for a path to economic growth and subsequent development. In light of this professed aim, both the transnational methodological approach and comparative law theories are used in this paper to critically analyse the various processes conducted under the OHADA banner and to engage in discussions on the highly debated role of law as a vehicle for development in sub-Saharan Africa. This exercise, which proves crucial in order to trace its origin within the global governance and law and development theories, allows us to present OHADA as a transnational legal system, while also highlighting both its strengths and limitations.
Keywords: Law and development; Law reform; Legislative unification; OHADA; Transnational law

Harmonisation et mise en cohérence des politiques d'aide publique au développement au regard des principes de la Déclaration de Paris : cas de Madagascar - Ravaoharinirina, Hanitriniaina Liliane (Université de Bordeaux, 2018)
Madagascar classé parmi les pays moins avancés et se trouvant en situation précaire a bénéficié des aides venant de nombreux bailleurs, bilatéraux et multilatéraux, traditionnels ou nouveaux pour financer pour l’appuyer à mettre en œuvre son programme de développement.Depuis son indépendance jusqu’à ce jour, il n’a cessé de recevoir des aides publiques au développement. Pourtant, jusqu’à ce jour sa situation ne s’améliore guère. L’adoption en 2005 de la Déclaration de Paris (DP) lors du forum de haut niveau par le CAD de l’OCDE a instauré une nouvelle orientation politique plus centrée sur la promotion de l’harmonisation et la coordination des politiques d’aides pour atteindre l’efficacité de toutes les actions menant à une stabilité mais également à un développement durable. Conscient des défis à relever, Madagascar s’est engagé dans cette démarche de mise en cohérence des politiques et d’harmonisation des pratiques. Il est un des cinquante pays qui ont adopté et signé cette déclaration. Cette orientation politique devait donner un souffle et recommande les partenaires techniques et financiers (PTF) à fédérer et travailler ensemble réellement pour que les aides soient vraiment un outil de développement non plus un problème du pays bénéficiaire. La dernière déclaration faite à Busan sur l’efficacité de l’aide en 2011 souligne encore sur cet aspect .Aussi, depuis 2005 le Gouvernement malgache avec l’appui de l’ensemble de ses PTF, bailleurs de fonds, a décidé de mettre en place un agenda pour l’horizon 2015. Cet agenda, une sorte de feuille de route, fixe les grandes étapes que les acteurs devraient suivre pour instaurer des mécanismes de gestion harmonisés et coordonnés des aides publiques au développement. Ce sont des cadres incitatifs de partenariat entre bailleurs et Gouvernement que ce dernier tente d’instaurer. Ces actions ont débuté par la mise en œuvre des réformes pour rendre fiables les systèmes nationaux et regagner la confiance des PTF. Par la suite, il a été procédé à la mise en place d’un organe de coordination et des mécanismes de suivi-évaluation nationale et conjointe des politiques publiques et celles des aides extérieures. Parallèlement, au niveau de chaque secteur , il est cherché l’adaptation des approches dans le but d’aller dans le sens de cette nouvelle orientation politique. Dans la pratique, ces démarches ne sont pas faciles à appliquer et des difficultés sont ressenties tant politiques que techniques. C’est ce qui engendre le désordre dans la cartographie nationale de l’aide et la méfiance dans l’application des cinq principes de mise en cohérence : Appropriation, Alignement, Harmonisation, Gestion accès sur les résultats et responsabilités mutuels connu sous le sigle d’harmonisation.L’instabilité causée par la survenance de la crise de 2009 a ralenti le processus bien enclenché bien que les résultats obtenus ont été encourageants. En effet, l’évaluation de la mise en œuvre de la DP en 2010 a évoqué une baisse de performance par rapport à celle de 2008. La recherche de complémentarité, de synergie entre les bailleurs avec comme facteurs de réussite l’appropriation des politiques sont les défis à relever. Le maintien des acquis s’avèrerait important pour éviter le recul et le retour des anciennes pratiques non adaptées à la politique de coopération internationale pour le développement . De même, du côté des autorités malgaches l’attention doit être focalisée sur le comment instaurer un climat et environnement administratif et économique sain pour regagner la confiance des acteurs nationaux de développement et les bailleurs de fonds. Madagascar among less advanced countries in a precarious situation has benefited aids from many donors, bilateral and multilateral, traditional or new ones, to finance its development program implementation.Since its independence, it has not stopped receiving such public aids for development. However, no improvement has occurred up to now. In 2005, the adoption of the Paris Declaration during the High Level Forum by the Development Assistance Committee (DAC-OECD) established a new political orientation based on promoting harmonisation and coordinating aid policies to ensure efficiency of all actions for a sustainable stability and development. Being aware of the challenges to take up, Madagascar enrolled in the process of ensuring the politics and practise harmonization consistency. It is one of the fifty countries that adopted and signed for this declaration. The above political orientation had to provide a breath of fresh air and recommends to the technical and financial partners (PTFs) to really unite and work together so that aids could be an actual development tool and no more a problem for the beneficiary country. The last Busan Aid Effectiveness Declaration in 2011 still emphasizes this aspect .Therefore, since 2005, the malgache government with the support of all its PTFs, donors, has decided to put an agenda in place for the 2015 horizon. This agenda, a sort of roadmap, fixes the important steps that the players should follow to establish harmonized and coordinated managing mechanism of the public development aids. It is a partnership incentive between donors and government that the latter tries to establish. Those actions began with the reform implementation to make the national system reliable and to win back the PTFs’ confidence. Therefore, the implementation of the coordinating entity and the mechanism of national monitoring survey joint with public policies and external aids has been processed. Simultaneously, at each sector’s level, the approach adaptation has been searched to be in agreement with this new political orientation. In practice, these processes are not easy to carry out and some difficulties are politically and technically experienced. This engenders disorder in the national aid mapping and suspicion in the application of the five consistency principles: Ownership, Alignment, Harmonisation, Managing for results and Mutual accoutability known as harmonisation.The instability caused by the 2009 crisis occurrence has slowed down the well engaged process despite the promising results. In fact, the 2010 DP implementation survey evoked a performance decrease if compared to that of 2008. The search for complementary feature, for synergy between financial donor(s) with politics appropriation as a factor in the success are the challenges. Knowledge keeping would be important to prevent from regression and coming back to the old practices that are not adapted to the international cooperation for the development . In the same way, the malgache authority should more focalize their attention to the way how to regain the national development players’ and the donors’ trust.
Keywords: Aide publique au développement; Cohérence; Consistency; Coordination; Déclaration de Paris; Développement économique; Harmonisation; Harmonization; Integrated; Intégré; Madagascar; Paris Declaration; Programme; Public aid for development; Subventions

Intégration et Souveraineté étatique, approche comparative entre l'Europe et l'Afrique à travers l'UE, l'UEMOA et l'OHADA - Seck, Ami Collé (Université Clermont Auvergne, 2018)
La présente thèse vise à décrire et analyser l’évolution ambigüe du rapport Souveraineté-Intégration dans les cadres européen et africain. A cet effet, elle révèle qu’un tel rapport est part d’un antagonisme de principe entre Souveraineté et Intégration mais débouche cependant sur des réalités différentes qui sont fonction du contexte précis de mise en application de cette relation. En effet, si au départ, on peut noter une certaine convergence de vue en Europe et en Afrique sur la nature antagonique des rapports entre Souveraineté et Intégration ; à l’arrivée, la pratique de l’intégration ne semble pas avoir conduit aux mêmes effets quant au sort de la souveraineté étatique dans les cadres européen et africain. En réalité, alors que la souveraineté de l’Etat a été fortement amoindrie par l’intégration dans l’UE, confirmant ainsi largement leur antagonisme de départ ; du côté africain, cette hypothèse initiale d’antagonisme a plutôt été compromise par la pratique car dans l’UEMOA et l’OHADA, l’opposition entre souveraineté et intégration s’est avérée largement ineffective. This thesis aims to describe and analyze the ambiguous evolution of the Sovereignty-Integration report in the European and African frameworks. To this end, it reveals that such a relation started from an antagonism of principle between Sovereignty and Integration but nevertheless leads to different realities that depend on the precise context of the application of this relation. Indeed, while at the outset one can note a certain convergence of view in Europe and in Africa on the antagonistic nature of the relations between Sovereignty and Integration; the practice of integration seems to have led to contradictory effects on the fate of state sovereignty in the European and African frameworks. In facts, whereas sovereignty of States has been greatly diminished by integration in the EU, thus largely confirming their initial antagonism ; on the African side, this initial hypothesis of antagonism has rather been compromised by practice because in UEMOA and OHADA, the opposition between sovereignty and integration has proved largely ineffective.
Keywords: European Union; Integration; Intégration régionale; Intégration sous régionale; Intégration supranionale; Intégration économique internationale; Organisation pour l'harmonisation en Afrique du droit des affaires; Organization for the harmonization of business law in Africa; Souveraineté; Souverainté étatique en Afrique; Souverainté étatique en Europe; Sovereignty; Unification internationale; Union européenne; Union économique et monétaire Ouest africaine; West African economic and monetary union

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules

O papel da integração regional como mecanismo de inserção internacional e de promoção de desenvolvimento: um estudo de caso sobre a SADC - Calich, Ana Paula de Mattos (Universidade Federal do Rio de Janeiro, 2018)
A intensificação dos processos de integração regional no pós-Guerra Fria e a ascensão de alguns países do Sul global trouxeram para o campo das Relações Internacionais o desafio da atualização do estudo acerca do tema. Partindo do entendimento que estas regiões periféricas possuem uma lógica singular, o presente trabalho busca ver os blocos de integração estabelecidos neste contexto como uma forma de modificar a inserção internacional desfavorável e promover desenvolvimento nos países-membros. Para validar tal análise, a Comunidade para o Desenvolvimento da África Austral (SADC) foi selecionada como estudo de caso, fazendo-se o esforço de correlacionar as políticas do bloco com as transformações econômicas, políticas e sociais que ocorreram nos anos de vigência da integração.
Keywords: Desenvolvimento; Inserção Internacional; Integração Regional; SADC; África Austral

La protection juridique des réfugiés et déplacés climatiques à assurer par les organisations régionales : rôle de l'Union Africaine - Koïbé Madjilem, Roméo (Université Paris 10, 2017)
Depuis quelques années, le réchauffement climatique est un thème qui fait l’objet de plusieurs débats houleux. Mais à l’heure actuelle, il est difficile d’affirmer avec certitude que le réchauffement climatique et les catastrophes qui se multiplient, ces derniers temps, en sont les conséquences évidentes. Toutefois, il ne fait l’ombre d’aucun doute que ces catastrophes naturelles ou celles d’origine anthropique ont des incidences avérées sur l’environnement et le milieu de vie humain. C’est le cas dans le Pacifique avec les îles du Tuvalu exposées à la montée du niveau de la mer, à l’érosion et même à la disparition. C’est aussi le cas dans le Sahel avec le lac Tchad qui, en raison d’une baisse de la pluviométrie, de la sécheresse et d’une mauvaise gestion de ses eaux, connait un rétrécissement inquiétant, obligeant ainsi, des milliers de personnes à migrer dans l’espace du bassin conventionnel du lac Tchad partagé entre le Nigéria, le Niger, le Cameroun et le Tchad. Ces mouvements internes et transfrontaliers mal encadrés sont sources de tensions et d’insécurité. Cette situation semble peu préoccuper les pays touchés, moins encore les pays riches et la communauté internationale, qui en l’absence de tout cadre juridico-humanitaire et d’un statut protecteur international, montrent peu de signe d’empressement pour trouver des solutions afin d’assister les réfugiés et déplacés climatiques et environnementaux qui risquent d’être lésés dans leur droit à la vie et à une vie décente. En raison du vide juridique au niveau international, il serait souhaitable de faire un état des lieux des possibilités actuelles de protection juridique universelle et régionale avant de revenir vers des pistes de solutions adaptées aux besoins spécifiques de l’Afrique par le biais de l’Union Africaine. Une option audacieuse mais qui vaut la peine en raison du contexte actuel qui impose une recherche de solutions scientifiques et juridiques pouvant aider à l’action des décideurs politiques. In recent years, global warming has been the subject of several heated debates. But, it is currently difficult to affirm with certainty that global warming and the increase in natural disasters in recent times are the obvious consequences. However, there is no doubt that these natural disasters or those caused by human activities have a proven impact on the environment and the living environment. This is the case in the Pacific with the Tuvalu islands which have been exposed to rising sea levels, erosion and even extinction. This is also the case in the Sahel region where due to a decline in rainfall, drought and poor management of its waters, the Lake Chad is experiencing a disturbing contraction, forcing thousands of people whose life depends on it to migrate in the space of the conventional basin of Lake Chad shared between Nigeria, Niger, Cameroon and Chad. These poorly managed internal and cross-border movements are sources of tension and insecurity. This situation does not appear to be of sufficient concern to the countries affected by these changes, and even less to the developed countries and the international community, which in the absence of any legal and humanitarian framework and international protective status, show no signs of eagerness to find temporary or permanent solutions to assist climate and environmental refugees and environmentally displaced persons whomay be harmed in their right to life and decent life. Due to the current legal vacuum at the international level, it would be desirable to take stock of the current possibilities of universal and regional legal protection before returning to possible solutions adapted to the specific needs of Africa, through the African Union. This is a bold but worthwhile option because of the current context that requires a search for scientific and legal solutions that can help policy makers.
Keywords: African Union; Climate refugees; Droits de l'Homme; Environmental migrants; Global warming; Human rights; Migrants environnementaux; Organisations régionales; Regional organizations; Réchauffement climatique; Réfugiés climatiques; Réfugiés environnementaux; Union africaine

Regional trade integration and co-operation in Southern Africa : the case of the Southern African Development Community (SADC) - Mathebe, Mpubane Mox (University of South Africa, 2017)
Mercantile Law
Keywords: Economic integration; Foreign economic relations; Foreign trade regulation; Free Trade; Monetary unions; SADC; Southern African Development Community

L'adhésion de la République Démocratique du Congo à l’OHADA et son impact sur le droit congolais des affaires : cas de la ville de Kolwezi - Kahilu Mutshima, Christophe (KAS African Law Study Library, 2017)
Il est vrai que la récente adhésion de la République Démocratique du Congo à l’organisation pour l’harmonisation en Afrique du Droit des Affaires (OHADA) depuis le 12 septembre 2012, à travers la loi n° 10/002 du 11fevrier 2010 autorisant l’adhésion de la République Démocratique du Congo au traité du 17 octobre 1993 relatif à l’harmonisation du Droit des affaires en Afrique, a doté ce pays d’un Droit des affaires moderne, actualisé et attractif pour les investisseurs internationaux, mais aussi pour les opérateurs économiques nationaux. Cette adhésion vient de constituer un changement majeur pour ce pays par une réforme en profondeur d’une bonne partie de la législation relative au Droit des affaires. À cet effet, de nombreux textes législatifs régissant le Droit des affaires au Congo et spécialement à Kolwezi, dont la plupart sont non adaptés au climat des affaires, voire obsolètes, viennent d’être remplacés par les Actes Uniformes modernisés avec effet immédiat d’application. La présente adhésion constitue également une étape décisive pour l’extension de l’espace OHADA dont la vocation continentale est affichée dans le traité. Le fait pour la République Démocratique du Congo de naître dans l’espace Organisation pour l’Harmonisation en Afrique du Droit des Affaires aujourd’hui, reste un élément majeur non seulement pour ses prérogatives analogues à un Droit de veto, mais aussi concoure à l’élargissement pour l’organisation, de son champ d’application, et de son influence sur l’arsenal juridique congolais. En conséquence, affirmons que cette victoire de cette Organisation en République Démocratique du Congo vient de constituer une preuve de la pertinence et de la modernité des Actes Uniformes. Cependant, il est important pour nous de savoir si la République Démocratique du Congo s’était réellement préparée en conséquence, pour cette adhésion à l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires. Disons que même si l’immense majorité des juristes, des hommes d’affaires tant nationaux qu’internationaux, des investisseurs et autres de Kolwezi ou d’ailleurs, sont enthousiastes à l’avènement de l’adhésion de la République Démocratique du Congo à cette organisation, reconnaissons encore que ce phénomène fait en même temps, l’objet de quelques réticences et discussions sur le plan interne. Ainsi, la méthode juridique et celle sociologique nous servirons de cadre tout au long de notre réflexion, appuyée par la technique documentaire. Etant donné qu’il s’agit d’un traité auquel la République Démocratique du Congo doit adhérer, faudra-t-il réviser la Constitution de la République avant son adhésion à cette organisation? Nous disons que conformément aux dispositions de l’article 215, il n’en est pas le cas parce que ladite disposition établit que : les traités et accords internationaux régulière- ment conclu ont dès leurs publications, une autorité supérieure à celle des lois. C’est pourquoi au cours de notre analyse nous parlerons des notions sur le Droit OHADA (A), de la modernisation du Droit des Affaires congolais (B), des craintes liées à l’adhésion de la République Démocratique du Congo à l’Organisation pour Harmonisation en Afrique du Droit des Affaires (C), et de nouveaux défis pour les Actes Uniformes (D).

Le rôle du droit dans la mise en place d'un marché commun des télécommunications dans l'espace CEDEAO - Gueye, El Hadji Modou (Université Cheikh Anta Diop, 2017)
Keywords: CEDEAO; Marché commun; Télécommunications (droit)

L'harmonisation internationale du droit des brevets - Lenoir, Pierre-Etienne (Université de Nantes, 2017)
Face à l'accroissement de l'importance politique et économique des fora internationaux, quel est aujourd'hui le degré de liberté des États dans la définition de leur propre système de protection ? L'harmonisation internationale du droit des brevets nécessite de mettre en place des éléments de flexibilité permettant à chaque État de transposer le droit international dans leur ordre interne en fonction de leur spécificité économique et politique. Or, les débats actuels au sein des fora internationaux démontrent une divergence entre États-membres qui porte atteinte à la notion même d'harmonisation. Alors que les pays développés prônent une suppression progressive des éléments de flexibilité au profit d'une uniformisation internationale du droit, les pays émergents, sous couvert de principes universels liés au développement, remettent en cause l'insuffisance de flexibilité du régime international des brevets face aux crises majeures du XXIe siècle. li s'en suit un mouvement cyclique mettant en scène les rapports entre bilatéralisme et multilatéralisme face au déclin des organisations internationales. While the economic and political importance of international fora is increasing, what is today the degree of freedom of States in defining their own system of protection? The international harmonization of patent law requires the introduction of flexibilities allowing each State to transpose international law into their legislation in accordance with· their economic and political specificities, The current debates in international for a demonstrate a divergence between Member States which undermines the notion of harmonisation. While developed countries promote the gradual elimination of flexibilities in favour of international standardization of the law, emerging countries, under the guise of universal development-related principles, challenge the lack of flexibility of the international patent regime vis-à-vis Major crises of the XXlst century. This is followed by a cyclical movement highlighting the relationship between bilateralism and multilateralism in the face of the decline of international organizations.
Keywords: Bilatéralisme; Brevets d'invention; Droit comparé; Intellectual property; Multilatéralisme (relations internationales); Organisation mondiale du commerce; Propriedade intelectual; Propriété intellectuelle

L’intégration par l’énergie : Quels progrès 50 ans après le traité d’Abuja ? - Gbaguidi, Ochozias A. K. (Revue Interventions économiques, 2017)
Les États africains ont fait le choix de pôles énergétiques pour combattre les inégalités d’accès à l’énergie. Les progrès vers l’intégration régionale en Afrique ont fait l’objet de nombre d’évaluation ces dernières années. Une des plus récentes, (CEA, UA et AfDB, 2016) indique que, malgré les différents défis, les pays africains ont poursuivi leur marche vers l’intégration de leurs économies et ceci dans la quasi-totalité des domaines ciblés depuis le traité d’Abuja. En particulier dans le ...

Intégration commerciale de l’Afrique et libre-échange global : défis et perspectives - Kotcho, Jacob (Revue Interventions économiques, 2017)
Le modèle d’intégration choisi par le continent africain est un mix entre l’intégration par les marchés et celle par les institutions. Le continent africain et ses États sont engagés tant dans un processus d’intégration commerciale comportant plusieurs étapes, selon un calendrier prévu par le Traité d’Abuja établissant la Communauté Économique Africaine que dans divers processus de négociation d’accords commerciaux régionaux avec des partenaires étrangers (UE, Chine, USA, etc.). Dans un conte...

Bilan de la libre circulation des personnes en Afrique - Mouangue Kobila, James (Revue Interventions économiques, 2017)
La SADC offre le meilleur exemple de la libre circulation en Afrique. La libre circulation des personnes (et leur libre établissement) participe des domaines clés de l’intégration économique, à côté de la libre circulation des marchandises, des capitaux, des services. On y inclut également la promotion commune des investissements, les communications, la construction d’infrastructures routières et ferroviaires, la convergence macroéconomique, la gestion commune de l’agriculture et la sécurité ...

Réforme de la structure fiscale et Intégration régionale - Nguimkeu, Pierre (Revue Interventions économiques, 2017)
L'Afrique semble s'être intégrée au reste du monde bien plus rapidement qu'avec elle-même. Pour la plupart des pays, le plus important partenaire commercial se trouve de l'autre côté de la frontière. La logique économique dicte qu’un produit doit parcourir la distance la plus courte possible pour atteindre son marché - puisque les coûts augmentent avec la distance. L'Afrique postcoloniale est une exception récalcitrante à cette règle fondamentale de l’économie. La structure des économies afri...

Infrastructures, commerce intra-africain et développement économique en Afrique - Sané, Malick (Revue Interventions économiques, 2017)
La gestion de la crise infrastructurelle sera l’un des plus grands défis et l’une des plus grandes opportunités de développement pour l’Afrique dans les décennies à venir. Le commerce intra-africain se situe à environ 12 %, très en deçà du commerce intra-régional en Europe, en Amérique du Nord et dans les pays de l’Asean avec respectivement 60 %, 40 % et 30 % (CNUCED, 2013). Même si plusieurs raisons expliquent la faiblesse du commerce intra-régional en Afrique, la carence en infrastructure o...

Environnement institutionnel des affaires en Afrique : Contexte et structure d'harmonisation du droit OHADA - Kagisye, Emmanuel (HAL Open science, 2017)
A l’heure de la mondialisation de l’économie, l’Afrique, à l’instar des autres continents s’est lancée dans de vastes entreprises d’intégration économique et juridique. S’il vrai que l’idée d’intégration africaine remonte assez loin dans l’histoire, mais celle d’harmoniser les droits africains remonte à la période post-coloniale. Plus tard, cette idée fut reprise par des juristes africains et connut un premier aboutissement au sein de l’Union africaine et malgache (UAM) et dans la Convention pour l’Organisation commune africaine, malgache et mauricienne (OCAM). Finalement, elle sera concrétisée par la création de l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA). Cet article revient sur le contexte qui justifiait l’harmonisation et présente la structure de l’harmonisation du droit des affaires ohada.
Keywords: Droit OHADA; Environnement institutionnel des affaires en Afrique; Structure d'harmonisation

Environnement juridique des affaires en Afrique : Système juridique et judiciaire de l'OHADA - Kagisye, Emmanuel (HAL Open science, 2017)
L’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) a été créé par le Traité de Port Louis du 17 octobre 1997. Le Traité fut signé à l’origine par quatorze Etats et l’OHADA rassemble aujourd’hui dix-sept pays africains et reste ouverte à tout État membre de l’Union africaine et à tout État, non membre de l’Union africaine, invité à y adhérer d’un commun accord des États parties. La nature juridique de l’OHADA constitue une singularité de l’Organisation par rapport aux modèles classiques d’organisations internationales. En effet, l’Organisation a créé un véritable espace juridique et a institué un véritable système juridique et judiciaire. Cet article présente le système OHADA tant dans ses composantes normatifs (sources et caractéristiques) que juridictionnelles.
Keywords: Environnement juridique des affaires en Afrique; OHADA; Système judiciaire; Système juridique

L'adhésion des organisations d'intégration au Traité OHADA : un impératif pour une meilleure rationalisation de l'intégration juridique - Kagisye, Emmanuel (HAL Open science, 2017)
Les conflits de normes dans l’espace OHADA invite à réfléchir autrement la rationalisation de l’intégration en Afrique : Ohadanisation de l’intégration juridique. L’ohadanisation, simple néologisme, part de l’idée que l’OHADA doit être le « Centre principal de législation » en matière de droit des affaires et le leitmotiv des autres législations communautaires. Le processus d’ohadanisation commencerait par l’adhésion des organisations d’intégration au Traité OHADA. L’adhésion des organisations d’intégration régionale à une autre organisation est une idée tout à fait nouvelle, qui n’avait pas suscitée de réflexions au cours de tous les travaux sur la rationalisation de l’intégration régionale en Afrique. Dans cet article, nous présentons et justifions la nécessité d’une adhésion des organisations régionales voisines au Traité OHADA, pour ensuite en présenter les modalités et les effets.
Keywords: Adhésion; Conflits de normes; Intégration; Rationalisation; Traité OHADA

Le droit OHADA, la libre circulation et harmonisation du droit des affaires dans la Région des Grands Lacs : Défis et perspectives - Kagisye, Emmanuel (HAL Open science, 2017)
La situation actuelle présente le risque de voir se multiplier dans la région des grands lacs des poches de droits concurrents et celui d'ouvrir une ère de rivalité juridique entre les systèmes juridiques auxquelles appartiennent les pays membres de la CEPGL. Cette situation de balkanisation juridique n’est pas de nature à favoriser ni la libre circulation des marchandises, des services et de capitaux ni l’harmonisation du droit des affaires dans la Région des Grands Lacs. Pour remédier à cette situation, cet article recommande l’adoption du droit harmonisé par l’OHADA. Cette adoption, permettra aux pays membres d’avoir un droit harmonisé sans être amené à renoncer à sa tradition juridique.
Keywords: Droit OHADA; Harmonisation du droit des affaires; Libre circulation; Région des Grands Lacs

La lutte contre la délinquance économique et financière dans l'Union Economique et Monétaire Ouest Africaine (UEMOA) et dans l'Organisation pour l'Harmonisation du Droit des Affaires en Afrique (OHADA) : état des lieux et perspectives - Diakhate, Serigne Modou (Université Paris 1, 2017)
La délinquance économique et financière, constituée par l'ensemble des activités illégales, qui peuvent être commises de manière individuelle, en entreprise ou bande organisée, a des méthodes d'action différentes de celles des infractions de droit commun. Le plus souvent, elles se commettent par des procédés astucieux (tromperie), ou frauduleux (faux par exemple), par l'exploitation des secrets commerciaux ou des données confidentielles (délits d'initiés), exigeant pour cela des connaissances et un savoir-faire propres au monde des affaires, voire une ingénierie financière, à l'encontre des particuliers, d'entreprises. de l'Etat ou d'organisations internationales. Généralement, leur finalité est la recherche du gain facile, donc de l'argent sale ou noir, fruit d'activités illégales ou criminelles. Cet argent est au centre de la délinquance économique et financière. Il en est le moteur. C'est une des raisons pour lesquelles la lutte contre cette forme de délinquance doit avoir comme principale finalité la saisie des avoirs d'origine criminelle ou délictuelle. A cette fin. nous avons fait dans cette étude, des propositions de réforme dans les codes pénaux et de procédure pénale des Etats appartenant à la sphère UEMOA-OHADA et d'y inclure des dispositions permettant de procéder efficacement à cette saisie. Cette question de saisie des avoirs d'origine illicite montre à quel point il est difficile de lutter contre cette forme de délinquance. Car, aujourd'hui, l'action des Etats, pris individuellement. pour combattre ce fléau, a perdu son efficacité. C'est pourquoi, le traitement de cette délinquance devrait nécessairement passer par une harmonisation du droit pénal des affaires de l'OHADA et une uniformisation du droit pénal économique et financier de l'UEMOA. Cependant. ce combat au niveau communautaire n'est pas sans poser quelques difficultés dans la mesure où les Etats membres de ces deux organisations ne veulent pas se départir, au profit des Institutions communautaires, du pouvoir d'élaborer des sanctions pénales contre les incriminations communautaires applicables sur leur territoire. D'où la nécessité de tenir compte de l'impératif d'harmonisation des règles pénales de sanction contre les violations du droit communautaire, d'un côté, et de l'impératif du respect de la souveraineté des Etats, de l'autre, même si ces deux impératifs sont difficilement conciliables. En tout état de cause, pour rendre efficace la lutte contre ce phénomène criminel, les dispositifs actuels doivent évoluer vers de nouveaux instruments plus adaptés. Ainsi des typologies de mesures relatives au droit pénal de forme et de fond sont elles proposées tant au niveau national et régional. En effet, une lutte envisagée à un seul niveau est d'avance vouée à l'échec. C’est ainsi qu'il faut instaurer un véritable coopération judiciaire dans l'espace UEMOA-OHADA pour une lutte efficace contre la délinquance économique et financière dans cet espace.
Keywords: Acte uniforme; Afrique; Criminalité des affaires; Difficulties of unification or harmonization; Difficultés d'unification ou d'harmonisation; Droit (réforme); Délinquance économique et financière; Economic and financial criminality; Etat des lieux et perspectives; Lois uniformes; OHADA; UEMOA; Uniform Act; WAEMU

Le paradoxe de l'internationalisation du droit constitutionnel en Afrique : réflexions sur les interactions normatives, institutionnelles et politiques dans l'espace CEDEAO - Diompy, Abraham Hervé (Université de Bordeaux, 2017)
Difficile de nier qu’il arrive quelque chose au droit constitutionnel sousl’effet conjugué de l’internationalisation du droit et de la construction communautaire. Eneffet, le droit constitutionnel s’internationalise, se régionalise dans un mouvement exponentiel. L’Afrique en général et l’espace CEDEAO en particulier n’échappent guère àcette dynamique globale du constitutionnalisme moderne. Aussi, a-t-on constaté que l’internationalisation du droit constitutionnel sur le continent africain qui prend la forme d’un processus d’impact, d’influence ou parfois de contraintes induit à la fois à une reconfiguration horizontale des pouvoirs constitutionnels et une redistribution verticale du pouvoir au sein del’Etat. En revanche, au niveau supranational, ce processus dynamique et intense qui marqueune ouverture des systèmes de droit et favorise la communicabilité entre ordres juridiques se traduit par un phénomène d’intégration, d’harmonisation progressive des systèmes constitutionnels étatiques autour de standards démocratiques consacrés par le Protocole de laCEDEAO sur la démocratie et la bonne gouvernance de 2001. La dialectique est, au final,paradoxale en ce que l’internationalisation du droit constitutionnel en Afrique et plus particulièrement dans l’espace CEDEAO se révèle être l’expression d’un phénomène perturbateur des ordres juridiques constitutionnels étatiques et communautaire mais aussi et en même temps un instrument de convergence matérielle (droits fondamentaux) et structurelle (régime politique démocratique) de ces dits ordres au travers de standards constitutifs du patrimoine constitutionnel commun. It is difficult to deny that something has happened to constitutional law under the combined effect of the internationalization of law and the construction of the community. Indeed, constitutional law is internationalized, regionalized in an exponential movement. Africa in general and the ECOWAS area in particular do not escape the global dynamics of modern constitutionalism. Thus, it has been observed that the internationalization of constitutional law on the African continent, which takes the form of a process of impact, influence or sometimes constraints, leads both to a horizontal reconfiguration of constitutional and a vertical redistribution of power within the state. On the other hand, at the supranational level, this dynamic and intense process, which marks an opening up of legal systems and promotes communication between legal orders, is reflected in a phenomen on of integration and progressive harmonization of the state's constitutionalsystems around democratic standards The ECOWAS Protocol on Democracy and Good Governance of 2001. The dialectic is, in the end, paradoxical in that the internationalization of constitutional law in Africa and more particularly in the ECOWAS area proves to be a phenomenon Disrupting the constitutional legal systems of the state and the community, and at the same time an instrument of material (fundamental) and structural (democratic political rule, rule of law) convergence of these orders through standards which constitutethe common constitutional heritage.
Keywords: Afrique; CEDEAO; Common constitutional heritage; Communauté économique des États de l'Afrique de l'Ouest; Communicability of legal orders; Communicabilité des ordres juridiques; Community law; Constitutional law; Constitutionalism; Constitutionnalisme; Democratic standards; Droit communautaire; Droit constitutionnel; ECOWAS; Internationalisation; Internationalization; Patrimoine constitutionnel commun; Regionalization of constitutional law; Régionalisation du droit constitutionnel; Standards démocratiques

Internationales Einheitsprivatrecht im Zeitalter der Globalisierung - Basedow, Jürgen (Rabels Zeitschrift für ausländisches und internationales Privatrecht / The Rabel Journal of Comparative and International Private Law, 2017)

Intégration, exequatur et sécurité juridique dans l’espace OHADA. Bilan et perspective d’une avancée contrastée - Ekani, Serge Christian (Revue internationale de droit économique, 2017)

Moeda, poder e rivalidade interestatal : o novo banco de desenvolvimento dos BRICS - Gaiotto, Felipe Camargo (Universidade Federal do Rio Grande do Sul, 2017)
A crise financeira de 2007-2008 proporcionou perdas de legitimidade política e econômica aos EUA no sistema interestatal. Até então, o modelo de organização socioeconômica estadunidense era hegemônico na economia-mundo capitalista. Mas, mais do que um modelo de capitalismo, as desregulações financeiras e a defesa excessiva da austeridade orçamentária para os demais Estados foram adotadas pelos EUA com o objetivo de assegurar a emissão exclusiva da moeda internacional dos sistemas financeiro e monetário internacional. A possível substituição do dólar como fundamento do padrão monetário desses sistemas diminuiria a autonomia relativa dos EUA. Assim, eles mantiveram as vantagens políticas e econômicas propiciadas pelo poder monetário e pelo estadismo monetário e asseguraram a manutenção da configuração hierárquica favorável desse sistema interestatal. Por outro lado, essa crise estimulou a formação de novas alianças geopolíticas e novas relações de cooperação entre Estados localizados na semiperiferia e na periferia da economia-mundo. Esses Estados propõem, em maior ou menor grau, outros modelos de desenvolvimento e procuram mudar a configuração hierárquica interestatal, com uma aposta no multilateralismo. O Novo Banco de Desenvolvimento (NBD) criado pelos BRICS é uma das alternativas que surgiram como possibilidades de reordenamento hierárquico nesse sistema, começando o elo conflito em torno da moeda e das finanças. Desse modo, o objetivo geral desta tese doutoral é avaliar qual a viabilidade de possíveis mudanças nas relações de poder monetário e de estadismo monetário no sistema interestatal capitalista a partir do NBD dos BRICS. Para tanto, analisa-se de que maneira, em geral, a relação entre moeda e poder influencia na hierarquia de Estados e moedas no sistema interestatal da economia-mundo capitalista. Da mesma forma, examina-se especificamente o processo de construção do poder monetário e do estadismo monetário dos Estados Unidos a partir da construção do regime Dólar-Wall Street e de que forma essa estratégia contribuiu, de forma não intencional, para enfraquecer a própria hegemonia estadunidense no pós-crise. E, por fim, avalia-se a capacidade da influência do NBD para a reforma monetária e financeira internacional no sentido de maior multilateralismo. Nesse processo, o NBD representa uma alternativa de acesso a financiamento para a acumulação autônoma de capital e de defesa contra a manipulação monetária e financeira por parte dos Estados do núcleo orgânico desse sistema, em particular os EUA. Da mesma forma, o NBD reforça as demandas para reformar o sistema financeiro e monetário internacional, o que pode alterar a capacidade de exercício do poder monetário estadunidense e suas consequentes vantagens políticas e econômicas. Assim, haveria uma mudança qualitativa na hierarquia desse núcleo orgânico. A possível substituição, ou perda de importância, do dólar diminuiria a autonomia relativa dos EUA e contribuiria para mudanças na configuração hegemônica da economia-mundo capitalista.
URI: https://lume.ufrgs.br/handle/10183/172457
Keywords: BRICS; Brasil; China; Dollar; Economia monetária; Estados Unidos; Moeda; Monetary power; New Development Bank; Política internacional; Rússia; Sistema monetário; United States; África do Sul; Índia

The African Union and the Development of African International Criminal Law - Kahombo, Balingene (Freien Universität Berlin, 2017)
This study is situated in the context of the regionalisation of international criminal law. It deals with the development of African international criminal law under the aegis of the African Union (AU). It aims to examine the factors which inform this development, the concept and the content of regional law so laid down for the African continent. The primary objective has been the exploration of theoretical and practical bases for the establishment of a viable system of African regional criminal justice in order to deal with crimes against peace and security in Africa, which put in danger African regional public order. The thesis also examines the relationship between African international criminal law and the global system of international criminal justice, currently dominated by the International Criminal Court (ICC) and the United Nations Security Council. The systemic analysis of these different issues have enabled to reach three main conclusions. First, the development of African international criminal law is not simply a conjectural consequence of the crisis observed within global international criminal law. It is also and chiefly the result of the policy of self-reliance of the AU and its member states aiming to protect and defend African regional public order through the recourse to regional institutions of criminal accountability. Second, the African Union is consequently promoting a system of African regional criminal justice based on three optional models of justice, namely the delegation of jurisdiction to a member state, the creation of hybrid courts with participation of regional judges and the establishment of a regional criminal court. Together with those crimes against peace and security that are of specific concern to the African continent, these models of justice form the core of the content of African international criminal law. However, the viability of the system towards delivering efficient justice remains problematic. There are numerous challenges to overcome, including ratifying the Malabo Protocol of June 2014 instituting the “Criminal Court of the African Union”, promoting judicial cooperation of African states and finding financial resources to support the Court’s actions. Third, African international criminal law is not a replacement of global international criminal law in the continent. There is rather a coexistence of norms and institutions which commands a certain degree of coordinated relationships to avoid competing actions and so inefficiency of justice. This thesis discusses two main approaches to consistent relationships between African regional criminal law and the global system of international criminal justice, namely the hierarchical model and the cooperative approach. It proposes a third alternative approach, that is, the regionalisation of the ICC in conjunction with the principle of regional territoriality.
Keywords: African Court of Justice and Human and Peoples' Rights; African Union; International Criminal Court; International Criminal Law; Regional Territoriality; Regionalisation; Universal Jurisdiction

A política externa de Moçambique e sua inserção no processo de integração regional na África Austral - Massangaie, Arnaldo Timóteo (Universidade Federal do Rio Grande do Sul, 2017)
A inserção internacional de Moçambique é um processo que ocorreu em fases, tendo se iniciado com os esforços empreendidos na década de 1960 pelo Dr. Eduardo Chivambo Mondlane, Primeiro Presidente da Frente de Libertação de Moçambique (FRELIMO). Visando criar o isolamento internacional do regime colonial Português e obter o apoio necessário para a causa da independência de Moçambique, Mondlane estabeleceu contatos com governos de vários Estados do mundo incluindo países ocidentais, países progressistas africanos e países socialistas, projetando, deste modo, a imagem de Moçambique no mundo. Iniciada com as decisões tomadas no Segundo Congresso da FRELIMO realizado em 1968, a política externa de Moçambique tinha em vista “criar mais amigos e poucos inimigos”, num contexto de bipolaridade ideológica que caracterizava a guerra-fria. O novo contexto internacional emergente no período após o fim da guerra-fria viria a originar uma redefiniçao desta política que passou a ser definida como de “criar mais amigos e mais parceiras”. A nível da região da África Austral a FRELIMO considerou sempre que a independência de Moçambique só seria completa com a libertação de todos os países da região que ainda se encontravam sob a dominação de regimes coloniais e minoritários tendo dado o seu apoio incondicional à luta de libertação do Zimbábue, África do Sul e Namíbia, para além do seu grande empenho no processo de cooperação e integração regional. É neste contexto que se pode enquadrar esta tese cujo tema é “a política externa de Moçambique e sua inserção na região da África Austral” a qual procura, através de uma vasta revisão bibliográfica, analisar os contornos que estiveram à volta da afirmação de Moçambique como Estado reconhecido no concerto das nações tanto a nível regional como internacional. The international insertion of Mozambique is a process that took place in phases, starting with the efforts made in the 1960s by Dr. Eduardo Chivambo Mondlane, First President of the Liberation Front of Mozambique (FRELIMO). In order to create the international isolation of the Portuguese colonial regime and obtain the necessary support for the cause of Mozambique's independence, Mondlane established contacts with governments in several states of the world including Western countries, progressive African countries and socialist countries, thus projecting the image of Mozambique in the world. Initiated by the decisions taken at the Second FRELIMO’s Congress held in 1968, Mozambique's foreign policy aimed to "create more friends and few enemies" in a context of ideological bipolarity that characterized the Cold War. The new emerging international context in the period after the end of the Cold War would lead to a redefinition of this policy, which was defined as "creating more friends and more partners". At the level of the southern African region FRELIMO always considered that Mozambique's independence would only be complete with the liberation of all the countries of the region that were still under the domination of colonial and minority regimes and gave its unconditional support to the liberation struggle in Zimbabwe, South Africa and Namibia, in addition to its strong commitment to regional cooperation and integration. It is in this context that one can frame this thesis whose theme is "the foreign policy of Mozambique and its insertion in the region of Southern Africa" which seeks, through a vast bibliographical review, to analyze the contours that were around the affirmation of Mozambique as State recognized in the concert of nations at both regional and international levels
URI: https://lume.ufrgs.br/handle/10183/168604
Keywords: Foreign policy; Intégration régionale; Mozambique; Moçambique; Política externa; Southern Africa

Les caractères généraux du droit communautaire - Soma, Abdoulaye (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2017)

East African Community Law: Institutional, Substantive and Comparative EU Aspects - Ugirashebuja, Emmanuel; Ruhangisa, John; Ottervanger, Tom; Cuyvers, Armin (Brill, 2017)
East African Community Law provides a comprehensive and open-access text book on EAC law. Written by leading experts, including the president of the EACJ, national judges, academics and practitioners, it provides the most complete overview to date of this increasingly important field. Uniquely, the book also provides a systematic comparison with EU law. EU companion chapters provide concise overviews of EU law and its development, offering valuable inspiration for the application and further development of EAC law. The book has been written for all practitioners, judges, civil servants, academics and students faced with questions of EAC law. It discusses institutional, substantive and jurisdictional issues, including the nature of EAC law, free movement and competition law as well as the reception of EAC law in Partner States.
Keywords: Comparative law

Réflexions autour de la protection des consommateurs de la zone UEMOA dans sa perspective d'intégration économique communautaire : Étude comparative avec le droit europén (Français) - Zoungrana, Ibrahim (Université de Perpignan Via Domitia, 2016)
Depuis un certain nombre d’années, les Etats membres de l’UEMOA se sont lancés dans un vaste projet de libéralisation économique suivi d’une ambition d’intégration économique, rendant ainsi difficile les projets législatifs consuméristes nationaux. A ce titre, nous nous posons la question de savoir, si les ambitions de cette intégration économique prennent en compte l’intérêt des consommateurs et si elles ne se heurtent pas au besoin d’une protection efficace des consommateurs sur le marché commun. Comment concilier ce libéralisme économique avec une protection efficace des consommateurs au sein du marché commun ? Autrement-dit, une divergence entre les différentes dispositions des Etats membres ne serait-elle pas dommageable aux consommateurs ? Enfin, peut-on parler d’un véritable ordre juridique consumériste ouest-africain? Nous tentons de démontrer à travers cette étude qu'il y a un acquis de protection communautaire des consommateurs, mais que celle-ci est sectorielle. Toutefois, les domaines laissés vacants par le droit communautaire sont implicitement régis par les différentes dispositions nationales embryonnaires et plus ou moins identiques, d'où le risque d'insécurité juridique et la nécessité du projet OHADA sur le droit des contrats comme une perspective dans le cadre de la protection des consommateurs de l'UEMOA au sein du marché commun.
Keywords: Afrique occidentale; Consommateur (protection); Droit européen et français; Intégration économique; Protection des consommateurs; UEMOA; WAEMU

The liability of trade unions for conduct of their members during industrial action - Mlungisi, Ernest Tenza (University of South Africa, 2016)
South Africa has been experiencing a number of violent strikes by trade unions in recent times. The issue is not only to hold unions liable for damage caused during strikes, but also to reduce the number of violent strikes. This study investigates if victims of such violence can hold trade unions liable for the violent acts committed by their members during industrial action. The Labour Relations Act, 66 of 1995 (LRA) makes provision for the dismissal of employees who commit misconduct during an unprotected strike. It also provides the remedy of an interdict and a claim for just and equitable compensation which can be made against the union, during an unprotected strike. It is further possible to hold the union together with its members liable for damages in terms of the Regulation of Gatherings Act, 205 of 1993 (RGA). The study argues that a strike or conduct in furtherance of a strike that becomes violent could lose protection and the trade union should consequently be held liable, in terms of the LRA and/ or the RGA, for damages caused by its members. This study investigates the position in Canada, Botswana and Australia to determine if there could be any other basis upon which to hold trade union liable for the conduct of its members. The study recommends that the common law doctrine of vicarious liability should be developed by the courts to allow trade unions to be held liable for damages caused by members during violent industrial action. Policy considerations and changing economic conditions and the nature of strikes in the Republic favours the expansion of the doctrine of vicarious liability to trade union member relationship.
https://uir.unisa.ac.za/handle/10500/23172
Keywords: Common law; Industrial relations; Interest arbitration; Labor unions; Liability (Law); Secret ballot requirement; South Africa; Strikes and lockouts; Tort liability of labor unions; Trade union denial; Trade union liability

Le Cameroun, État membre de l'OHADA : la souveraineté de l'État à l'épreuve de l'entreprise de construction supranationale - Awoumou, Côme Damien Georges (Université de Poitiers, 2016)
Le Cameroun demeure libre des transferts de compétences qu'il opère. Cependant, la question de la constitutionnalité de l'adhésion du Cameroun à l'OHADA demeure soulevée. Tout part de la contestation de la validité des fondements de l'insertion du droit OHADA dans l'ordre juridique camerounais, et de son impact sur les marques de la souveraineté de ce pays. D'où la nécessité d'une articulation des compétences souveraines entre l'OHADA et l'État du Cameroun. La loi n°96-06 du 18 janvier 1996 portant révision de la Constitution du 02 juin 1972 dégage des perspectives susceptibles d'améliorer la conciliation des contraintes du Cameroun comme État souverain et État partie à l'OHADA, à travers une meilleure implication de son parlement et de ses juridictions dans cette dynamique d'intégration juridique.
Keywords: Cameroon; Cameroun; Constitutional identity; Control of conventionality; Contrôle de constitutionnalité; Contrôle de conventionnalité; Contrôle juridictionnel des lois; Identité constitutionnelle; Member state; Organisation pour l'harmonisation en Afrique du droit des affaires – Cameroun; Review of constitutionality; Souveraineté; Sovereignty; Supranationality; Supranationalité; État membre

Convention de l’Union africaine sur la cybersécurité : plaidoyer pour un dépassement des traditions - Kablan, Serge; Oulai, Arthur; Sanni Yaya, Mouhamadou (Revue de droit des affaires internationales, 2016)
« Au commencement était l’Afrique ». Cette évocation, que continuent d’étayer les découvertes successives de fossiles d’Australopithèques, est à la Commission de l’Union africaine l’indication des origines temporelle et géographique de « l’immense aventure humaine du progrès ». Le continent, tout autant exposé aux phases contemporaines de l’équipée, entendues particulièrement des développements technologiques, a engagé plusieurs initiatives d’accompagnement dont l’une des plus récentes, promue par l’Union africaine, vise à doter ses 54 États membres d’une convention instituant un cadre juridique de confiance pour la cybersécurité. Il y a, dans cette convention, l’ambition triple d’organiser les transactions électroniques, d’assurer la protection des données à caractère personnel et de lutter contre la cybercriminalité. D’un point de vue prospectif, les auteurs apprécient l’effectivité de la convention eu égard à la question spécifique du commerce électronique, en tentant de déterminer si, dans sa forme comme dans sa substance, cet instrument a les moyens de satisfaire aux préoccupations de sécurité juridique et technique des différents milieux concernés.

L'application de la loi étrangère en droit international privé - Buruianã, Monica-Elena (Université de Bordeaux, 2016)
Le droit international privé, tel qu’il résulte des droits nationaux et du droit de l’Union européenne, accorde une attention particulière aux systèmes juridiques étrangers. L’application de la loi étrangère constitue l’expression de l’importance reconnue aux systèmes juridiques étrangers, mais appliquer une loi qui est extérieure au système juridique du for peut provoquer, du fait de sa différence, des réactions défensives. L’application de la loi étrangère se trouve ainsi confrontée à différents obstacles qui tendent àgarantir une application prioritaire de la lex fori. D’une part, les techniques employées par le système juridique du for pour appliquer la loi étrangère ne lui sont pas favorables, comme en témoigne l’intervention récurrente de l’exception d’ordre public international. D’autre part, des éléments exogènes au système juridique du for, comme la compréhension différente d’une même institution juridique, peuvent également faire échec à l’application de la loi étrangère. Il existe ainsi un décalage entre la lettre des règles de droit international privé du for, qui permettrait d’envisager une application fréquente de la loi étrangère et l’usagequi en est fait par les autorités du système juridique du for, qui mène souvent à sa neutralisation. Cette étude défend un meilleur respect de la lettre des règles relatives à l’application de la loi étrangère, qui aurait pour effet de promouvoir ce type d’application. Dans cette perspective, le droit international privé de l’Union européenne fournit d’importants enseignements, dans la mesure où il dynamise l’application de la loi étrangère appartenant à d’autres Etats membres.
Keywords: Abuse; Adaptation; Adjustment; Classification; Conflict of laws; Conflict rule; Conflit mobile; Conflits de lois; Droit international privé; Droit public étranger; Droits acquis; Equivalence; Foreign law; Foreign public law; Fraude; Loi étrangère; Lois de police; Mobile conflict; Ordre public (droit international privé); Ordre public international; Overriding mandatory rules; Preliminary questions; Public policy; Qualification; Questions préalables; Renvoi; Règle de conflit; Substitution

Integration through comparative private law: Four lessons from Cappelletti - Infantino, Marta (International Journal of Constitutional Law, 2016)
The aim of this article is to explore Cappelletti’s most enduring teachings relevant to those who promote global or regional integration of private laws. The article will review Cappelletti’s insights into the dynamic history of law, the need to respect diversity and take into account society’s imbalances, and the duty of comparative lawyers to engage in “applied” interdisciplinary legal research.

L’ordre juridique communautaire "OHADA" et les enjeux d’intégration du droit des affaires - Mikponhoue, Hervis Igor Cariol (Université de Perpignan Via Domitia, 2016)
Au lendemain de leur accession à l'indépendance dans les années 1960, les pays d'Afrique Francophone étaient dotés d'un système de droit privé étroitement dérivé de celui de l'ex-puissance coloniale. Pendant près de deux décennies, ces États ont fait évoluer séparément leurs législations conformément à l'expression de la souveraineté nationale même si la volonté d'unifier le droit en Afrique était matérialisée par des tentatives sous-régionales ayant peu abouti.Aujourd’hui, l’Organisation pour l’Harmonisation en Afrique du droit des Affaires(OHADA), créée depuis 1993 à Port-Louis œuvre pour une harmonisation du droit desaffaires en Afrique. Par l’adoption de ses divers actes uniformes, elle a su harmoniser voire uniformiser au plan communautaire les domaines essentiels du droit des affaires, notamment le droit commercial, le droit des sociétés et le droit des sûretés. Dans sa perspective d’intégration, elle envisage aussi d’énormes chantiers de codification afin d’étendre sa communauté à d’autres Etats encore réticents à une perte de leur souveraineté au profit d’une instance d’intégration et d’harmonisation du Droit des affaires.Dans la logique des objectifs poursuivis, nos premiers travaux de terrain ont porté sur l’ERSUMA étant donné qu’elle dispose d’une documentation très fournie sur l’OHADA, et que cette institution dont le rôle consiste à former les magistrats des divers Etats membres sur les textes communautaires, est ainsi le principal outil de vulgarisation des actes uniformes et des traités de l’organisation. Elle est donc l’une des instances les plus actives et les plusindispensables de l’OHADA.Retenons que cette perspective d’intégration de l’OHADA soulève encore d’énormesinterrogations relatives à la finalité des objectifs de l’Organisation, qui s’inscrit plus dans une perspective d’uniformisation que d’harmonisation comme le laisserait penser sa dénomination ; ajouté à l’épineuse question de la criminalisation des infractions en droit des affaires en Afrique et surtout à l’existence ou non d’un ordre juridique pour l’OHADA. Aussi, d’autres points importants, et diverses autres problématiques liées à l’intégration africaine du droit des affaires, ne présagent pas encore d’un avenir glorieux pour l’Organisation. Following their accession to independence in the 1960s, the countries of Francophone Africa were equipped with a system of private law closely derived from that of the former colonial power. During about two decades, these States have separately evolved their legislation in accordance with the expression of national sovereignty even if the desire to unify law in Africa was marked by sub regional attempts little successful. Today, the Organization for the Harmonization of Business Law in Africa (OHADA), created 1993 since in Port Louis works for business law harmonization in Africa. With the adoption of its various uniform acts, it has managed to harmonize or standardize at community level the essential areas of business law, including business law, corporation law and reliability law. In its perspective of integration, it is also considering consolidation sites in order to expand its community in other States which still reluctant to a loss of sovereignty for the benefit of an instance of integration and harmonization of business law. Let us remember that this OHADA integration perspective still raises huge questions regarding the purpose of the Organization's objectives, which fits more in a perspective of standardization over harmonization as its name would suggest; added to this sensitive issue of offenses criminalization in Business Law in Africa. Also, other important points and various issues related to African integration, which do not portent a glorious future for the Organization.
Keywords: Accountability or liability; Acte uniforme; Afrique francophone; Droit des affaires; Harmonisation; Harmonization; Integration's reform of OHADA; Reformes d’intégration OHADA; Responsabilité; Straight of business; Unification internationale; Uniform Act

Les instruments de la convergence des politiques budgétaires dans la zone UEMOA - Sawadogo, Elvis Flavien (Université de Bordeaux, 2016)
Les études juridiques portant sur les Finances publiques africaines n’abordent que très rarement les questions depolitiques budgétaires. Le caractère économique de la matière n’y est sans doute pas étranger. Or, la constitution d’espacesd’intégration économique entre Etats, partageant une même monnaie, conduit le droit, notamment communautaire à s’emparerdes questions de politiques budgétaires. Tout laxisme budgétaire de la part d’un Etat, se répercute sur les autres Etats membreset sur la stabilité de l’Union monétaire. Le renforcement de l’intégration économique, en Afrique de l’ouest, avec le TraitéUEMOA de 1994, a ainsi été accompagné de la mise en place d’un dispositif de convergence des politiques budgétaires desEtats membres. Celui-ci consiste, à travers un cadre institutionnel communautaire, à surveiller le respect par les Etats, decertains critères essentiellement budgétaires. La convergence des politiques budgétaires renvoie donc à la discipline budgétairecommune que devront respecter les Etats membres de la zone UEMOA. L’instauration d’un tel dispositif, aboutitnécessairement sur le plan normatif, à la transformation du droit public financier des Etats. Le respect de la discipline budgétairecommunautaire passe par une autodiscipline que les Etats doivent s’imposer dans la gestion de leur Finances publiques. Cenouveau pouvoir communautaire influence donc les Finances nationales au travers de leur contenu, choix de politiquespubliques comme de techniques de gestion. L’objectif de cette étude est de s’intéresser à l’un des facteurs déterminants destransformations des systèmes nationaux de gestion des Finances publiques dans les Etats membres de la zone UEMOA. Legal studies on African Public Finance rarely address fiscal policy issues. The economic nature of this subject isprobably the reason. Yet the creation of economic integration space between states sharing the same currency led the law,including community law, to take a firm hold on fiscal policy issues. Any fiscal laxity from a state has repercussions on theothers and the stability of the monetary Union. The strengthening of economic integration, in west Africa, with the WAEMUTreaty of 1994 has been accompanied by the setting up of a converging measures of budgetary policies of states members. This consists in monitoring, through a community institutional framework, compliance by states with some criteria, mainlybudgetary. The convergence of budgetary policies thus refers to common budgetary discipline to be observed by the statesmembers of the WAEMU area. The establishment of such measures necessarily ends at the normative level by thetransformation of public finance law of states. The compliance with community budget discipline goes through self-discipline that states must self-impose in the management of their public finances. This new community power has an effect on national finance through their content, their public policy choices and management techniques. The aim of this study is to take an interest in one of the determining transformations factors of national public finance management systems in the states members of the WAEMU area.
Keywords: Afrique occidentale; Ajustement structurel; Budgetary discipline; Budgetary law; Discipline budgétaire; Droit budgétaire; Droit de la comptabilité publique; Fiscal policies; Fiscal sovereignty; Monetary Union; Politique des dépenses publiques; Politiques budgétaires; Public accounting; Souveraineté budgétaire; Structural adjustment; UEMOA; Union monétaire; Union économique et monétaire Ouest africaine; WAEMU

Les systèmes financiers publics des Etats de l'UEMOA à l'épreuve de la nouvelle gouvernance financière publique - Batonon, Serge B. (Université Paris 1, 2016)
L'examen des systèmes financiers publics des États de l'UEMOA a permis de constater que ces systèmes ont évolué dans le contexte contemporain de la nouvelle gouvernance financière publique. Le souci de la transparence, de la sincérité, de la responsabilité et de l'efficacité, principes cardinaux de la nouvelle gouvernance financière publique, a permis aux États de l'UEMOA sous l'égide de la Commission communautaire de renouveler les bases normatives et institutionnelles de leurs systèmes financiers publics. Les nouvelles normes introduisent une gestion financière publique axée sur les résultats avec une plus grande responsabilisation des acteurs. Elles confortent la suprématie budgétaire du Ministre des finances tout en investissant la direction du budget d'un rôle d'avant-gardiste programmatique en matière budgétaire et le contrôle financier d'une fonction d'évaluation de la dépense publique. Elles ont mis en perspective l'action du Parlement et des juridictions des comptes des États qui doivent mettre la veille à l'efficacité de la dépense publique au cœur de leurs actions. La mise en œuvre des nouvelles normes financières publiques change l'architecture et la méthode d'élaboration du budget qui passe d'une approche de moyen à une approche de résultat. Un ensemble de technicité et de rigueur entour désormais l'élaboration du budget dont les documents de programmation et les mécanismes de conception requièrent plus d'exigences. Les mécanismes et outils de pilotage de la gestion financière des États ont également changé. L'introduction de la responsabilité managériale a rendu nécessaire la mise en œuvre des outils de pilotage empruntés au secteur privé. Mais l'analyse des réalités sociologiques et des capacités internes des États révèle que la corruption, la non application délibérée des textes et l'insuffisance qualitative et quantitative des ressources humaines, matérielles et informationnelles constituent un blocage au bon fonctionnement des systèmes financiers publics. De même, au lieu d'être du "sur mesure" les nouvelles normes paraissent encore être du ''prêt à porter'' et ne tiennent pas toujours compte des réalités sociologiques des États. C'est pourquoi, la présente thèse propose de passer de l'imitation à l'innovation institutionnelle. Elle fait de la consolidation endogène des systèmes financiers publics une condition de réussite qui passe, entre autres, par l'instauration dans les États de la bisannualité budgétaire ; des profils des députés, du comité ordonnateur dans les ministères, de la responsabilisation solidaire du comptable et de l'ordonnateur et de l'instauration d'une responsabilité morale à travers l'implication de la chefferie traditionnelle et des confessions religieuses à la discipline financière.
Keywords: Afrique occidentale; Communauté économique des États de l'Afrique de l'Ouest; Finances publiques; Gouvernance financière publique; Nouvelles normes financières; Politique économique; Public financial governance; Public financial systems; Systèmes financiers publics; UEMOA; Union économique et monétaire Ouest africaine; WAEMU

Afri̇ka’da Ekonomi̇ Hukuku’nun Uyumlaştirilmasina İli̇şki̇n Sözleşme’ye (ohada Sözleşmesi̇)* Genel Bakiş - Namlı, Mert (Public and Private International Law Bulletin, 2016)
Uzun bir suredir, bircok Afrikali devlet, ulkelerine yapilan yabanci yatirimin istenilen seviyeye ulasmamasindan yakinmakta olup, bunun baslica nedeninin ise “hukuk duzen- lerindeki belirsizlik ve istikrarsiz oldugunu tespit etmislerdir. Bunun sonucunda, bolge devletlerinin hukuk duzenlerini uyumlastirma(daha dogru bir ifadeyle yeknesaklastirma) yoluyla yeni bir “birlesik hukuk” yaratilmasi bir ihtiyac olarak belirmistir. Iste bu amacla bircok Afrikali devlet, ozellikle de Frank Bolgesi devletleri, 07.10.1993 tarihinde Port- Louis’de(Mauritus) bir uluslararasi sozlesme imzalayarak Afrika’da Ekonomi Hukuku Uyumlastirilmasi Orgutu’nu (OHADA) kurmuslardir. OHADA’nin temel amaci, Afrika’da Ekonomi Hukuku alaninda modern ve uyumlu bir hukuk yaratilarak bolge devletleri ara- sinda bu alanda hukuki entegrasyonun saglanmasidir. Bu makale, Sozlesme’nin tarihsel arka planini, temel amaci ve yontemini, cografi ve maddi kapsamini, yeknesak islemlerin temel ozellikleri ve kabul edilme usulunu, OHADA’nin kurumlari olan Devlet ve Hukumet Baskanlari Konferansi, Bakanlar Konseyi, Ortak Adalet ve Tahkim Mahkemesi, Daimi Sek- reterlik ve Bolgesel Yuksek Hakimlik Okulunu (ERSUMA) ve OHADA’nin Afrika’daki diger ekonomik ve parasal birlikler arasindaki yerini an hatlariyla tanitmayi amaclamaktadir. Anahtar Kelimeler: OHADA, Afrika, Ekonomi Hukuku, hukuki entegrasyon, uluslar arasi sozlesme.
Keywords: Afrika; Ekonomi Hukuku; hukuki entegrasyon; uluslar arası sözleşme

The OHADA Common Court of Justice and Arbitration: Exogenous Forces Contributing to Its Influence - Dickerson, Claire Moore (Law and Contemporary Problems, 2016)

Dealing with trade defence instruments in the context of economic integration in Africa - El Taweel, Khaled (University of Pretoria, 2016)
The launching of the T-FTA in June 2015 presents an opportunity for accelerating regional integration in Africa towards the establishment of a single market through deepening COMESA-EAC-SADC integration. This milestone can contribute positively to African development. Nevertheless, it faces different structural and technical challenges, including the risk of aggressive export strategies and unfair trade practices, which may wipe away a substantial part of the integration gains. This could undermine African integration plans and the largely infant industries in Africa, especially since many African countries lack sufficient technical skills, institutional capacity, and the legal framework to deal efficiently and effectively with unfair trade practices and to respond to situations which may require the application of emergency tools to better adapt to economic challenges. Apart from Egypt, Morocco, Tunisia, South Africa and Zambia national Trade Defence Instruments (TDIs) are not well developed. This could further constrain the ambitious African plans of economic integration. The thesis concludes that, although an effective TDI system is crucial for African integration as it can provide the required protection for African infant industries and unlock the potentials of African economic integration, the current African TDI systems are not effective. This is confirmed by the limited resort to TDIs in the African continent and the general perception that an effective TDI system is not a priority on the integration agenda. The concluded T-FTA TDI legal regime is not supportive for African integration plans in the long run. Africa should envisage how to upgrade its TDI system to make better use of the tools available under the WTO to deal with unfair trade measures, including anti-dumping to face dumped imports, countervailing measures to face subsidized imports, and safeguard measures to temporarily suspend concessions in the face of surge in imports. Africa can improve its national and regional TDIs system by learning from more developed TDI systems incorporated by other economic blocks such as the EU, NAFTA, Mercosur, and ASEAN. This thesis submits that the EU TDIs system is the most suitable to the African integration objectives. This submission is made while recognising the different level of development on both sides. The thesis submits that the long-term objective of the T-FTA is to have a regional investigating authority. It draws several recommendations to enhance African TDI system by working on five main categories: (A) The strategic direction; (B) The institutional framework; (C) Enhancing engagements; (D) Application of TDIs; and (E) The supportive factors.
URI: https://repository.up.ac.za/handle/2263/60043
Keywords: Economic integration; Trade defence instruments; Unfair trade practices

L’espace judiciaire pénal CEMAC : regard sur la déterritorialisation du droit pénal - Gatsi, Éric-Adol (Revue générale de droit, 2016)
Les enjeux liés à la lutte contre la criminalité transfrontalière et le raffermissement du Marché commun ont amené le législateur communautaire à jeter les bases d’un espace pénal commun dans la Communauté économique et monétaire des États de l’Afrique centrale (CEMAC). Intervenant dans un domaine où la souveraineté de l’État a longtemps été considérée comme un obstacle à toute harmonisation, la construction de l’espace pénal communautaire est perceptible sur les plans matériel et procédural. Sur le plan matériel, elle se manifeste par une communautarisation des règles pénales au moyen de l’institution d’infractions communautaires assorties de sanctions. Sur le plan procédural, la construction de l’espace pénal commun procède de la consécration, bien qu’imparfaite, du principe de la reconnaissance et de l’exécution mutuelles des décisions judiciaires en matière pénale, d’une part, et d’une procédure de coopération judiciaire qui emprunte progressivement la voie des organes communautaires, d’autre part.
Keywords: CEMAC; Coopération judiciaire; Espace pénal; Judicial co-operation; Penal space

L'effectivité du droit économique dans l'espace OHADA - Hiez, David; Menétrey, Séverine (l'Effectivité du droit économique dans l'espace OHADA, 2016)
Keywords: Droit africain; Droit coopératif; Effectivité; OHADA

Regional Powers and Leadership in Regional Institutions: Nigeria in ECOWAS and South Africa in SADC - Hulse, Merran (KFG The Transformative Power of Europe, 2016)
Regional powers are not always benevolent leaders when it comes to the building of regional institutions. While powerful states – particularly the “new” rising powers – may have a vested interest in regionalism as a means of projecting influence, regional powers may behave as coercive or benevolent leaders, or alternatively display an absence of leadership altogether. The drivers of varying regional power behavior can be attributed to their competing concerns regarding (economic) power, functional efficiency, international legitimacy, and neopatrimonial networks. This paper explores the varying behavior of Nigeria and South Africa in relation to the institutionalization of free trade areas and regional courts within their respective regions. Nigeria has displayed little leadership in ECOWAS trade integration due to domestic opposition; however, a newly-democratic Nigeria’s search for international legitimacy drove the establishment of the ECOWAS Court of Justice. Likewise, South Africa’s search for legitimacy drove its support for the SADC Tribunal, but the competing demands of different audiences led it to abandon this support. South Africa has also displayed leadership in relation to the SADC Free Trade Area; however, its neighbors perceive it as a self-interested, almost coercive actor. The findings suggest that the motivations for regional powers’ behavior vary across time and policy sectors, and that inconsistent behavior is driven by a change in the priority granted to different drivers.
Accepted: 2018-06-08T11:13:32Z https://refubium.fu-berlin.de/handle/fub188/21860

Pourquoi, en Afrique, « le droit » refuse-t-il toujours le pluralisme que le communautarisme induit ? - Le Roy, Étienne (Anthropologie et Sociétés, 2016)
Me posant cette question depuis une cinquantaine d’années, j’ai successivement écarté l’explication d’un simple laisser aller dans la reconduite de l’héritage colonial puis l’hypothèse d’une prétendue supériorité, jamais vérifiée autrement que dogmatiquement, du « droit moderne » sur la « coutume ancestrale ». Plus sérieuse fut l’explication liée à l’économie politique, un héritage marxien, et exigeant que les superstructures politiques et juridiques soient en phase avec l’insertion de l’Afrique dans le marché mondial. Mais, depuis ma participation à l’étude internationale sur les transferts de connaissances juridiques Nord-Sud, à la fin des années 1970, j’ai mis en évidence la place et le rôle de l’idéologie professionnelle des juristes et en particulier de leur philosophie spontanée idéaliste dont je dévoilerai ce qu’il masque à la lumière de mes travaux récents et selon le nouveau paradigme de la juridicité et de son pluralisme « intégral ». This question is focused on my research in the years 1960. After dismissing the continuity of policies such as bureaucratic carelessness of colonial inheritance and the hypothesis of a superiority of modern law facing to ancestral customs, I have debated an another inheritance, the Marxist one, about the link between the generalization of capitalism and legal and political superstructures. But an international project on legal transfers at the end of the 1970s’ revealed the place and role of a professional ideology, of the Lawyers, associated with technical training in law schools and enforcing monologism in the legal discourse. To escape to the effects of this ideology, we have to overhaul the analysis on the basis of the new paradigm of « juridicity » and of a « complete » pluralism.
Keywords: Colonization; Customs; Juridicity; Law and Anthropology; Legal Modernity; Marxism; Professional Ideology of Lawyers; anthropologie et droit; antropología y derecho; colonisation; colonización; costumbres; coutumes; ideología espontanea de los juristas; idéologie spontanée de juristes; juridicidad; juridicité; marxisme; marxismo; modernidad jurídica; modernité juridique

Contribuição para uma apreciação jus-internacional da integração regional africana - Moco, Marcolino (Universidade de Lisboa, 2016)
A partir da pretensão inicial, expressa no título e tema, este trabalho acaba por resultar numa reflexão aturada e solitária (como aliás muitos autores o destacam no caso das suas teses de doutoramento) que ultrapassou o mero âmbito da “apreciação jus-internacional da integração regional africana”, para desembocar num levantamento (pelo menos) de pistas sobre o fenómeno e as concepções do Direito, em geral, e particularmente na interacção historicamente inevitável entre os direitos públicos africano e euro-ocidental. Diferentemente da maioria dos trabalhos académicos sobre a África dita moderna (tanto por africanos como por outras entidades, que não precisam sequer de exibir qualquer tipo de ostensivo eurocentrismo, já minimamente extirpado do mainstream formal hodierno), que partem, geralmente, dos pressupostos teorético-formais euro-ocidentais, transportados, quase sempre de forma acrítica para o Continente, em processos legislativos e noutros aspectos hermenêutico-aplicativos do Direito, nós seguimos uma metodologia que julgamos singular. Singularidade que não reside sequer ou simplesmente na ideia de partirmos de uma pretensa rede de sistemas teorético-formais “genuinamente africanos”, o que, desde logo, conflituaria com a ideia apurada de que essa “África moderna” é uma “invenção” tão recente e prenhe de tensões que mal a deixariam criar tais sistemas com alguma consistência e coerência. Entendemos que a singularidade metodológica deste empreendimento reside, essencialmente, no facto de que tentamos partir da realidade nua e crua da factologia histórica, antropológica e cultural múltipla e diversa dessa África moderna, que resultou da traumática experiência colonial e pós-colonial, sem no entanto deixarmos de relacioná-la com o seu passado mais remoto (perante si e perante o resto da Humanidade). Ora, ao confrontarmos essa pura realidade africana com as metodologias aplicativas do direito moderno (estamos essencialmente no domínio da criação e “efetivização” do direito público, base do nosso objeto de dissertação) de matriz, necessariamente, euro-ocidental, embembido no seu extasiante perfume formal-positivista que lhe vem de Roma, do Renascimento europeu e do Século das Luzes, deparamo-nos com um enorme “buraco negro”, devorador atroz do conteúdo e do sentido desse tipo de direito, no Continente, e desintegrador, ao mesmo tempo, de sistemas tradicionais positivos, no sentido da dignidade e da dignificação humana. Concluímos, pois, que o problema não reside nem na realidade, que é e será sempre inelutável como a força do vento, nem propriamente na formulação da proposição jurídica de cariz euro-ocidental que acompanha essa infiltração, inicialmente exógena, mas que se tornaria ela própria irreversível e integradora necessária da realidade africana hodierna. Propomos, assim, uma nova metodologia de aplicação do direito: olhar para as atitudes dos agentes políticos e de outros aplicadores do Direito, acima das estritas normas jurídicas formais, perante os imperativos ético-morais que a situação do Continente exige. Quanto ao que ao “direito de integração regional e continental” diz respeito, nem sequer é o seu conteúdo e sentido que são absorvidos pelo aludido “buraco negro”, mas antes os das próprias regras adjectivas programadas para a sua criação, autonomizando-o de um direito internacional africano, ele próprio vogando em atribulados mares e agitados ”grandes lagos”. Na África Austral, particularmente na África do Sul, com base na presumível sublimação da filosofia tradicional Ubuntu, tentando sustentar uma convivência na multirracialidade e multiculturalidade, não obstante a pressão a que está sujeita pelo mainstream “afrocentrista”, encontramos o modelo em que tal “buraco negro” é, aparentemente, diminuto, tendo em conta a preservação dos dois pilares (europeu e nativo) em que assenta a sociedade, com reflexos positivos no funcionamento e aplicação do Direito, na base de um casamento, aparentemente ideal, entre a tradição e a modernidade. Enquanto isso, em Angola, estudada como caso médio da África Negra, encontramos o protótipo de uma sociedade em que o “buraco” devorador de conteúdos e sentidos jurídicos é avassalador, como resultado tanto de uma política assimilacionista-integracionista colonial, seguida de outra, a do racionalismo marxista-leninista, que contribuiu para o acanhamento e desvirtuamento da axiologia nativa ou tradicional, completando-se o drama com a diluição dos valores positivos da modernidade ocidental, com as prolongadas guerras civis que determinaram, inicialmente, um êxodo considerável de populações de origem europeia, como suportes deste outro pilar da construção da nação africana moderna, em Angola. De todo o modo, podemos nos aperceber de alguns traços de um direito de integração regional africana, reflectidos e sustentados, ao mesmo tempo, no e pela emergência de uma frágil jurisprudência. Fica a dúvida de se saber se esses diáfanos traços poderão sobreviver à virulência das “próximas chuvas” e preencher-se de vez o vazio lamentado pelos últimos pan-africanistas como Ki-Zerbo e Édem Kodjo
http://hdl.handle.net/10451/27578

Democracy and Accountable Governance in the SADC Region - Omede, Jolade; Akindola, Rufus; Ngwube, Arinze (African Journal of Politics and Administrative Studies, 2016)
The call for democracy worldwide is based on the assumption that it allows citizens involvement on how they are governed. Being a representative system of government, democracy is projected to make political leadership responsive and responsible to the entire citizenry of the state. Southern Africa region has the most animated economy in sub –Sahara Africa, and democratic ideals appear more firmly established in the region compared to other regions in Africa. This has made the region, among others in the continent, the preferred choice of many migrants from different parts of the world. It is believed that the region has reached its Eldorado. However, a close observation of the politics of that region tends to suggest there has been the institutionalization of democratic rule without commensurate enthronement of responsible and accountable governance. This study systematically examined the political configurations of the region to concretely determine how the practice of liberal democracy in the sub-region has translated to accountable and responsible governance and its overall impact of the living standard of the citizens of the countries of that region. The paper examined accountable governance in the sense that leaders will be able to mange resource of the state for the well being of the populace. The reverse has been the case for the region. Southern Africa needs a developmental and capable state for socio-economic progress and sustainable democracy. This cannot be achieved without responsible political leadership, which would be responsive to the yearnings of the people. The mode of analysis was based on secondary sources and observation method. The paper adopted secondary and observation techniques as the mode of analysis
Keywords: Accountability; Democracy; Development; Governance; Leadership

Harmonisation du droit européen des contrats: enjeux et défis - Atmani, Bilal (Revue Académique de la Recherche Juridique, 2015)
L’harmonisation du droit des contrats demeure un objectif à atteindre pour la commission européenne qui a multiplié les appels au rapprochement des règles du droit des contrats au niveau interne tout en respectant la souveraineté des Etats membres de l’union. La commission européenne a réaffirmé, à l’occasion de l’adoption de deux résolutions adoptées en date des 23 mars 2006 et 06 septembre 2006, sa conviction qu’un marché intérieur uniforme ne peut être pleinement opérationnel sans de nouveaux efforts d’harmonisation du droit civil. Ma contribution vise à étudier la politique européenne en matière d’harmonisation du droit des contrats et mettre en lumière le constat de cette politique.
Keywords: Contrats; Droit des contrats; Droit européen; Harmonisation; Principes fondamentaux; Sécurité juridique

La sécurité civile dans les Etats de la Communauté Economique et Monétaire de l'Afrique Centrale (CEMAC) - Ngolle III, Patrice Emmanuel (Université de Montpellier, 2015)
La sécurité civile des Etats de la Communauté Économique et Monétaire de l’Afrique Centrale, dont la mission première est de protéger les personnes, les biens et l’environnement fait face à la diversité des risques et des crises contemporains. La vulnérabilité et l’insouciance quasi généralisées dans cette partie de l’Afrique, aggravées par des contraintes chroniques dues à la pauvreté et la faiblesse des cadres institutionnels les exposent aux conséquences meurtrières et désastreuses des catastrophes.La situation est préoccupante ; mais la matière peine à rentrer dans les priorités des politiques publiques, tant en interne dans le cadre de chaque Etat de la C.E.M.A.C, que sur le plan sous régional.Les actions initiées çà et là au plan institutionnel, juridique et humain demeurent timides. Une des raisons majeures est que la sécurité civile dans cette partie du continent est relativement jeune et partagée entre une multitude d’acteurs confrontés en permanence aux événements dramatiques et à la complexité des crises.Elle a, plus que d’autres disciplines, besoin d’être précisée et consolidée. La question majeure qui structure le travail entrepris est par conséquent celle de savoir comment faire face aux situations complexes, éviter et prévenir les crises dans un environnement où les vulnérabilités sont décuplées par la pauvreté ? Autrement dit, que faire en cas de catastrophe dans un contexte où la capacité d’anticiper et de gérer les risques est particulièrement limitée ?A partir de la démarche juridique, mais aussi interdisciplinaire, l’on a montré la limite du modèle classique sur lequel repose principalement les systèmes de sécurité civile des Etats de la C.E.M.A.C, au détriment d’autres modèles pertinents de gestion crises (prise en compte des vulnérabilités et de la résilience) qui n’apparaissent dans le droit de la sécurité civile de ces Etats que sous forme de linéament.La réalité est claire et brutale : les risques et les catastrophes sont omniprésents en zone C.E.M.A.C, telle une ombre projetée sur le présent et le futur. Ce catastrophisme étale l’absence de développement de a sous-région et la faible diffusion des technologies et des savoirs. Face à cette situation inédite, outre la prévention des risques, l’on a préconisé de briser les sentiments d’impuissance, d’apprendre à affronter la catastrophe, à cesser de l’imaginer dans un futur improbable ; mais à la penser au présent, à expérimenter les capacités de résister et de résilience. Il devient dès lors essentiel de renouveler l’organisation générale de la sécurité civile des Etats de la C.E.M.A.C. A cet égard, l’émergence et /ou le renforcement d’un modèle communautaire de protection des personnes consoliderait le dispositif sous régional de sécurité civile. La recherche d’une gouvernance éclairée et participative peuvent aussi être des vecteurs minimaux, mais puissants de relance d’une garantie de la sécurité humaine et des droits fondamentaux. Civil security in the Economic and Monetary Community of Central African States, whose main objective is the protection of persons, goods and the environment, is faced with different contemporary risks and crisis. The quite widespread vulnerability and disregard in this part Africa, heightened by unabating constraints caused by poverty and weak institutional frameworks exposes them to deadly and disastrous disaster consequences.The situation is alarming; yet it is hardly a priority on government policies, both in the internal policies of each CEMAC member state and at the sub regional level.The various actions initiated here and there at the institutional, legal and human levels are still timid. One of the major reasons is that civil security in this part of the continent is relatively young and divided amongst a multitude of actors confronted permanently with dramatic events and the complexity of the crisis.Moreover, it needs more than other fields, to be specified and consolidated. The major problem which is developed in the thesis is then, how to face the challenging issues, avoid and prevent crisis in an environment where the vulnerabilities are enhanced by poverty? In other words, what happens during a disaster in a context where the ability to preempt and to manage risks is particularly limited?From the legal approach, as well as interdisciplinary, we have revealed the limits of the classical model which civil security systems of CEMAC states basically depend on, to the detriment of other relevant models of risk management(taking into account vulnerability and resilience) which feature on the law of civil security of these states just as an alignment.The reality is clear and brutal: risks and disasters are omnipresent in the CEMAC zone; this is the shadow overbearing the present and the future. This gloom reveals the absence of development of the sub region and the poor dissemination of technology and knowledge. Faced with this unprecedented situation, besides risk prevention, we call on breaking this feeling of helplessness, master disaster management, cease from imagining it far-fetchedly; but to think of it in the present, evaluate the resistance and resilience capacities. It is therefore necessary to renew the general organization of civil security in CEMAC states. In this vein, the emergence and/or the enhancement of a community model of protection of persons shall reinforce the sub regional civil security mechanism. The search for informed and participative governance can also be minimum vectors, but powerful catalyst to guarantee human security and fundamental rights.
Keywords: Catastrophes; Civil protection; Civil security; Communauté Economique et Monétaire de l'Afrique Centrale; Disasters; Economic and Monetary Community of Central African States (CEMAC); Gestion des situations d'urgence; Protection civile; Risks; Risques; Sécurité civile

Une approche régionale de l’harmonisation du droit des affaires : l’exemple de l’OHADA - Haddoum, Kamel (Annales de l’université d’Alger, 2015)
Pour faire face au phénomène de la mondialisation du marché international des affaires et des défis qu’il met en jeu, le développement économique semble s’orienter de plus en plus vers une approche régionale afin de mieux défendre les intérêts nationaux pourtant souvent contradictoires. En effet, la mondialisation de l’économie exige la mondialisation du droit., l’un des exemples le plus illustratif, nous viens de l’Afrique, qui a privilégié l’intégration régionale par le droit des affaires, à travers la création de l’Organisation de l’OHADA qui devait permettre à une partie de l’Afrique de mieux s’intégrer à l’économie mondiale, de faciliter les échanges entre les Etats parties, d’attirer les investisseurs étrangers, et de mettre fin à l’insécurité juridique. Selon les initiateurs du traité OHADA, l’intégration économique qui est une condition sine qua non du développement de la région, ne peut réussir, qu’à travers la mise en place d’une harmonisation du droit des affaires. Le fonctionnement de L’OHADA s’appuie sur un certain nombre d’organes et sur l’élaboration de plusieurs Actes Uniformes touchant au domaine du Droit des Affaires constituant ainsi le droit dérivé. Néanmoins face à un environnement économique et juridique en constante évolution, l’OHADA était dans l’obligation de mener des réformes d’ordre institutionnel et normatif.
Keywords: Actes Uniformes; Afrique; Arbitrage africain; Droit des affaires; Economie Africaine; Harmonisation juridique; OHADA; Régionalisation

Une approche régionale de l’harmonisation du droit des affaires : l’exemple de l'OHADA - Haddoum, Kamel (Annales de l’Université d’Alger, 2015)
Pour faire face au phénomène de la mondialisation du marché international des affaires et des défis qu’il met en jeu, le développement économique semble s’orienter de plus en plus vers une approche régionale afin de mieux défendre les intérêts nationaux pourtant souvent contradictoires. En effet, la mondialisation de l’économie exige la mondialisation du droit., l’un des exemples le plus illustratif, nous viens de l’Afrique, qui a privilégié l’intégration régionale par le droit des affaires, à travers la création de l’Organisation de l’OHADA qui devait permettre à une partie de l’Afrique de mieux s’intégrer à l’économie mondiale, de faciliter les échanges entre les Etats parties, d’attirer les investisseurs étrangers, et de mettre fin à l’insécurité juridique. Selon les initiateurs du traité OHADA, l’intégration économique qui est une condition sine qua non du développement de la région, ne peut réussir, qu’à travers la mise en place d’une harmonisation du droit des affaires. Le fonctionnement de L’OHADA s’appuie sur un certain nombre d’organes et sur l’élaboration de plusieurs Actes Uniformes touchant au domaine du Droit des Affaires constituant ainsi le droit dérivé. Néanmoins face à un environnement économique et juridique en constante évolution, l’OHADA était dans l’obligation de mener des réformes d’ordre institutionnel et normatif.

Attractivité économique des investissements directs étrangers en zone CEMAC : harmonisation des instruments juridiques aux règles internationales - Memphil Ndi, Evelyne Patience (Université de Nice Sophia-Antipolis, 2015)
Les courants de la mondialisation des marchés, marqués par la libre circulation des capitaux et le phénomène du libre-échange ont favorisé la mise en œuvre de politiques communautaires de relance économique et d’attractivité des territoires. C’est dans cette lancée que des regroupements géographiques à visée économique comme la Communauté Économique et Monétaire de l’Afrique Centrale (CEMAC) sont apparus. Six pays de l’Afrique Centrale dont le Cameroun, le Congo, le Gabon, la Guinée Equatoriale, la République Centrafricaine et le Tchad en sont membres et font l’objet de notre analyse sur l’attractivité économique de l’investissement Direct étranger (IDE) dans cette sous-région. L’IDE est devenu un acteur incontournable du processus de développement, et la zone CEMAC une destination privilégiée pour les investisseurs. Il apparait néanmoins une ambiguïté dans les rapports entre le flux d’IDE, la croissance économique et le développement des pays membres de la CEMAC : le taux sans cesse croissant des flux d’IDE entrants dans la sous-région, n’est malheureusement pas toujours synonyme de croissance économique. Pour comprendre ce paradoxe, l’on procède à une analyse des instruments encadrement de l’IDE dans la sous-région CEMAC. Il en ressort que, pour un rendement optimal de ces dispositifs et la garantie d’une croissance économique à long terme dans ces États, il est nécessaire d’associer les politiques actuelles d’attractivité économique des IDE, à une diversification des domaines économiques exploitables , mais aussi adapter les standards internationaux aux spécificités socioculturelles mais aussi économiques de la sous-région CEMAC. The currents of the globalization of the markets, marked by the free movement of capital and the phenomenon of free trade supported the implementation of Community policies of economic revival and attractivity of the territories. It is in this impetus that geographical regroupings with economic aiming like the Economic community and Monetarist of Central Africa (CEMAC) appeared. Six countries of Central Africa of which Cameroon, Congo, Gabon, Equatorial Guinea, the Central African Republic and Chad are members and are for it, the object our analysis on the economic attractivity of direct foreign investment (FDI) in this under-area. The FDI became an inevitable actor of the development process, and CEMAC zones, a privileged destination for the investors. It appears nevertheless an ambiguity in the relationship between the flow of FDI, the economic growth and the development of the member countries of the CEMAC : the rate unceasingly crescent of flows of FDI entering the under-area, is unfortunately not always synonymous with economic growth. To understand this paradox, one carries out an analysis of the instruments framing of the IDE under-area CEMAC. This reveals that, for an optimal output of these devices and the warranty of one long-term economic growth in these States, it is necessary to associate the current policies of economic attractivity of the FDI, with a diversification of the exploitable economic domains, but also to adapt the international standards to sociocultural but so economic specificities of under-area CEMAC. The case of the countries of the BRICS can in this respect, being used as illustration for an “other way” of thinking the development.
Keywords: Afrique centrale; Attractivité économique; Communauté Economique et Monétaire de l'Afrique Centrale; Conditions économiques; Economic attractivity; Foreign direct investment; Harmonisation; Harmonization; Investissements directs étrangers; Investissements étrangers

La CEDEAO entre interétatisme et supranationalité - Diouf, Moustapha (Université Cheikh Anta Diop, 2015)
Keywords: CEDEAO; Intégration régionale

Le déclin de exorbitance du droit administratif sénégalais sous l’effet du droit communautaire - Kebe, Abdou Aziz Daba (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2015)
I) L’indifférence du statut de la puissance publique dans l’applicabilité du droit communautaire A) La prépondérance du critère matériel d’application du droit communautaire 1) Le critère de commercialité dans la législation OHADA 2) L’entreprise dans la législation UEMOA B) Le maintien exceptionnel du critère organique pour l’application du droit communautaire 1) Une immunité d’exécution conférée aux organismes publics 2) L’élargissement par la CCJA du spectre des personnes bénéficiaires de l’immunité d’exécution II) Une restriction du champ d’application du droit administratif A) L’expansion du doit communautaire dans les secteurs d’activité de la puissance publique 1) La soumission du service public aux règles concurrentielles 2) L’immixtion du droit privé dans le domaine des contrats administratifs B) Le contournement du juge de l’administration 1) Le droit pour les personnes publiques de recourir à l’arbitrage 2) La renonciation par l’administration à son privilège de juridiction Conclusion

Law and Development in West and Central Africa OHADA - Winship, Peter (SMU Dedman School of Law Legal Studies Research Paper, 2015)
This seminar paper considers whether OHADA - an experiment in unifying business law in African countries - has been a success. Following a prologue that explains the origins of the paper, the first part of the paper sets out basic information about the Organisation pour l’Harmonisation du Droit des Affaires en Afrique (“Organization for the Harmonization of Business Law in Africa,” known by the acronym OHADA). This part is followed by a review of law and development literature to assess the value of this literature for an evaluation of the success (or not) of OHADA. A third part then focuses on one specific uniform law, the law of secured transactions. The paper concludes that notwithstanding challenges the OHADA institutions exist and have produced uniform business laws for the formal business sector. Whether OHADA has been the cause of increased investment and trade requires studies that have not been carried out.
Keywords: African law; Secured transactions; commercial law; law and development; law reform; unification of law

Toward an Elaboration of a More Pluralistic Legal Landscape for Developing West African Countries: Organization for the Harmonization of Business Law in Africa (OHADA) and Law and Development - Hiez, David; Menétrey, Séverine (The Law and Development Review, 2015)
In Europe and especially in France, the African business law landscape, as well as the legal discourse, for developing West African countries is almost exclusively dedicated to OHADA, the Organization for the Harmonization of Business Law in Africa, created in 1993. While economic development in the Member States is the obvious underlying reason for the modernization and unification of African business law, the exact nature of such development remains uncertain, as does the manner in which a such result can or will be achieved. OHADA’s Uniform Acts are, with some minor exceptions, a carbon copy of French business law. The only goal is to increase international investment, which, in turn, is expected to generate economic development, but all without taking any notice of equality or social justice issues. That, without a doubt, is the reason why OHADA is constantly criticized as a law that benefits foreign investors, while remaining ineffective, even illusory, for local traders. To go beyond the criticism, the authors have decided to focus on the relationship between law and the informal sector and to draw lines between formal and informal rules in the business sector.
Keywords: Informal rules informal sector; OHADA (Harmonized Business Law in Africa); informal rules; informal sector

Business in West and Central Africa: The Legal Framework - an Introduction to the Laws of the OHADA - Hahn, Anne-Catherine; Darbellay Suso, Aline; Desax, Robert; Herzog, Sabine; Meyer, Manuel; Monnier, Philippe; Schnyder, Marion; Zemp, Rafael (Baker & McKenzie, 2015)

The impact of non-operationalisation of the SADC protocol and international transport agreements on cross border road transport movement in the SADC region - Monyepao, Kaine (Working Together to Deliver - Sakha Sonke, 2015)
The failure by Sothern African Development Community (SADC) countries to fully implement the SADC Protocol on Transport, Communications and Meteorology (the Protocol) and bilateral agreements in regard to road transport negatively impacts the seamless movement of cross border road transport and significantly contributes to the challenges faced by the cross border industry as a whole. The full implementation of the Protocol in regard to road transport, and bilateral agreements would lead to efficient cross border transport regulation and transportation and in turn culminate in reduction of challenges facing the sector. This would lead to reduction of transportation costs, improvement in productivity, and accelerated growth in intra-regional trade, regional economic integration and overall SADC socio-economic development. This paper outlines the extent to which the provisions of the Protocol and bilateral agreements have been implemented by SADC countries and the key challenges emanating from the partial operationalisation of the instruments. The paper is based on findings from engagements with key government and private sector stakeholders in the regional transport environment and various research conducted by the C-BRTA between 2011 and 2014. The partial operationalisation of the instruments has resulted in disjointed regulatory frameworks and inability to: holistically address corridor constraints/ non-tariff barriers, facilitate seamless cross border movements, facilitate liberalisation of access to transport markets in the region, harmonise standards and procedures, and facilitate economic growth and trade between SADC countries. It is possible for the SADC region to realise the aspirations set out in the Protocol and bilateral agreements, and this paper outlines some of the solutions. To begin with, there is need for SADC countries to embrace the need to eradicate the existing self-centric regulatory approach limited to micro-needs and market protectionism. This would need to be underpinned by strong orientation towards the need to achieve macro benefits emanating from a regional perspective in regard to regulating cross border road transport movement. Taking off from this departure point, SADC countries can objectively establish a solid ground towards fully operationalising the Protocol and bilateral agreements. This paper outlines some of the interventions that can be implemented to ensure SADC countries fully operationalise the provisions of the Protocol on transport and bilateral agreements.
Accepted: 2016-11-08T12:11:22Z Artwork Medium: PDF Interview Medium: PDF
Keywords: Southern African Transport Conference; Transportation

Building legal bridges: fostering eastern Africa integration through commercial arbitration - Muigua, David K. (Alternative Dispute Resolution, 2015)
This paper explores the feasibility of commercial arbitration as a means to foster the process of Eastern Africa integration. The author proffers an argument in the context of Eastern Africa integration, that commercial arbitration offers a better platform for dealing with commercial disputes that are bound to arise considering the differing personal or state interests in the ongoing Eastern Africa integration, as compared to national Courts. This discourse is premised on the fact that the five member countries making up the East African Community (EAC) have different legal systems and this presents a major challenge in harmonising the various legal systems. This also affects the possible use of courts in managing the potential transnational commercial disputes due to the potentially different rules of procedure and practice. The paper briefly examines the state of commercial arbitration in the EAC Member States with a view to identifying the existing frameworks and any impediments in their effectiveness. Finally, the author makes a case for utilizing commercial arbitration to build bridges and foster Eastern Africa integration for development.
http://erepository.uonbi.ac.ke/handle/11295/81712
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Establishing continental sovereignty in Africa: risk and opportunity in financial integration - lessons for Africa from a legal perspective - Ngwafor Ndeh, Edwin (University of Glasgow, 2015)
This thesis identifies and defines the new African sovereignty. It establishes a modern sovereignty in Africa hatched from the changing nature of sovereignty in which countries come together at various levels or grades of partial surrender of national sovereignty in order to work closer together for their mutual advantage and benefit. To this end, the narrative zooms in on the central issues within the realms of money matters whereby a new model of monetary sovereignty and monetary solutions is designed in an attempt to ease the recurring tensions and challenges of modern national sovereignty in the continent of Africa. As such, this discussion will offer a historical journey through the constitution of sovereignty, to the birth of the nation state and international public law. It develops the theory of the changing nature of sovereignty within the modern state and opens new lines of inquiry for Africa. In this regard, it draws from juxtaposing and mixing elements of regional and global financial integration as well as retaining national financial sovereignty features to form this new design which I dub continental sovereignty. At its core, the thesis will deal with the legal aspects that stem from the co-mingling of legal systems of nation states and communities at the regional and global levels within the context of financial integration. The argument is that the rule of law remains sacrosanct in monetary management. Effective financial integration is the result of properly structured and managed legal frameworks with robust laws and institutions whether at a national, regional or global level. However, the thesis reveals that in order to avoid undermining the progress of Africa’s financial integration project, any solution for Africa must be immersed within a broader global solution where development issues are addressed and resolved and Africa can form a more central part in all relevant international discussion fora. The work will expound these issues by applying them within a regional and global context, with the state of affairs in Africa forming the nucleus. This application consequently presents the six key themes of the thesis which will be considered therein. They are: a.) regional advantage: which exploits the possibilities of deeper and further financial integration between smaller communal arrangements; b.) regional risk and exposure: the extent to which this deeper form of financial integration can spiral out of control if effected too quickly and too ambitiously; c.) global advantage: which considers the merits of global financial integration and the influence exerted by financial laws on the global financial architecture; d.) global risk and exposure: which considers the challenges of global financial integration especially within the background of the Global Financial Crisis 2007-2008; e.) African challenge: which considers the extent to which this analysis impacts the African economic and financial integration agenda; and f.) development challenge: which examines the extent to which global development issues impact the African solution (continental sovereignty) and the need for any solution for the continent to be roped into a broader global solution within which Africa can form an important part. Even though the thesis requests an optimistic undertone on the progress made so far, it unearths the African problem of multiple national sovereignty and multiple overlapping regional sovereignty constituted as the ‘spaghetti bowl’ dilemma. As such, the unique contribution to knowledge on financial integration in Africa can be echoed in these words: Africa‘s financial integration agenda has had little success in authenticating a systematic and dependable legal framework for monetary management. Efforts made have been incomplete, substandard, and not carefully followed through particularly reflected in the impuissant nature of the judicial enforcement mechanisms. Thus, the thesis argues that, any meaningful answer to the problems dogging the continent is inter alia deeply entrenched within a new form of cooperative monetary sovereignty. In other words, the thesis does not prescribe the creation of new laws; rather it advocates the effective enforcement of existing laws.
Keywords: African Integration Project; Crisis response; Financial crisis; Financial integration; Regional systems; Regulation of financial markets; continental sovereignty

Exploring shared governance as an alternative institutional model for the Southern African development community - Nyathi, Mkhululi (University of Pretoria, 2015)
The Southern African Development Community (SADC) was initially established as a coordination conference in 1980 and was transformed into a treaty organisation in 1992. Challenges of lack of coordination, inefficiency and lack of policy harmonisation led to the amendment of the Treaty in 2001. While the amendment of the Treaty served to address some of the challenges of the organisation, it failed to address the core challenge of the democratic deficit inherent in SADC s governance framework. While the SADC Treaty has as part of its principles and objectives the observance and promotion of democracy and the rule of law, both in its own processes and in its Member States, the design of the SADC institutions does not reflect these normative values. Governance of SADC is characterised by excessive executivism under the overarching powers of the Summit of Heads of State or Government. This democratic deficit is most prominently evidenced by the suspension and eventual disbandment of the SADC Tribunal, the only judicial organ of the organisation. The suspension and disbandment of the Tribunal, in addition to the obvious issue of legality that it raises since it was done in the absence of Treaty amendment, also raises the fundamental question of decision making in SADC in general, as the current treaty framework does not provide for meaningful conversation between and among the key institutions of SADC in matters involving policy formulation and implementation. There is also no institution with a strong oversight role in SADC. There is need for constitutional change in SADC if the organisation is serious in its commitment to achieve its objectives, which it has defined as its Common Agenda. This study proposes a treaty based reform process that is informed by the institutional model of shared governance. One of the several core tenets of this model is that in an organisation, there should be meaningful conversation among the internal stakeholders before a decision is made. For such conversation to be meaningful, there should be the broadest possible exchange of information among the components of an organisation. The proposals made by this study include transforming the Secretariat into an effective institution that formulates SADC laws and policies as well as their implementation frameworks; creation of a SADC parliament that would play a meaningful role on the amendment of the SADC Treaty and in the adoption of the budget; and an independent and accessible judicial body with significant powers of review. Shared governance as conceptualised in this study is not a substitute for, nor does it compete with related concepts like constitutionalism, separation of powers, the rule of law and participatory democracy, but in fact complements them. In addition to these proposals, there is a recommendation for the adoption of a robust access to information regime in which the shared governance institutional model would be anchored. There is also a recommendation for a new regime of law making through community legal instruments that would be directly applicable in Member States as opposed to the largely ineffective protocols.
URI: https://repository.up.ac.za/handle/2263/52280
Keywords: Civil society engagement; SADC; Southern African Development Community

L'union économique et monétaire ouest africaine (UEMOA) : une nouvelle approche de l'intégration économique en Afrique de l'Ouest - Cissé, Mouhamadou Makhtar (Université Cheikh Anta Diop, 2014)
Keywords: Intégration économique; UEMOA; WAEMU

Regional Integration in Africa through the Harmonisation of Laws - Simo, Regis Yann (Regional Integration and Policy Challenges in Sub-Saharan Africa, 2014)
Domestic laws on the African continent have been considered inadequate to attract the investment needed for development and economic growth. A crucial catalyst in attracting investment on the continent is law reform. The formulation of legislation has twofold effects: firstly, it is perceived to mitigate the risks associated with doing business in Africa; secondly, it legally obligates African governments to comply with standards of protection accorded to international investors through the regulation of the business environment. The formulation of legislation is a key determinant of the quality of investment attracted to the continent. This Chapter assesses how the Organization for the Harmonization of African Business Law (OHADA) has contributed to regional integration and economic growth on the continent.
Keywords: Africa; Institutions; Law Reform; OHADA; Regional integration

Law and Development à L'Africaine: Evidence from the OHADA's Harmonization Process - Simo, Regis Yann (African Yearbook of International Law, 2014)
Until recently, doing business in developing countries, and in Sub-Saharan Africa in particular, was associated with high risk. Although each investment decision is associated with some risk, there are always obligations incumbent on host States in that regard. However, when domestic law is too obsolete to match the requirements of an evolving investment and commercial environment which it is supposed to regulate, and when its effects are unpredictable, one of the fundamental conditions for attracting investment goes missing. This eventually underscores the need for a legal reform. The phenomenon of 'globalisation' on the one hand, and the need for (developing) countries to integrate their economies into the global market, on the other hand, considerably accentuated the postulate of development through law.Against this background, some African countries, at the dawn of the 1990s, felt a need to 'modernise' their legal systems for the major part inherited from colonialism. In this vein, they entrusted a supranational organ, the OHADA, to perform that legal reform. This paper is an attempt to test the OHADA against the discourse of law as a development engine. Furthermore, this is an assessment of the extent to which OHADA, as a legal tool, could be useful in serving the purpose of regional integration and economic growth in Africa.
Keywords: Africa; Comparative Law; Law and Development; Law and economics; Law and finance; OHADA

Harmonising Public Procurement in the SADC - Harpe, Stephen de la (Journal of Law, Society and Development, 2014)
The promotion of international trade is seen as one of the important instruments to ensure development in developing nations and regions. The history of the World Trade Organisation (WTO) and the drafting of many regional and similar international trade agreements are evidence of this. The Southern African Development Community (SADC) is no exception.1 It is therefore strange that many states that are members of the WTO and actively encourage the opening up of international borders to free trade do not include public procurement2 in such free trade arrangements. This is particularly evident in developing states. If the WTO Government Procurement Agreement (GPA), which is a plurilateral agreement, is considered it is clear that many states do not wish to open their internal markets to competition in the public procurement sphere. It is therefore not surprising that public procurement has been described as the last rampart of state protectionism (Ky, 2012). Public procurement is an important segment of trade in any country (Arrowsmith & Davies, 1998). It is estimated that public procurement represents between 10% and 15% of the gross domestic product (GDP) of developed countries and up to 25% of GDP in developing states (Wittig, 1999). Unfortunately, governments often expect private industry to open up national markets for international competition but do not lead the way. Except for the limited use of pooled procurement,3 no specific provision is at present made for the harmonisation and integration of public procurement in the SADC. In view of the proximity of the member states, the interdependency of their economies and the benefits that can be derived from opening up their boundaries to regional competition in public procurement, the possibility of harmonisation and deeper integration in this sphere needs to be given more attention. The importance of public procurement in international trade and regional integration is twofold: first, it forms a substantial part of trade with the related economic and developmental implications; secondly, it is used by governments as an instrument to address socio-economic issues. Public procurement spending is also important because of its potential influence on human rights, including aspects such as the alleviation of poverty, the achievement of acceptable labour standards and environmental goals, and similar issues (McCrudden, 1999). In this article the need to harmonise public procurement in the SADC in order to open up public procurement to regional competition, some of the obstacles preventing this, and possible solutions are discussed. Reference is made to international instruments such as the United Nations Commission on International Trade Law (UNCITRAL), the Model Law on Public Procurement and the GPA. In particular, the progress made in the Common Market for Eastern and Southern Africa (COMESA) with regard to the harmonisation of public procurement, which was based on the Model Law, will be used to suggest possible solutions to the problem of harmonising public procurement in the SADC.

Political and Economic Integration in the SADC: Reforming the Energy Sector Regulatory System - Jobodwana, Z. Ntozintle (Journal of Law, Society and Development, 2014)
The Southern Africa Development Community (SADC), the African Union (AU) and other African regional economic communities (RECs) have as their ultimate objective the political and economic integration of the African continent. The SADC is home to a number of countries, all of them striving to improve their investment climate to attract foreign investors by reducing the costs of doing business in the region. One way of achieving this is by setting targets for and speeding up political and economic integration, improving interconnectivity and thereby enlarging the market size and enhancing its attractiveness. The SADC region still suffers from high levels of energy poverty through low access levels in all countries except South Africa and Mauritius. Numerous studies have shown that greater regional trading and cooperation on power development within the SADC could substantially reduce investment and operational costs as well as carbon emissions. The need for a regional power trading pool and regional cooperation grew out of the power utilities’ recognition of the vulnerability of individual countries if each continued to pursue a policy of self-sufficiency rather than out of a desire to minimise the social or financial costs of the region’s power. The power sector in southern Africa is undergoing tremendous reforms, more especially since the establishment of the Southern African Power Pool (SAPP) in August 1995. The SADC, however, faces serious challenges that include diminishing surplus generation capacity and the need to ensure that SADC citizens have equitable access to electricity at affordable prices. To meet these challenges, treaties and protocols have been adopted but are failing to deliver at the implementation stage. This article reviews the SADC energy-electricity regulatory framework in the context of economic and political integration and recommends the establishment of an independent regional regulatory authority to oversee the implementation of integrated holistic energy and air pollution control and prevention, and a common climate change policy. Such a regulator would be a highly resourced regional institution that will liaise with international institutions. This independent regional authority will serve as a catalyst for regional economic integration. It will also have a mandate to introduce and coordinate the establishment of an SADC regional emissions trading scheme that will contribute to managing the mitigation of greenhouse gases (GHGs) and the implementation of global warming adaptation strategies in the region.
Keywords: Climate change; Economic integration; Energy regulation; GHGs; Global warming; Political integration; Regional independent regulatory authority; SADC; SAPP; Treaty regime; UNFCCC

Harmonising the law of sale in the Southern African Development Community (SADC) : an analysis of selected models - Shumba, Tapiwa (Stellenbosch University, 2014)
It is generally recognised that diversity of laws may act as a barrier to the development of trade, both at international and regional level. In a globalised era, trade is necessary for economic development and ultimately for the alleviation of poverty. Although the WTO has done extensive work towards the removal of tariff barriers, there is also a need to focus on addressing non-tariff barriers which include legal barriers to trade. Institutionalised legal harmonisation at an international level has provided the necessary impetus for the development of harmonised laws in the area of international trade. The creation of regional economic communities within the purview of the WTO has also given rise to the necessity of legal harmonisation to facilitate intra-regional trade. A number of regional economic communities and organisations have noted legal harmonisation as one of their areas of regional cooperation. This study focuses on the need to harmonise the law of international sale within the SADC region in order to facilitate cross-border trade. The study points out that the harmonisation of sales laws in SADC is important for the facilitation of both inter-regional and intra-regional trade with the aim of fostering regional integration, economic development and alleviating poverty. Although the necessity of harmonising sales laws has been identified, no effort to this end exists currently in the SADC region. This study addresses the mechanisms by which such harmonisation could be achieved by analysing three models which have been selected for this purpose, namely the CISG, the OHADA and the proposed CESL. The main issues addressed include whether SADC Member States should adopt the CISG, join OHADA, emulate the CESL or should use any of the other instruments as a model for creating a harmonised sales law for SADC. In conclusion, it is observed that SADC has its own institutional and operational mechanisms that require a process and instrument tailor-made for the unique needs of the region. It is recommended that SADC should create its own common sales law based on the CISG but taking into account lessons learnt from both the OHADA system and the CESL. A number of legislative, institutional and operational transformative and reform mechanisms are recommended to enable the creation of such a community law and ensure its uniform application and interpretation.
Keywords: Africa; Economy; Foreign trade promotion; International unification; Mercantile law; Regional disparities; SADC; Southern African Development Community; Trade law

Diaspora, African Union and Sustainable Regional Integration in Africa - Asogwa, Felix; Didiugwu, Ifeanyi (African Journal of Politics and Administrative Studies, 2014)
The role of African Union in the African integration project has remained a topical issue among scholars. Various views have been canvassed on how to strengthen African Union for a more effective regional integration in Africa. This paper examined the central role the African Diasporas can play in repositioning African Union for a sustainable regional integration in Africa. Its analysis of the situation was anchored on the mo-functionalist integration framework and applied essentially the secondary data gathering techniques. Among other recommendations, it suggested for the creation of a pan-African Diaspora Organization.
Keywords: African; Diaspora; Regional integration

Globalization and Private International Law in Commonwealth Africa - Oppong, Richard (University of Arkansas at Little Rock Law Review, 2014)

Nuclear energy in Africa : a legal framework for sustainable energy access - Barnard, Michelle (North-West University, 2014)
The promotion of sustainable development is an objective shared by African Union (AU) member states and the pursuance thereof is expressly mandated by the Constitutive Act of the African Union, 2000 and the Treaty Establishing the African Economic Community, 1992. Lack of access to modern energy sources, such as electricity and the heavy reliance on traditional biomass as primary energy source are factors contributing to the non-achievement of the promotion of sustainable development. These factors are collectively referred to as energy poverty. The African Continent as a whole has limited, and in some instances, lack access to modern energy sources while the majority of its population relies heavily on traditional biomass as primary energy source. Africa can accordingly be classified as an energy poor region–a situation which does not bode well for the promotion of sustainable development. Access to reliable, affordable, economically viable, socially acceptable and environmentally sound energy services and resources is fundamental to socio-economic development. Mitigating the impacts of energy poverty and more specifically lack of access to modern energy sources on the sustainable development of Africa depends upon ensuring increased access to modern energy sources. The above-mentioned instruments furthermore contain provisions which link regional cooperation on the formulation of coordinated regional law and policy on areas/matters of common concern with the achievement of the objective of promoting sustainable development in Africa. One of the areas of common concerns listed is that of energy. Regional cooperation must accordingly be geared towards the effective development of the continent‘s energy and natural resources; promoting the development of new and renewable energy in the framework of the policy of diversification of sources of energy; and establishing an adequate mechanism of concerted action and coordination for the collective solution of the energy development problems within the AU. The formulation of coordinated energy law and policy should take place with reference to the specific sources of energy to be regulated. In this regard, the provisions of the Abuja Treaty and other sub-regional energy access initiatives list various sources of energy as forming part of a diversified AU energy mix – one of which is nuclear energy. In this study recommendations are made as to what should be embodied in a coordinated AU regional nuclear legal framework aimed at regulating increased access to nuclear energy capable of contributing towards the promotion of sustainable development. The recommendations are based on an examination of relevant international, regional and sub-regional legal instruments and other initiatives.
Keywords: African Union; Coordinated legal framework; Energy access; Energy poverty; Nuclear energy; Regional cooperation; Sustainable development

Sanitary and phytosanitary measures in the SADC region : a South African legal perspective - Joubert, Biandri (North-West University, 2014)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health within specified territories from the risks associated with the introduction and spread of pests and diseases through trade. The World Trade Organisation (WTO) developed an agreement on the application of SPS measures. South Africa is a member of both the WTO and the Southern African Development Community (SADC). In SADC, SPS measures are provided for in the SADC Sanitary and Phytosanitary Annexure to the Protocol on Trade of 1996. International Standard Setting Bodies (ISSBs) facilitate the effective application of the main elements of the relevant SPS agreements, especially harmonization and equivalence by establishing scientifically justified standards on which members may base their SPS measures. The relevant ISSB’s in terms of SPS measures are the OIE, IPPC and Codex Alimentarius. SPS measures have the potential to become or be used as non-tariff barriers to trade (NTBs). The SADC Protocol on Trade 1996 stipulates that policies and measures are to be implemented by members to eliminate existing forms of NTBs. Additionally members may not enforce new NTBs affecting or related to intra-SADC trade. The most relevant South African legislation in the context of SPS measures and this study is as follows: Agricultural Pests Act 36 of 1983, the Agricultural Products Act 119 of 1990; the Fertilizers, Farm Feeds, Agricultural Remedies and Stock Remedies Act 36 of 1947, the Liquor Products Act 60 of 1989, Meat Safety Act 40 of 2000, Foodstuffs, Cosmetics and Disinfectants Act 54 of 1972, Medicines and Related Substances Act 101 of 1965 and National Regulator for Compulsory Specifications Act 5 of 2008. The purpose of this study is to establish to what extent the South African legal framework complies with its obligations in terms of the SADC SPS Annexure to the Protocol on Trade.
Keywords: ISSB; NTB; SADC; SPS; Sanitary and phytosanitary measures; South Africa; WTO

La problématique de l’existence du droit communautaire africain: L’option entre mimétisme et spécificité - Kazadi Mpiana, Joseph (Revue libre de Droit, 2014)
Depuis la décennie 1990, une nouvelle génération des Organisations internationales africaines (OIA) émerge sur l’échiquier africain en s’inspirant, pour l’essentiel de son articulation normative et institutionnelle, du modèle européen d’intégration, notamment dans sa dimension communautaire tout en y apportant des spécificités africaines. Dès lors, le droit communautaire pose ses racines dans certaines OIA suscitant l’intérêt sans cesse nourri de la doctrine sur cette nouvelle matière. Mais existe-t-il vraiment un droit communautaire africain dont la doctrine s’efforce de présenter les grandes lignes, du moins de manière thématique ? La présente étude constitue une contribution à la problématique posée en envisageant de cerner la nature ainsi que les caractéristiques de ce droit qui se développe, principalement, en Afrique centrale et occidentale. Since the 1990s, a new generation of African International Organizations (AIO) emerges on the African continent, inspired, for most of its normative and institutional articulation, by the European model of integration, including its Community law while by bringing African specificities. Thus Community law is rooted in some AIO and the interest by the doctrine on this new branch is still constant. But is there really an African Community law that the doctrine seeks to systematize, at least thematically? This paper is a contribution to the problem posed by considering the nature and characteristics of this law developed mainly in Central and West Africa.

Legitimation of the economic community of West African states (ECOWAS): a normative and institutional inquiry - Nwankwo, Chidebe (Brunel University, 2014)
This thesis was submitted for the degree of Doctor of Philosophy and awarded by Brunel University LondonThis study is an attempt at determining the normative legitimacy of the Economic Community of West African States (ECOWAS). At its core, it scrutinizes the current mandate of the organization following the layering of economic integration objectives with human rights protection, sustenance of democracy, and the rule of law. The study discusses the elements of legitimacy across disciplines mainly, international law, international relations and political science. Legitimacy is eventually split along two divides, the normative and descriptive/sociological aspects. The study traces the normative content (shared/common values) underlying integration in Africa, concluding that integration has been born on new ideals such as human rights, democracy and the rule of law. Expectedly, Regional Economic Communities (RECs) as building blocks of the prospective African Economic Community (AEC) under the African Union (AU) regime are mandated to play a vital role in moving the continent forward upon these values. The inquiry is extended to the institutions of ECOWAS to determine their capacity to effectively implement the new mandate of the organization and operate supranationally. In the process, key legal and institutional shortcomings are discussed, particularly in relation to national institutions. It is argued that while human rights protection enhances the normative legitimacy of ECOWAS, it must not be pursued in isolation. Economic integration and protection of citizens’ rights are co-terminus and mutually reinforcing. Hence, community institutions must reflect this link if they are to be effective. The study concludes on the note that, while ECOWAS possesses layers of legitimacy, and have carried out legitimation steps, it cannot be considered a legitimate organization if Member States continue to be non-compliant with community objectives and if key legal questions remain unaddressed. It is submitted that ECOWAS is merely undergoing legitimation, whether it can eventually be considered a legitimate organization is dependent on addressing the identified challenges
Brunel University Research Archive
Keywords: AU; Democracy; ECOWAS; Human Rights; Humanitarian Intervention; Legitimacy; Peace and Security; Regional integration

Direito comunitário material e integração sub-regional: contributo para o estudo das mutações no processo de integração económica e monetária na África Ocidental - Pereira, João Mendes (Universidade de Lisboa, 2014)
Pretende–se com esta tese intítulada “ Direito Comunitário material e Integração Sub–Regional: Contributo para o Estudo das Mutações no Processo da Integração Económica e Monetária da África Ocidental” pôr em evidência as mutações ocorridas na actual zona franco, no período colonial e pós colonial dos países africanos e as reformas das principais instituições comunitárias nela verificadas.Impõe–se uma nova abordagem da realidade contemporânea, no quadro das profundas mudanças ocorridas, a reclamar novos instrumentos de análise e de integração regional.Neste sentido, o Tratado da União Monetária Oeste Africana (UMOA) proclamou expressamente a vontade que animava os Estados–membros de prosseguirem na via da integração regional e de transformarem o conjunto das relações entre os si numa União Económica e Monetária.Com o propósito de somar à moeda única a harmonização legislativa, a abertura e a unificação dos mercados, a adopção de politicas económicas convergentes, propõe–se a União Económica e Monetária da África Ocidental (UEMOA) levar a cabo a habitual sequência da integração regional.Analisamos profundamente as políticas comunitárias, distinguindo primeiro políticas visando mais directamente a livre circulação das mercadorias, das pessoas, dos serviços e dos capitais no âmbito da UEMOA e da CEDEAO.A presente tese de doutoramento visa retratar o regime monetário regional que historicamente está ligado ao espaço colonial francês e depois se integrou progressivamente no sistema monetário internacional.Enfatizamos os principais instrumentos de política monetária regional, bem como o quadro institucional da União.Traçamos as premissas para uma teoria geral da integração dos Estados–membros da zona franco no contexto duma integração monetária e do novo multilateralismo comercial.Num ambiente cada vez mais concorrencial e difícil tornam-se prementes uma firme e necessária cooperação e integração regionais.No contexto da União Africana e da Nova Parceira para o Desenvolvimento do Continente Africano (NEPAD), evocamos as condições prévias do desenvolvimento com relação ao combate à pobreza. A nova Parceria Económica entre os países africanos e a União Europeia, consubstanciada no reforço do comércio internacional, permitindo robustecer as económicas africanas frágeis, que evidenciam falta de competitividade e de complementaridade, e uma um melhor inserção na económia regional e mundial.Nesta ordem de ideias, debruçamo-nos sobre as vantagens comparativas dos países da zona franco face às regras da Organização Mundial do Comércio (OMC).Partindo do entendimento de que o comércio internacional é necessário e que as trocas comerciais venham mesmo a ser inevitáveis, o que se propõe é uma nova discussão, inquirindo–se se o sistema multilateral de comércio pode fomentar e englobar um projecto de desenvolvimento. Intended with this designated thesis "Communitarian’ s Right material and Integration Sub - Regional: Contribute of Changes in the State Process of Economic Integration and Monetary Union of West Africa" to highlight the changes occurred in the actual franc zone during the colonial, post colonial countries African partners and major reforms of the main communitarian institutions been verified. It imposes - a new boarding of the contemporary reality, in the context of profound changes, to complain new instruments of analysis and regional integration. In this sense, the Treaty of West African Monetary Union (UMOA) expressly declared the will that animated the states members to proceeded the path of regional integration and to transform the set of relations between States in their economic and monetary union. In order to add the single currency legislative harmonization, unification and the opening market, the adoption of economic policies converge, it is proposed to Economic and Monetary Union of West Africa (UEMOA) the habitual sequence of regional integration. We deeply analysed the politics communitarian, distinguishing first politics aiming at more directly the free movement of goods, people, services and capitals in the scope of the UEMOA and the CEDEAO. This doctoral thesis aims to portray the regional monetary regime is historically linked to the French colonial space, after it was progressively integrated into the International monetary system. We set the foundations for a general theory of integration of states - members of the franc zone in a context of monetary integration and the new multilateral trade. We followed the assumptions for a general theory of integration of states - members of the franc zone in a context of monetary integration and the new commercial multilateralism. 6 In an increasingly competitive and difficult to become a strong and urgent need for cooperation and integration regional’s. In the context of the African Union and New Partnership for the Development of Africa (NEPAD) evoke the preconditions of development in relation to combat poverty. Having in account the new Economic Partnership between the countries and consubstantial in the reinforcement of the international trade for the fragile African economics, evidencing lack of competitiveness and complementarily with sight to one better insertion in the regional and world-wide economic. In this order of idea, concentrating on the comparative advantages and more favourable to the franc zone countries over the rules of the World Trade Organization (WTO). From understanding that international trade is necessary and that trade may even be inevitable, what is proposed is a new thread, asking if the multilateral trading system can promote and incorporate a development project.
Keywords: African Union; Communitarian Right; Comércio; Democracia; Democracy; Desenvolvimento; Development; Direito Comunitário; Estado; Franc zone; Globalization; Globalização; Integração regional; Pan Africanism; Panafricanismo; Regional integration; State; Trade; União africana; Zona franco

Integração na África Austral : a comunidade para o desenvolvimento da África Austral (SADC) e os condicionantes históricos e políticos da integração - Xavier, Nathaly Silva (Universidade Federal do Rio Grande do Sul, 2014)
A Comunidade para o Desenvolvimento da África Austral (SADC) é um dos principais processos de integração regional da África. A criação da Comunidade está fundada no processo de descolonização da África Austral e na mobilização dos Estados da Linha de Frente na contenção das políticas de desestabilização da África do Sul durante o período do apartheid. A concepção de regionalismo desenvolvimentista, na qual os processos de integração regionais têm objetivos mais amplos do que os meramente comerciais, vai ao encontro da realidade da África Austral. O conceito de comunidade de segurança também é útil para compreender as relações regionais que envolvem a criação e o desenvolvimento da SADC ao longo das décadas, tendo em vista a sua atuação também nas questões securitárias. O objetivo desse trabalho é analisar a evolução da SADC, desde a sua criação até os anos 2000, enfatizando os aspectos históricos e políticos desse processo. Parte-se do pressuposto de que há uma forte relação entre segurança, desenvolvimento, paz e integração e que não há como a integração econômica aprofundar-se em um contexto de instabilidade político-securitária regional. The Community for the Southern African Development Community (SADC) is one of the main regional integration processes in Africa. The creation of the Community has its origins in the process of decolonization in Southern Africa and in the Front Line States the mobilization to contain the destabilization policies by South Africa during the apartheid period. The concept of developmental regionalism, in which the processes of regional integration have broader objectives than purely commercial, folows the reality of Southern Africa. The concept of security community is also useful for understanding regional relations involving the creation and development of SADC over the decades, concerning your activity also in security issues. The aim of this study is to analyze the evolution of SADC since its creation until the 2000’s, emphasizing the historical and political aspects of this process. It adopts the assumption that there is a strong relationship between security, development, integration and peace and there is no way to deepen economic integration in a context of regional political and security instability. La Communauté de Développement de l'Afrique Australe est l'un des principaux processus d'intégration régionale en Afrique . La création de la Communauté est fondée dans le processus de décolonisation en Afrique australe et dans la mobilisation de les État du Linge de Front pour contenir les politiques de déstabilisation de l'Afrique du Sud au cours de la période de l'apartheid. Le concept de régionalisme développementiste, dans lequel les processus d'intégration régionale ont des objectifs plus larges que purement commerciale, répond à la réalité de l'Afrique Australe . Le concept de communauté de sécurité est également utile pour comprendre les relations régionales sur la création et le développement de la SADC au cours des décennies , en vue de ses performances aussi dans les questions sécuritaire . L’objectif de cette étude est d'analyser l'évolution de la SADC depuis sa création jusqu'aux années 2000 , mettant l'accent sur les aspects historiques et politiques de ce processus . Séjours à l'hypothèse selon laquelle il existe une relation forte entre la sécurité, le développement, l'intégration et la paix et il n'ya aucun moyen d'approfondir l'intégration économique dans un contexte d’instabilité politique et securitaire régionale.
URI: https://lume.ufrgs.br/handle/10183/106413
Keywords: Afrique Australe; Comunidade para o Desenvolvimento da África Austral; História; Integration; Integração regional; Política; Relações internacionais; SADC; Southern Africa; África

Les conventions ACP-EU et les sanctions économiques de l'Union européenne contre les Etats ACP : le cas du Togo - Nikabou, Lantame Jean (Université de Strasbourg, 2013)
L’Accord de Cotonou, signé en juin 2000 entre l’Union européenne et les États d’Afrique, des Caraïbes et du Pacifique (ACP), se caractérise par un respect des droits de l’homme, des normes démocratiques et de l’État de droit d’une part, et la quête d’une conformité des normes aux principes de l’Organisation mondiale du commerce (OMC), d’autre part. En effet, la politique de développement mise en place par l’Europe au profit des États ACP a vu le jour avec le Traité de Rome et la création du Fonds européen de développement au profit des ces pays. Pendant longtemps, le partenariat, essentiellement économique, a octroyé d’énormes avantages aux pays ACP en vue d’assurer leur développement. Depuis bientôt deux décennies que les normes politiques ont été insérées dans ce partenariat, force est de constater que quelques pays, dont le Togo, demeurent toujours réticents quant à l’instauration de réelles réformes démocratiques en vue d’assurer une véritable alternance politique. En dépit des sanctions infligées çà et là par l’Union européenne, ces pays trouvent un appui auprès de la Chine qui mène, avec les pays d’Afrique, un partenariat en toute exclusion de la société civile.
Keywords: ACP; Accord ACP-UE de Cotonou; Accord de Cotonou; Afrique; Chine; Cotonou agreement; Economic partnership between EU and ACP; Partenariat; Partenariat économique; Partnership between China and Africa; Pays ACP; Pays de l'Union européenne; Relations extérieures; Relations économiques internationales; Togo; Traités; UE

La modernisation du cadre budgétaire des pays de l'UEMOA - Zoure, Daouda (Université Paris 1, 2013)
La recherche porte sur la modernisation du cadre budgétaire des pays de l’UEMOA. Il s’agit d’évaluer la portée des réformes budgétaires développées dans chacun de ces pays. On s’est essayé à mettre en évidence la nécessaire mise en place d’une standardisation de certains dispositifs ainsi que d’une adaptation des procédures ayant fait leurs preuves non seulement dans certains États de la zone mais également dans d’autres pays confrontés à des problèmes similaires. On s’est appuyé sur les comparaisons internationales existantes et l’on a évalué la pertinence des solutions proposées notamment par les bailleurs de fonds. This research relates to the transformation of budgetary framework of West African Economic and Monetary Union (WAEMU) countries. It is a question of evaluating the extent of the budgetary reforms undertaken in each respective country. The research has tried to highlight the necessary installation of certain standard devices as well as adapting proven reliable procedures not just for certain zones of specific countries but also other countries confronted with similar issues. This exercise was based on existing international comparisons and the evaluation examined the relevance of the solutions suggested in particular by the financing institutions.
Keywords: Afrique occidentale; Budget framework; Budgetary framework; Contrôle judictionnel; Finance publique; Loi des finances; Processus budgétaire; Public finance; UEMOA; Union économique et monétaire Ouest africaine – 1990-2020; WAEMU

La régionalisation de la paix et de la sécurité internationales post-guerre froide dans le cadre de la CEDEAO : la construction d’un ordre sécuritaire régional, entre autonomie et interdépendance - Ali Gazibo, Kadidiatou (Université Paris 1, 2013)
Ce travail a pour objectif d'analyser la nature et l'ampleur des tentatives d'institutionnalisation d'un régime régional de sécurité dans le cadre de la communauté des États de l'Afrique de l'Ouest (CEDEAO). Elle part du constat que la fin de la guerre froide et la globalisation ont provoqué un changement dans la nature de la conflictualité et changé la donne pour l'ONU et les grandes puissances dans le domaine du maintien de la paix. Face à la multiplication des conflits internes et régionaux, on observe l'émergence de nouveaux acteurs de sécurité qui leur contestent le monopole des opérations de maintien de la paix et de la sécurité. En Afrique de l'Ouest, sous l'action de la CEDEAO, on assiste à partir de 1990 à la "sécurisation" progressive d'enjeux non militaires (politique, social, économique et environnemental) avec comme objectif, la mise en place d'une communauté de sécurité. En nous appuyant sur les cas empiriques d'interventions de la CEDEAO au Libéria, en Sierra Léone et en Guinée-Bissau entre autres, nous analysons pourquoi et comment la régionalisation des opérations de paix a produit des transformations, notamment une politique d'intégration et une reformulation des enjeux sécuritaires dans la région. Cela nous conduit à appréhender la CEDEAO comme région et comme acteur de sécurité dans le champ des relations internationales. En recourant à différentes approches (fonctionnalistes, constructivistes, réalistes), nous explorons d'une part le processus régional de sécurisation au plan empirique et institutionnel, et d'autre part les difficultés, les apprentissages et les jeux d'acteurs dans le champ des opérations de paix. Dans la mesure où ce dernier est ouvert et investi par différents acteurs, se pose également la question de la coordination de leurs interventions.
Keywords: Afrique occidentale; CEDEAO; Communauté de sécurité; Communauté économique des États de l'Afrique de l'Ouest; Fonctionnalisme (sciences sociales); Institutionalizing; Institutionnalisation; Maintien de la paix; Peacekeeping; Regionalization; Régionalisation; Security community; Sécurité internationale; Sécurité économique

Some reflections on the prospects for the harmonization of international business laws in Africa : OHADA and beyond - Fombad, Charles Manga (Africa Today, 2013)
The evidence of developments in the harmonization of international business laws shows that Africa is lagging seriously behind. There are still some skeptical voices about the need for and the value of harmonization of international business laws, but such voices are now in a minority. The aim of this paper is to assess the prospects for harmonizing international business laws in Africa. The main contention is that the debate today in Africa is not whether or not there should be harmonization of international business laws, but how this should be done. The paper reviews the imperatives for harmonization and the options that exist and then focuses on the present approach to harmonizing business laws in Africa under the auspices of the Organization for the Harmonization of Business Laws in Africa, better known under its French acronym, OHADA. Based on the critical review of the weaknesses and strengths of the OHADA regulatory framework, the paper suggests ways in which the agenda to develop a harmonized and modern set of business laws in Africa can be achieved.

Normes OHADA et constitutions des Etats membres : conflit en léthargie ou simple temps mort ? - Kagisye, Emmanuel (HAL Open science, 2013)
L’articulation du droit uniforme et des droits nationaux constitue l’une des questions les plus importantes pour le développement d’un système juridique cohérent, particulièrement dans sa composante normative. A cet égard, la supranationalité des normes ohada consacrée par l’article 10 du Traité OHADA et l’interprétation dont en a fait la Cour commune de justice et d’arbitrage constituent une solution de principe . Malheureusement, force est de constater que la supranationalité de normes ohada ne permet pas de les résoudre tous les conflits entre les normes ohada et les normes internes des Etats membres. C’est le cas de normes constitutionnelles des Etats membres qui peuvent entrer en conflit avec les normes primaires et les actes uniformes de l’OHADA.
Keywords: Conflits; Constitutions; Droit OHADA

Common Problems Affecting Supranational Attempts in Africa: An Analytical Overview - Fagbayibo, Babatunde Olaitan (Potchefstroom Electronic Law Journal, 2013)
Ever since the colonial era, attempts have been made throughout the various regions of Africa at building supranational units chiefly for administrative and legal convenience. Examples of such attempts include the Federation of Rhodesia and Nyasaland, the East African High Commission and the federations in former French West and Equatorial Africa, all of which were attempts at forging a supranational nation state. These experiments laid the foundation for further supranational initiatives in post-colonial Africa. In this respect, every region in Africa has either experimented with or is currently experimenting with the idea of supranational regional organisations. This article aims at investigating selected attempts at supranationalism on the continent, the successes and failures of such experiments, and the lessons to be learnt from them. As Africa embarks on the journey of solidifying its unity through the establishment of leviathan continental institutions, efforts should be geared towards building on the experiences of past and present experiments at the sub-regional level. Such experiments offer instructive lessons as they are rooted in similar historical and social contexts.
Keywords: African integration; Central African Economic and Monetary Community; East African Community; Economic Community of West African States; OHADA; Southern Africa Customs Union; Supranationalism; West African Economic and Monetary Union

Legal Innovation for Development: The OHADA Experience - Frilet, Marc (Legal Innovation and Empowerment for Development, 2013)
The World Bank legal review gathers this input from around the world and compiles it into a useful resource for all development practitioners and scholars. The subtitle of this volume, legal innovation and empowerment for development, highlights how the law can respond to the chal-lenges posed to development objectives in a world slowly emerging from an economic crisis. The focus on innovation is a call for new, imaginative strategies and ways of thinking about what the law can do in the development realm. The focus on empowerment is a deliberate attempt to place the law into the hands of the poor; to give them another tool with which to resist poverty. This volume shows some of the ways that the law can make an innovative and empowering difference in development scenarios. Development problems are complex and varied, and the theme of innovation and empowerment naturally has a broad scope. Consequently, this volume reaches far and wide. It considers the nature, promise, and limitations of legal innovation and legal empowerment. It looks at concrete examples in places such as Africa, the Asia-Pacific region, and Latin America. It considers developments in issues with universal application, such as the rights of the disabled and the effectiveness of asset recovery measures. The theme of legal innovation and empowerment for development complements substantive and institutional sensibilities in current development policy. Substantively, development policy discourse seems to have moved away from tacking hard toward statist policy or neoliberal policy. Although this brief introduction cannot do justice to the richness and complexity of these contributions, it does consider each focal point in turn.

The development of a commercial law structure in the SADC with specific reference to OHADA - Leno, Ngaundje Doris (University of Pretoria, 2013)
In a region where there is diversity of laws, the author maintains that law reform is a catalyst for investment and development. This thesis aims at demonstrating that OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC. This is following OHADA’s success in developing uniform commercial rules that are directly applicable in the contracting states. To achieve this, the thesis uses a “structured focused comparison” methodology that allows for two separate, but structurally linked accounts of the structures of both organisations. In exploring the structures of both organisations, the thesis endeavours to: determine whether there is the need for the development of a commercial law structure in the SADC; whether such a structure can be developed within the current SADC structure and whether OHADA can serve as a possible model for the SADC. The findings show that no part of the African continent has witnessed regional legal reform on the scale of that initiated by OHADA. It equally reveals the absence of a uniform commercial law structure in the SADC and the lack of supranational structures to adopt full panoply of business laws and to preserve the uniformity of laws in the member states. The findings from this thesis provide evidence that there is the need forthe development of a commercial law structure in the SADC and improvement of the current SADC structure. There is no doubt that thi swould do away with legal uncertainty in cross-border commercial transactions among SADC states.
Accepted: 2016-05-20T09:04:41Z URI: https://repository.up.ac.za/handle/2263/52731

The Quest for a Supranational Entity in West Africa: Can the Economic Community of West African States attain the Status? - Lokulo-Sodipe, Jadesola O.; Osuntogun, Abiodun J. (Potchefstroom Electronic Law Journal, 2013)
To reflect the growing trends in the international scene and in furtherance of the objective of its Revised 1993 Treaty, the Economic Community of West African States (ECOWAS) summit in December 2006 revolutionised the structure of ECOWAS by re-designating the Executive Secretariat into a quasi-independent commission headed by a President with a Vice President and seven commissioners. The rationale behind the revision was to make ECOWAS a supranational entity. This article considers whether or not a supranational system is essential for the attainment of ECOWAS' objectives. It asks if the conditions for an effective supranational system are in place in the West African sub-region which could provide a solid foundation for its success and why the quest for a supranational system has not yielded any fruitful result in West Africa. It argues that a retreat from the quest for supranationalism and a return to an inter-governmental system would be a retreat rather than the way forward, and expresses the need for the course of action to be sustained courageously till the impact of integration begins to emerge, and the disguised, patriotic impulse of states to protect their national sovereignty gives way to the full manifestation of ECOWAS as a supranational entity.
Number: 3
Keywords: Community Court of Justice; ECOWAS Commission; Intergovermental organisation; Regional integration; Supranational entity

L’expression de la souveraineté des Etats membres de l’OHADA (l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires): une solution-problème a l’intégration juridique - Moneboulou Minkada, Hervé Magloire (Juridical Tribune - Review of Comparative and International Law, 2013)
The title of this contribution concerns the sovereignty of OHADA’s States as a solution or a problem of juridical integration. In our analysis, we consider that the States of the OHADA’s area are the main actors of this integration. In fact, the States express their sovereignty towards organs and tools of OHADA. In one hand, the way States express their sovereignty enable to have the same law amongst OHADA’s States. In another hand, by allowing any State to have his own criminal law (as far as sanctions are concerned) the aim of integration (unification) has been jeopardized. The solution of this problem is to have the same penal approach.
Keywords: Business law; Criminal law; Juridical integration; OHADA; Sovereignty

The regional integration of African trade mark laws: challenges and possibilities - Mupangavanhu, Yeukai (University of the Western Cape, 2013)
Keywords: African Union; Differences; Harmonisation; Intellectual property; Regional integration; Similarities; TRIPs; Trade Mark Directive; Trade marks; Unification

Challenges to political and economic intergration in Africa : A socio-Legal perspective - Mwanawina, Ilyayambwa (North-West University, 2013)
This study is concerned with integration efforts on the African continent. This study sets out to investigate the politico-legal and economic impediments to regional and continental integration efforts in Africa. The documents, processes, and organs of the African Union, as the main continental organisation, are the focal point of this study. In order to achieve this, the study primarily adopted a qualitative approach since the literature involved in this work could not be reduced to a quantitative concept. The study ensured that the premises and the conclusions in this work conform to the principles of reliability and validity and in addition the elimination of bias in this was curtailed by validation and triangulation. This was achieved by the fact that the arguments in this work were not only based on qualitative arguments but, where possible, quantitative data was brought in to validate/ triangulate the qualitative arguments. Evidently, the study would have been incomplete if it did not discuss and evaluate the many regional economic communities that have been established to further the objectives of the Treaty establishing the African Economic Community. One of the major premises that this study discovers is that there is a direct and demonstrable relationship between democracy and economic progress; genuine and sustainable development has to be fostered primarily by securing peace and stability on the African continent. Some of the other key findings of the study include that; a) the ultimate goal of the African Union is full political and economic integration leading to the United States of Africa; b) overlapping memberships to a custom unions are highly detrimental to the state since it has to subscribe resources and political will to two or more different arrangements. c) overlapping memberships cause confusion, inertia and most importantly legal uncertainty thereby stifling trade liberalisation efforts; d) many African states still guard their sovereignty closely and that many perceive that yielding their sovereignty to a continental body is tantamount to losing their independence; e) the African Union infrastructure still lacks supra-national and national institutions that are capable of implementing its values; f) the African Union infrastructure does not contain an institutionalised mechanism for the promotion and management of Union affairs at national level; g) the NEPAD initiatives, the APRM process and the functions of the Peace and Security Council play a positive role in African politico-legal and economic development. It has however been shown that these mechanisms are more reactive than preventative and as such intervene too late in the internal affairs of member states; h) armed conflicts cause a reduction in the per-capita Gross Domestic Product growth rate of a nation experiencing a civil war/ conflicts. i) the African Union has regressed from the original timelines of the African Economic Community. The highest regression being Phase 2 which involves the most critical element of strengthening of African regional integration arrangements and the harmonisation of policies concerned. A thirteen (13) year postponement is noted in this regard. j) Africa's poor intra-trade performance is also attributed to the limited progress among African countries in fostering structural transformation. This structural transformation relates to the building of roads, bridges, railway lines and power grids; In order for the African continent to re-position itself in an attempt to harness the benefits of regional integration, some of the recommendations that the study makes are that; a) the African Union grant supra-national status to institutions of the Union for the equitable and speedy attainment of integration; b) the Union and member states should as soon as possible create mechanisms with decision making powers to manage Union affairs at regional and national level; c) the operationalization of the Pan African Parliament should be pursued with the utmost determination to bring the Parliament to full functionality as a Continental legislative body; d) the operationalization of the African Court of Justice and Human Rights be completed as soon as possible in order to allow the body to function as a fully-fledged continental judiciary. This will ensure that the development of integration jurisprudence from an international law perspective is not delayed. The Court will also pursue the enforcement of Human rights norms and practices; e) the Union should further lead the continent in the following sectors with clear and predictable deliverables; i) the establishment and upgrading of regional land, air, and other means of transportation and communication; ii) the creation of a cross-border power and energy generation and distribution network; iii) the establishment, advancement, and diversification of regional financial and commodity markets; iv) the establishment of a regional higher education system by facilitating wider access through specialization in regional integration; The study further acknowledges that these recommendations are not conclusive since the study of regional integration is still at its infancy and many other ideas on how to strengthen African regional integration still await discovery.

La Cour de justice face aux règlements de coopération judiciaire en matière civile et commerciale : quelques interrogations, dix ans après… - Nourissat, Cyril (Droit international privé : Travaux du Comité français de droit international privé, 2013)

Climate change and Africa : the normative framework of the African Union - Pallangyo, Daniel Mirisho (North-West University, 2013)
There is enough evidence on how climate change consequences will adversely affect Africa despite the fact that it is the continent that has least contributed to the problem. The international climate change regime recognises Africa's vulnerability to climate change and provides for special treatment under the United Nations Framework Convention on Climate Change (the UNFCCC). Thus, the international climate change regime presents an opportunity for African countries to adapt and mitigate the consequences of climate change through the UNFCCC mechanism. However, the international climate change legal regime has not been able to adequately assist African countries to address the consequences of climate change under the vulnerability principle. Although the current international climate change regime requires developed countries to reduce their greenhouse gas (GHG) emissions, Africa needs to take steps itself to address the problem, because it is most vulnerable to the consequences of climate change. The African Union (AU) could play a great role in ensuring that the international climate change regime addresses the consequences of climate change in the region. This could be done through fostering strong African common positions during international climate change negotiations. A strong common position could strengthen African bargaining power and might result in more funding, capacity building and technology development and transfer for adaptation and mitigation programmes under the UNFCCC-Kyoto Conference of Parties. However, reaching a strong common position requires the cooperation of the AU member states. In this context, African regional integration is an opportunity for the AU to foster such cooperation among member states. The Treaty Establishing the African Economic Community (the Abuja Treaty), the Constitutive Act of the AU and the Protocol on the Relations between the AU and Regional Economic Communities (RECs) prioritise regional economic integration and call for states' cooperation, but the call has not yet been heeded. To realise deep and viable African integration, there must be a well-structured institutional and legal framework that defines the relationship between the AU, the AEC and the RECs. African regional integration is also seen as an avenue whereby the AU can create its own regional climate-change regime. In this regard, the AU's and RECs' normative framework on climate change is examined in order to assess whether it adequately integrates climate change issues. This study finds that although Africa is most vulnerable to the consequences of climate change, the AU's and RECs' normative framework on climate change is weak and inadequate to address the problem. The Framework should integrate climate change issues in order to achieve sustainable development. The AU should also ensure that member states ratify the relevant treaties and protocols (the Maputo Nature Convention and the Protocol establishing the African Court of Justice and Human Rights) that have not yet been ratified in order that they may become operational. The Maputo Nature Convention puts sustainable development in the forefront of attention as a reaction to the potentially conflicting environmental and developmental challenges facing the continent (such as climate change), but it is not yet in force. This work finds that human rights law can strengthen the AU's role in addressing climate change through its normative framework. The human rights approach to climate change under the African Charter on Human and Peoples' Rights (the Banjul Charter) is a viable avenue because human rights law forms the basis for states' responsibility based on human rights obligations and principles. The extraterritorial application of the Banjul Charter presents an avenue for AU institutions such as the Human Rights Commission and the African Human Rights Court to curb the effects of climate change through a human rights lens. The future of the AU is presented within the context of a set of recommendations that identify strong African regional integration as an avenue through which the AU can foster the cooperation of member states to address the consequences of climate change in the AU's and RECs' normative frameworks. General recommendations are made on the need for the international climate change regime to pay more attention to issues of funding, capacity building and technology development and transfer on the basis of the vulnerability principle and in relation to the principles of equity and common but differentiated responsibilities and respective capabilities. Also, the AU needs to strengthen its legal and institutional structures to ensure deep African integration that is capable of addressing common challenges such as the consequences of climate change.
Keywords: African Charter on Human and Peoples Rights; African Economic Community (AEC); Climate Change; EAC Treaty; ECOWAS Treaty; Human rights; International climate change regime; Normative framework; Regional integration; SADC Treaty; State cooperation; The Constitutive Act of AU

The harmonisation of rules on the recognition and enforcement of foreign judgments in the Southern African Customs Union - Rossouw, Mandi (University of the Western Cape, 2013)
The thesis considers the approaches followed by the European Union with the Brussels Regime, the federal system of the United States of America under the ‘full faith and credit clause’; the inter-state recognition scheme under the Australia and New Zealand Trans- Tasman judicial system; as well as the convention-approach of the Latin American States. It finds that the most suitable approach for the SACU is the negotiation and adoption by all SACU Member States of a multilateral convention on the recognition and enforcement of foreign judgments, comparable to the 1971 Convention of the Hague Conference on Private International Law; the EU Brussels I Regulation and the Latin-American Montevideo Convention, as complemented by the La Paz Convention. It is imperative that a proposed convention should not merely duplicate previous efforts, but should be drafted in the light of the legal, political and socio-economic characteristics of the SACU Member States. The current legislative provisions in force in SACU Member States are compared and analysed, and the comparison and analysis form the basis of a proposal for a future instrument on recognition and enforcement of foreign judgments for the region. A recommended draft text for a proposed Convention on the Recognition and Enforcement of Foreign Judgments for the SACU is included. This draft text could form the basis for future negotiations by SACU Member States
Keywords: Civil and commercial transactions; Cross-border litigation; Foreign judgments; International Trade; Recognition and enforcement; Regional integration; Trade facilitation

Les normes internationales qui prescrivent l'existence ou l'inexistence d'une règle interne - Meunier, Hugo (Université Paris 2, 2012)
Cette thèse propose une théorie générale des normes internationales qui prescrivent l'existence ou l'inexistence d'une règle interne. Cette entreprise, qui est une première dans la doctrine de droit international, présente, à titre principal, deux intérêts. Premièrement, elle démontre que le concept de normes internationales prescrivant l'existence ou l'inexistence d'une règle interne permet de décrire une partie fondamentale du droit international positif, habituellement présentée au moyen d'autres concepts très connus, en particulier le principe de primauté ou de supériorité du droit international et le conflit ou la contrariété entre droit international et droit interne. Deuxièmement, en s'appuyant sur 250 instruments et 750 jugements, extraits principalement du droit des affaires, du droit de l'environnement, du droit des droits de l'homme, du droit pénal, du droit du travail et du droit de l'Union européenne, cette thèse prouve qu'il existe un régime commun à l'ensemble des normes internationales qui prescrivent l'existence ou l'inexistence d'une règle interne. This thesis establishes a general theory of international norms which prescribe the validity or the invalidity of an internal rule. This research, the first of its sort to be undertaken in international legal doctrine, follows two principal lines of enquiry. Firstly, it demonstrates that the concept of international norms which prescribe the validity or the invalidity of an internal rule provide a basis on which to describe a fundamental part of positive international law, usually presented by mean of well-know others concepts as the principle of primacy or superiority of the international law, and the conflict or contradiction between international law and internal law. Secondly, this thesis draws on more than 250 legal instruments and 750 judgments, relating principally to business law, environmental law, human-rights law, criminal law, labour law and European Union law, to illustrate the existence of a coherent regime governing all international norms prescribing the validity or the invalidity of an internal rule.
https://assasrecherche.u-paris2.fr/ori-oai-search/notice/view/2012PA020089
Keywords: Directives; Droit international et droit interne; Harmonisation; Harmonization; International law and internal law; International responsibility; Kelsen; Lois uniformes; Législation européenne; Primacy; Primauté; Responsabilité internationale; Standardization; Triepel; Unification internationale; Uniform law; Uniformisation

La fonction de représentation extérieure commune des organisations d’intégration ouest africaines dans les négociations commerciales - Yougbaré, Robert (Université de Ouaga 2, 2012)
Le régionalisme est un phénomène qui a pris de l'ampleur dans le monde, en général, et sur le continent africain en particulier. L'Afrique découvre le phénomène en même temps qu'elle expérimente l'étatisme, la forme d'organisation sociopolitique sous laquelle le continent s'est émancipé de ses anciens colonisateurs. Des indépendances à nos jours, en dépit de sa constance, le phénomène a connu une redynamisation, qui l'a conduit à une certaine unité théorique. Face à la constance du phénomène, l'on est en droit de s'interroger sur sa logique (MATTI, 1999), sur sa raison d'être. En partant d'une approche sociologique des relations internationales, aucun phénomène, aucune organisation spécifique n'est le fruit d'un hasard : chaque institution répond à un besoin donné. C'est de cette hypothèse qu'est parti le présent projet de recherche, qui s'est assigné pour objectif d'expliquer la rationalité du régionalisme, en général, et de sa dimension extérieure, c'est-à-dire, l'unité de front face au monde qu'elle constitue, en particulier. Le besoin d'un front d'action collective dans les relations internationales est évident pour les Etats africains, en proie à une marginalisation croissante dans les relations internationales. L'Etat africain manque, à lui seul, des facteurs, notamment le facteur structurel, qui pourraient inverser la tendance. Il lui faut par conséquent, d'autres approches. Le régionalisme est l'une de celles-là. L'étude s'est focalisée sur le sous-continent ouest africain, pour les besoins de vérification empirique. Elle s'est également inscrite dans le cadre des relations commerciales internationales pour y analyser le potentiel d'action internationale des organisations d'intégration africaines. Dans ce cadre, au-delà de l'explication de la ratio legis de la fonction de représentation extérieure commune -la fonction qui consiste pour une organisation à unifier et / ou coordonner l'action extérieure de ses membres, l'étude a porté sur l'existence théorique des conditions juridiques d'exercice de la fonction par deux des principales organisations d'intégration de la sous-région que sont la Communauté Economique des Etats de l'Afrique de l'Ouest (CEDEAO) et l'Union Economique et Monétaire Ouest africaine (UEMOA). Il s'est révélé qu'en dépit de quelques incertitudes résiduelles que la pratique peut aisément lever, ces organisations s'inscrivent bien dans cette logique de servir d'interface à leurs membres pour une action collective efficace dans les relations commerciales internationales. Bien au-delà de l'investigation théorique, l'étude a scruté le terrain empirique, pour se rendre compte de l'exercice éventuel de la fonction dans la pratique des organisations ouest africaines. Elle a examiné les conditions de leur présence dans le système juridique commercial multilatéral (le système de l'OMC) et leur implication dans un dossier qui semblait constituer une porte d'entrée dans l'arène de la diplomatie commerciale multilatérale, en l'occurrence, le dossier du coton africain à l'OMC. Leur implication y a été, malheureusement, en deçà de leur possibilité d'action. Toujours est-il que, d'un point de vue empirique, l'étude a examiné la participation des deux organisations dans la négociation de l'Accord de partenariat économique (APE) Afrique de l'Ouest - Union européenne. Dans ce dossier, les organisations ouest africaines ont fait preuve d'un certain leadership, affichant ainsi leur détermination à assumer cette fonction de représentant de la région. Certes, les résultats sont encore incertains, mais un certain satisfecit se dégage dans le camp ouest africain, pour avoir résisté face à l'avalanche des négociateurs européens. Le seul point critique demeure dorénavant l'aménagement de la participation des Etats dans le mécanisme de représentation commune, de façon à ce que chacun y voit individuellement un instrument de sa politique extérieure, pour une durabilité du dispositif. Un affinement dans ce sens renforcera et rendra réelle, la fonction de représentation extérieure commune dans les mains des organisations ouest africaines. Regionalism is a growing phenomenon in the world in general, and particularly on the African continent. Africa experimented at the same time regionalism and the modern state. From independence to the present days, despite its constancy, the phenomenon has been reinvigorated, leading to a degree of theoretical unity. Faced with the constancy of the phenomenon, we are entitled to question its logic (MATTI, 1999), its raison d'être. From a sociological approach to international relations, no phenomenon or specific organisation arises by chance: each institution responds to a given social need. This is the starting point for the present research project, which has set itself the objective of explaining the rationality of regionalism in general, and of its external dimension, that to say, the blocs it constitutes regarding the rest of the world, in particular. The need for a collective action in international relations is obvious for African states, which are increasingly marginalised in international relations. The African state, left alone, lacks the factors, particularly the structural factor, that could reverse the trend. It therefore needs other approaches. Regionalism appears to be one of them. The study focused on the West African sub-region, for the purposes of empirical verification. It also looked at international trade relations in order to analyse the potential for international action of African integration organisations. In this context, in addition to explaining the ratio legis of the function of common external representation - the function that consists of an organisation unifying and/or coordinating the external action of its members - the study focused on the positivity of legal conditions for the exercise of this function by two of the main integration organisations in the sub-region, namely the Economic Community of West African States (ECOWAS) and the West African Economic and Monetary Union (WAEMU) It turned out that, despite a few residual uncertainties that can easily be resolved in practice, these organisations are very much in line with this logic of serving as an interface for their members to ensure effective collective action in international trade relations. In addition to theoretical research, the study also looked at empirical evidence of how West African organisations perform this function in practice. It examined the conditions of their presence in the multilateral trade legal system (the WTO system) and their involvement in an issue that seemed to constitute a gateway into the arena of multilateral trade diplomacy, in this case the African cotton issue at the WTO. Unfortunately, their involvement fell short of their potential. Still from an empirical point of view, the study examined the participation of the two organisations in the negotiation of the West Africa-European Union Economic Partnership Agreement (EPA). The West African organisations have shown a degree of leadership in these negotiations, demonstrating their determination to represent the region. Admittedly, the results are still uncertain, but there is a certain satisfaction in the West African camp for having withstood the avalanche of European negotiators. The only critical point from now on is the way in which the States participate in the common representation mechanism, so that each one sees it individually as an instrument of its foreign policy, to ensure the sustainability of the mechanism. Refining the mechanism in this way will strengthen and make real the function of common external representation in the hands of West African organisations.
Keywords: Afrique de l'Ouest; CEDEAO; Common trade policy; ECOWAS; External common representation; Intégration régionale; Négociations commerciales; Politiques commerciales communes; Regional integration; Représentation extérieure commune; Trade negociations; UEMOA; WAEMU; West Africa

A Cooperação sul-sul como instrumento para o desenvolvimento: perspectivas para a República da Guiné-Bissau - Silva, Julinho Braz da (Universidade Federal de Santa Catarina, 2012)
O presente trabalho de pesquisa tem por objetivo analisar a origem e os fundamentos da Cooperação Internacional para o Desenvolvimento (CID), com ênfase na Cooperação Sul-Sul (CSS), no sentido de que esta possa atuar como instrumento potencializador do desenvolvimento nacional da República da Guiné-Bissau. Para tanto, o trabalho se estrutura em três capítulos onde se analisa interdisciplinarmente os fundamentos da CID e da CSS. Neste sentido, igualmente analisa o funcionamento da CID na República da Guiné-Bissau e indica uma proposta para o desenvolvimento da República da Guiné-Bissau a partir do Documento Estratégico Nacional para a Redução da Pobreza, do fortalecimento das instituições, das capacidades, da participação do setor privado e das oportunidades de uma parceria estratégica com a República Federativa do Brasil.
Keywords: Agências Governamentais; Cooperação Internacional; Cooperação Sul-Sul; Desenvolvimento; Relações Internacionais

The legal implications of harmonising labour laws in the Southern African Development Community (SADC) region - Okharedia, Akhabue Anthony (University of South Africa, 2012)
The purpose of this research is to explore the need for, and the legal implications of, harmonising labour laws in the Southern African Development Community (SADC). Chapter One highlights a number of factors that call for the harmonisation of labour laws in the SADC region and discusses some of the reasons why labour laws are not well developed in the region. The influence of globalisation on labour standards in southern Africa and the influence of regionalism on the harmonisation of labour laws are discussed at length. The inference that could be drawn from this discussion is that for a regionalisation process in southern Africa to be successful, there is an urgent need to harmonise the region’s labour law system. This thesis confirms that Southern Africa has many lessons to learn from the regional harmonisation of labour law in the European Economic Community and the current European Union. The implementation of international labour standards in southern Africa is investigated. The main areas examined include (1) freedom of association, (2) collective bargaining, (3) forced labour and (4) discrimination. The findings of this investigation show that there is no uniformity in the implementation of International Labour Organisation (ILO) standards in the SADC region and, therefore, it is recommended labour law should be harmonised in terms of ILO standards. In respect of the benefits to be derived from the harmonisation process, an empirical investigation was conducted in the SADC region and the following is recommended: the harmonisation of labour law in the SADC region will help with the implementation of ILO standards, protection of workers against the economic power of employers in the workplace and maintaining similar benefits for migrants in the region.
Keywords: Child labor; Collective bargaining; Compulsory labour; Discrimination in employment; Discrimination in the work environment; Droit du travail; Forced labour; Freedom of association; Harmonisation; International Labour Organization; International Labour Standards; Labour law; SADC

Political Economy of the Harmonisation of Business Law in Africa - Ntongho, Rachael (Journal of Politics and Law, 2012)
This paper examines the current dynamics of regulatory reforms in Africa and its implication on the continent. It analyses the highly political struggle for regulatory dominance of business law in Africa and how this interacts with the preferences and power of select international actors. It illustrates that the struggle between Francophone and Anglo-Saxon sections of society for OHADA to reflect their ideological stance is having a negative effect on the harmonisation process.

Regionalism : lessons the SADC may learn from OHADA - Leno, Ngaundje Doris (THRHR, 2012)
Meeste Afrikastate is klein en het nie die vermoë om effektief aan prosesse van die Wêreldhandelsorganisasie deel te neem nie. Hierdie onvermoë, saam met ander faktore, is die hoofrede vir die voortgesette marginalisering van die kontinent in die globale ekonomie en handel. Ten einde effektief aan genoemde prosesse deel te neem en in die voordele van die geglobaliseerde wêreld te deel, moet Afrikastate integreer. Regionalisme of integrasie is nie ’n doel op sigself nie maar is nodig vir die ekonomiese groei van Afrikastate. Dit skep groter markte vir handel en belegging en is ’n aansporing tot groter effektiwiteit, produktiwiteit en mededingendheid. In die lig hiervan stel die artikel drie kernargumente. Die eerste is dat regionalisme voordele bied wat Afrikastate kan ontgin ten einde marginalisering op globale vlak te oorkom. Die tweede argument is dat, terwyl die Suider-Afrikaanse Ontwikkelingsgemeenskap (SAOG) poog om besigheidsreg te harmoniseer, die Organisation for the Harmonisation of Business Law in Africa (OHADA) (Organisation pour l’Harmonisation en Afrique du Droit des Affaires) as voorbeeld kan dien aangesien dit reeds die grondslag gelê het vir die harmonisering van besigheidsreg in Afrika. Die derde argument is dat die SAOG-tribunaal verbeter moet word ten einde ’n meer regionale regsraamwerk binne die SAOG daar te stel. In hierdie verband belig die artikel sommige voordele van regionalisme in Afrika, die lesse wat die SAOG by OHADA kan leer, die voordele van ’n geharmoniseerde besigheidsreg teen die agtergrond van die OHADA-ondervinding en die moontlike wyses waarop die SAOGtribunaal verbeter kan word.

Le mythe de la souveraineté en droit international : la souveraineté des Etats à l'épreuve des mutations de l'ordre juridique international. - Bal, Lider (Université de Strasbourg, 2012)
La notion de souveraineté est souvent analysée, interprétée et critiquée sous un angle purement individualiste, comme appartenant à l'État. Toutefois, en raison de la pluralité des États qui caractérise le droit international, la souveraineté est une notion nécessairement pluraliste. L'analyse de la structure normative et institutionnelle de l'ordre juridique international montre effectivement que la souveraineté appartient à l'ensemble des États et signifie et assure leur statut privilégié dans cet ordre juridique. Dès lors, la souveraineté devient une qualité pour justifier les privilèges et les exclusivités des États par rapport aux autres entités de la scène internationale: tout dérive des États et tout doit nécessairement et obligatoirement passer par les États. Cependant, il existe un certain nombre de phénomènes qui affectent cette configuration état-centrique de l'ordre juridique international. Il s'agit notamment des phénomènes dits de la mondialisation qui font fi des divisions spatiales fondées sur l'organisation politique des États. Dans ce processus de mondialisation qui rend floues et in effectives les frontières étatiques, le rôle des États se trouve de plus en plus affaibli et remis en question. L'émergence de nouveaux acteurs représentatifs et des normativités alternatives est la manifestationde cette évolution qui va dans le sens d'un dépassement de la conception état-centrique du droit international et, par conséquent, d'une remise en question de la souveraineté des États.
Keywords: Communautés européennes; Droit international; European union; Globalization; International jurisdiction; International law; International norm; International organization; Intégration normative; Juridiction (droit international); Juridiction internationale; Legal pluralism; Mondialisation; NGO; Normative integration; Norme internationale; ONG; Organisation internationale; Organisations non gouvernementales; Pluralisme juridique; Responsabilité (droit international); Souveraineté; Sovereignty; State; Union européenne; État

A consolidação da União Africana e o desenvolvimento sustentável: novos horizontes da integração econômica para viabilizar o mercado comum da África - Fernandes, Joel Aló (Universidade Federal de Santa Catarina, 2012)
O presente estudo envolve-se com o tema da União Africana. Na sua abordagem procura analisar a relação do mercado comum africano com o desenvolvimento sustentável, transitando interdisciplinarmente em vários campos de conhecimentos, com ênfase nas Relações Internacionais, Direito Internacional, Economia, Política e História. A investigação, nesse sentido, tem como hipótese a afirmação de que a consolidação do processo de integração política do continente poderá, em primeiro momento, apresentar-se como medida necessária à sua unificação, para que seja realizado, em um segundo momento, por meio da integração econômica, o tão almejado mercado comum africano e seu desenvolvimento sustentável. Tal abordagem abrange diversas variáveis, especialmente o fenômeno do regionalismo, a integração política e econômica e o desenvolvimento sustentável. O objetivo principal consiste em abordar o universo da criação, evolução e consolidação da União Africana e do desenvolvimento sustentável, como instrumentos de superação das dificuldades da integração política e econômica da África. O resultado da pesquisa positiva a confirmação da hipótese, reconhecendo de que a unificação política será fundamental ao processo de integração econômica, rumo ao estabelecimento do mercado comum africano e seu desenvolvimento sustentável. This study involves the themes of the African Union and the sustainable development. In its approach it seeks to analyze the relationship of the African common market with sustainable development, transiting across disciplines in various fields of knowledge, with an emphasis on International Relations, International Law, Economic Policy and History. The scientific research relates to consolidation of the African Union and the sustainable development, whose chance to work is expressed in the sense of asserting that the consolidation of the process for political integration of the African Union may be first, presented as a measure for political unification of Africa and then, follow in a second step, to materialize through economic integration, its targeted African common market and the sustainable development. Such an approach includes several variables, especially the phenomenon of regionalism, the political and economic integration and the sustainable development. The main objective is to address the universe of creation, evolution and consolidation of the African Union and sustainable development, as a means of overcoming the challenges of political and economic integration of Africa. The result of the positive research confirms and recognizes the fact that the materialization of the African Union will help in the process of political and economic unity toward establishment of a common market and its sustainable development.
https://core.ac.uk/works/18417619/

La jurisprudence, source du droit OHADA - Gatsi, Jean (Persée - Portail des revues scientifiques en SHS, 2012)
La jurisprudence contribue à l’essor du droit OHADA, à travers l’éclairage ou la création des concepts, et l’application des dispositions des Actes uniformes. L’application des dispositions de droit OHADA se fait en amont par les juridictions nationales, et en aval par la Cour Commune de Justice et d’Arbitrage (CCJA) suivant les modes juridictionnel et arbitral. En droit OHADA, la jurisprudence de la CCJA est appréciée à travers la pertinence de ses avis consultatifs ayant valeur délibérante, ainsi que par rapport au contentieux et l’arbitrage. À la suite des juridictions inférieures des États parties, la CCJA connait des pourvois en cassation contre les décisions des juridictions internes traitant des questions relatives à l’interprétation des Actes uniformes. Elle est aussi compétente pour connaitre des questions d’arbitrage. Dans tous les cas, les décisions rendues par la CCJA s’imposent aux juridictions des États parties.

Le rôle des juridictions supranationales de la CEMAC et de l'OHADA dans l'intégration des droits communautaires par les Etats membres - Fipa Nguepjo, Jacques (Université Paris 2, 2011)
La Cour de Justice Communautaire (CJC), la Cour des Comptes Communautaire (CCC) et la Cour Commune de Justice et d’Arbitrage (CCJA) sont les trois juridictions supranationales créées respectivement par les traités de la CEMAC et de l’OHADA pour renforcer les nouveaux processus d’intégration économique et juridique des Etats membres. Dans la mesure où ces juridictions exercent un contrôle juridictionnel déterminant de la norme communautaire, le premier contrôle étant effectué par les juridictions nationales des Etats parties, la conception, l’organisation, le fonctionnement, les caractéristiques, les rôles ou compétences de ces juridictions nouvelles ainsi que la destinée des décisions qu’elles rendent dans leurs fonctions strictement judiciaires ou dans celles accessoires d’appui à la procédure arbitrale, présentent un intérêt digne d’une recherche doctorale. S’il est apparu que des jalons supplémentaires d’efficacité des nouveaux processus d’intégration ont été plantés par la création desdites juridictions, il a également été constaté que des pesanteurs d’ordre juridictionnel, structurel ou fonctionnel continuent d’en retarder la vitesse de croisière. Les solutions que nous avons proposées pour surmonter ces difficultés se regroupent en une réorganisation des juridictions communautaires, une répartition claire des compétences entre elles, un renforcement de la procédure de contrôle du droit communautaire, une vulgarisation permanente du droit de l’intégration, une revalorisation des titres exécutoires, une clarification des fonctions du juge d’exécution, une restriction du domaine de l’immunité d’exécution, un réaménagement des procédures de recouvrement, une formation continue des acteurs de la justice, une amélioration de leur condition de travail et de vie, une résurgence de l’éthique morale, une réelle indépendance de la justice… C’est dire que l’étude met un accent sur les obstacles qui entravent les nouveaux processus d’intégration et propose des solutions pour parfaire les textes législatifs et leurs interprétations jurisprudentielles, dans la perspective d’accélérer le développement économique des Etats concernés en particulier, pour une meilleure prospérité globale des économies mondiales. = The Communautary Court of Justice (CCJ), the Communautary Court of Account (CCA) and the Common Court of Justice and Arbitration (CCJA) are the three supranational jurisdictions respectively created by EMCAC and OHBLA treaties to reinforce the new processes of economical and judicial integration for their member States. In the measure where these jurisdictions are competent to exercise a juridictional control, by determining the communautary norms, the first control being carried out by the national juridictions, the conception, the organisation, the functioning, the characteristics, the roles or competences of these new jurisdictions and also the destiny of the decisions they rend in their strictly judiciary functions or in their accessory functions of supporting the arbitral procedure, present an interest worthy of a doctorate research. If it appears that the supplementary Milestones of efficiency of the new processes of integration had been installed by the creation of the said jurisdictions, it had also been observed that the gravities of jurisdictional, structural or functional order continue to delay the speed of cruise. The solutions that we have proposed to overcome these difficulties involves the reorganization of communautary jurisdictions, the clearly distribution of competences between them, the reinforcement of the communautarian law control procedure, a permanent vulgarisation of integration law, a revalorisation of executary titles, a clarification of immunity of execution domain, a development of the recovery procedures, a continual training of judicial actors, and improvement of their working and living conditions, a resurgence of moral ethic, a real independence of the Justice… This means that the study put a stress on the obstacles which hold up the new processes of integration and propose solutions to perfect the legislative texts and their jurisprudential interpretations, in the perspective of accelerating the economic development of the concerned States, for the best global prosperity of the world’s economies.
https://assasrecherche.u-paris2.fr/ori-oai-search/notice/view/2011PA020030
Keywords: Advisory opinion; Africa; Afrique; Afrique centrale; Arbitrage; Arbitragem; Arbitral sentence; Arbitration; Avis consultatif; CCJA; CEMAC; Central Africa economic and monetary community; Communautary court of justice; Communautary judge; Competent authority; Compétence (droit) - Afrique; Compétences; Conflicts; Conflit; Corruption; Cour Commune de Justice et d'Arbitrage; Cour de justice communautaire (CJC); Cour des comptes communautaire; Court of account; Droit commercial (droit international); EMCAC; Economic integration; Efficacité; Enforceable provisional execution; Enforcement; Executory title; Exequatur; Exécution provisoire; Harmonisation; Immunity of execution; Immunité d'exécution; Imperceptibility; Insaisissabilité; Integration; International unification; Intégration; Intégration économique; Juge communautaire; Juge national; Juridiction - Afrique; Jurisdiction; National court; OHADA; OHBLA; Organisation for the harmonisation of business law in Africa; Preliminary ruling; Provisional execution; Reforms; Regulation; Renvoi préjudiciel; Réformes; Régulation; Rôle; Sentence arbitrale; Supranationality; Supranationalité; Titre exécutoire; Traité; Treaty; UEAC; UMAC; Unification internationale

L'Application effective du droit communautaire en Afrique centrale - Tchuinte, Joël (CY Cergy Paris Université, 2011)
La réussite du processus d'intégration régionale dépend essentiellement de sa réception et de sa sanction dans les ordres juridiques internes. la crainte principale réside dans l'ineffectivité des règles communes dans les Etats parties. Ceux-ci peuvent en effet refuser de tirer toutes les conséquences du transfert des compétences qu'ils effectuent librement au profit des organes communautaires.Si la CEMAC peine aujourd'hui à trouver le juste équilibre entre les objectifs ambitieux qu'elle affiche et la capacité des Etats membres à les réaliser en commun, l'OHADA arrive, dans un environnement difficile, à tracer une voie qui est porteuse d'espoirs.
Keywords: African community law; Afrique centrale; CCJA; Communauté Economique et Monétaire de l'Afrique Centrale; Constitutionnal law; Cour Commune de Justice et d'Arbitrage; Cour de justice CEMAC; Droit communautaire africain; Droit constitutionnel; Droit international; Droit interne; Droit public; Droits constitutionnels africains; EMCCA; EMCCA Court; Effectivité; France; Intégration régionale; OHADA et CEMAC; OHBLA; OHBLA Court; Organisation pour l'harmonisation en Afrique du droit des affaires; Public law; Regional integration

De la réforme et de l'harmonisation du droit des sûretés dans un contexte de mondialisation de l'économie : vers un retour au paradigme de l'uniformisation du droit? - Leduc, Antoine (Université de Montréal, 2011)
La réforme et l’harmonisation du droit des sûretés mobilières sont à l’ordre du jour de plusieurs organisations internationales, car il est admis qu’un régime de sûretés efficient favorise l’accès au crédit à de faibles coûts. L’harmonisation de ce droit comporte deux volets. D’une part, dans l’Occident industrialisé, les efforts d’harmonisation vont de la réforme des droits internes à l’établissement de régimes spéciaux relativement à des biens spécifiques (principalement les biens mobiles de grande valeur, tels les aéronefs, le matériel ferroviaire roulant et les satellites, et les biens incorporels, comprenant les créances, valeurs mobilières, actifs financiers et titres intermédiés). Ces efforts d’harmonisation démontrent que d’un point de vue systémique, malgré quelques différences notables, les régimes nord-américains et européens sont fondés sur des principes similaires et atteignent des résultats comparables. En résulte l’émergence d’un ordre juridique transnational en droit des sûretés mobilières, fondé sur les principes de la primauté de l’individu et la reconnaissance du droit de propriété de l’individu dans ses biens, mis en œuvre grâce à l’État de droit. D’autre part, les institutions financières internationales encouragent l’établissement de régimes de sûretés dans les pays en voie de développement qui obéissent aux mêmes critères que ceux de l’Occident, en insistant sur les réformes institutionnelles et juridiques visant l’établissement d’une bonne gouvernance et l’État de droit. Cependant, une transposition des régimes occidentaux ne peut se faire sans heurts dans les pays en voie de développement, notamment pour des raisons socio-culturelles et politiques. Lorsque les principes de la primauté de l’individu, de la propriété individuelle et de l’État de droit ne sont pas reconnus dans un pays donné, la réforme et l’harmonisation du droit des sûretés s’en trouvent compromis. La démonstration de l’état d’avancement de la réforme et de l’harmonisation du droit des sûretés dans les pays occidentaux industrialisés est faite grâce à une comparaison du Uniform Commercial Code, du Code civil du Québec, des Personal Property Security Acts des provinces canadiennes de common law, des principes des droits français et anglais, de l’influence du droit communautaire sur les pays membres de l’Union Européenne. Sont analysés, aussi, dans cette optique, les principaux instruments de l’harmonisation du droit émanant des organisations internationales. Par ailleurs, deux études de cas relatifs à la réforme du crédit foncier en Égypte et à la réforme de l’urbanisme et de l’habitat en République démocratique du Congo, viennent étayer les difficultés que rencontrent les institutions internationales, telles la Banque mondiale et l’ACDI, dans le cadre de projets de réformes visant la bonne gouvernance et l’instauration d’un véritable État de droit, en partie à cause d’un pluralisme des ordres juridiques de ces pays. The reform and harmonization of secured transactions on movable (or personal) property is fostered by international organizations, on the assumption that an efficient regime of secured transactions will give access to affordable credit to a large number of persons and corporations. Such reform and harmonization process can be explained according to its two main features. Firstly, in Western and developped countries, the focus is on endeavours to harmonize the various regimes internally and to establish special regimes with respect to specific assets (for instance, high value mobile equipment, such as aircrafts, rolling stock or satellites, on the one hand, or incorporeal property, including securities, financial assets or security entitlements, on the other hand). Even though some differences remains from a systemic point of view, north american and european regimes are based on similar principles and achieve comparable results. It is therefore possible to see the emergence of a transnational legal order in the law of secured transactions, based on individuals and the enforcement of their rights of ownership, ascertained by the Rule of Law principle. Secondly, international financial institutions are encouraging the implementation of secured transactions regimes in developing countries along the same criteria as those used in Western developed countries, in the context of institutional and legal reforms under governance and rule of law projects. However, Western regimes must be adapted and customized before they are transplanted into a developing country. Indeed, for socio-cultural and political reasons, it is not possible to establish the same kind of regime therein. When individual rights and freedoms, including the right of ownership and the Rule of Law, are not recognized, the reform and harmonization of secured transactions is not likely to happen. The status of advancement of the reform and harmonization of secured transactions in the developed world is illustrated by a comparison between the Uniform Commercial Code, the Civil Code of Québec, the Personal Property Security Acts of canadian common law provinces, the applicable principles under both French and English Law, and the influence of European Law on its member states. An analysis of the main harmonization instruments proposed by international organizations is also conducted. Finally, the pitfalls of governance and rule of law reform projects are well described by two case studies. The first one deals with real estate and mortgage law reforms in Egypt, with a goal to encourage affordable access to housing; the second one is about urban planing and housing reforms in the Democratic Republic of Congo. The existence of a multiplicity of legal orders in these countries explains the difficulties encountered in such reform processes.
Keywords: ACDI; African Customary Law; Banque mondiale; Civil Law; Common law; Comparative law; Droit civil; Droit comparé; Droit coutumier africain; Droit et développement; Droit islamique; Harmonisation; Islamic Law; Law and Development; Rule of Law; Secured transactions; Sûretés mobilières; World Bank; État de droit

Can OHADA Increase Legal Certainty in Africa? - Beauchard, Renaud; Kodo, Mahutodji Jimmy Vital (The World Bank, 2011)
This paper describes the origins, structure, and practical impact of the Organization for the Harmonization of Business Law in Africa (OHADA). It analyzes the institutional framework created via the OHADA Treaty and the legal, jurisprudential, and functional challenges that OHADA Member States are still grappling with. Details of the nine substantive laws that have so far been ratified as uniform acts by means of the treaty have also been provided. The authors conclude that in making OHADA law effective, Member States face continuing and substantial resource deficits, institutional deficiencies, language ambiguities, and intransigent official attitudes toward the need for appropriate mechanisms for the pursuance and enforcement of OHADA laws and processes.

Multi-Membership and the Effectiveness of Regional Trade Agreements in Western and Southern Africa: A Comparative Study of ECOWAS and SADC - Afesorgbor, Sylvanus Kwaku; Van Bergeijk, Peter A. G. (Proceedings of the German Development Economics Conference, 2011)
Using a gravity model for 35 countries and the years 1995-2006 we estimate the impact of regional trade agreements in Africa (in particular ECOWAS and SADC) and compare this to the a benchmark of North South trade integration (Europe‟s preferential trade agreement). We find that  ECOWAS and SADC membership significantly increases bilateral trade flows (and by more than for example preferential trade agreements with the EU do),  SADC membership has a stronger impact compared to ECOWAS and  that the impact of multi-membership critically depends on the characteristics of the overlapping RTA We find a positive impact if an additional membership complements the integration process of the original RTA: overlapping memberships had a significant positive effect on bilateral trade within the ECOWAS bloc but it is insignificant for SADC.

Comparative regionalism: a new research agenda - Börzel, Tanja A. (KFG The Transformative Power of Europe, 2011)
After the end of the Cold War, students of International Relations observed an expansion of inter-state activities at the regional level. Regional and sub-regional groupings appeared to gain momentum as the way in which countries cooperate and should cooperate to pursue peace, stability, wealth and social justice. The surge and resurgence of regionalism has triggered the proliferation of concepts and approaches. The focus of this paper will be on processes and structures of state-led regionalism driven by the delegation of policies and political authority to regional institutions. Based on this understanding of regionalism, the existing literature will be reviewed with regard to three general questions. These questions do not only require research across regions but also allow developing a common research agenda to accumulate knowledge generated about specific regions. First, what are the outcomes of regionalism? How can we describe and compare the results of the delegation of policies and political authority? Second, what are the drivers of regionalism? Why do some governments choose to delegate policies and political authority while others do not? Finally, what are the internal effects of regionalism? How does the delegation of policies and political authority impact back on the domestic structures of the states involved?
Accepted: 2018-06-08T07:36:10Z

Economia política da integração regional na África ocidental : a União Econômica e Monetária (UEMOA) como estratégia para o desenvolvimento regional - Fernandes, Lito Nunes (Universidade Federal do Rio Grande do Sul, 2011)
No início do novo milênio, a formação de blocos econômicos regionais foi-se apresentando como estratégia de promoção do desenvolvimento para os países periféricos. Tratando-se da África Ocidental, a integração de seus pequenos países com vista a usufruir as vantagens decorrentes desse processo resulta em última instância, a solução potencial de seus diversos problemas, e a resposta da sua marginal posição na atual globalização. São países que enfrentam malformações estruturais e situações dramáticas de pobreza e miséria produto de séculos de exploração, repartição desinteressada e agressiva de seus territórios a beneplácito da acirrada competência imperialista e da colonização posterior. Neste sentido, esta tese propõe responder duas perguntas: quais as causas do estabelecimento de uma união econômica e monetária numa região sem condições prévias e se esta integração está conduzindo ou não a seus países ao desenvolvimento. A mesma parte da hipótese de a integração regional na atualidade ser a alternativa mais viável para garantir a sustentabilidade do processo de desenvolvimento nesta região. O objetivo da tese é analisar a dinâmica regional da integração da UEMOA, que surgiu contrária à visão convencional das teorias monetárias, como estratégia do desenvolvimento, e em seguida, vincular seus resultados ao desenvolvimento econômico dos países da região. Ressalta-se que foi dada prioridade a literatura africana, não por rechaço ou demérito da produção ocidental sobre o tema, mas pelo entendimento de que, neste aspecto específico, as opiniões dos autores africanos dariam um melhor enriquecimento e uma visão mais realista sobre o tema. Conclui-se que independentemente de não seguir as diretrizes convencionais, a integração da UEMOA está sendo fundamental para o desenvolvimento de seus países, segundo a realidade da região. Portanto, sua análise deve ser realizada acorde a especificidade local, sem esquecer as conseqüências do seu passado histórico que ainda repercutem negativamente na sua situação socioeconômico. Ou seja, sua valoração não deve seguir o modelo das regiões desenvolvidas ou emergentes, mas sim desde a perspectiva das duras realidades da região.
URI: https://lume.ufrgs.br/handle/10183/36098
Keywords: Afrique occidentale; Blocos econômicos; Desenvolvimento regional; Development; Integração econômica; Integração regional; Intégration régionale; Países em desenvolvimento; Regional integration; UEMOA; WAEMU; Western Africa; África Ocidental

Integração Econômica Regional Na África Ocidental: Uma Visão Crítica - Fernandes, Lito Nunes; Boukounga, Jean Christian; Júnior, José Fernandes (Conjuntura Austral, 2011)
Os blocos econômicos regionais estão sendo na atualidade instrumentos importantes na luta contra a pobreza, subdesenvolvimento e inserção na economia global e a África Ocidental (AO) apresenta como uma das regiões mais interessadas. Consciente desta realidade, o artigo trabalha com a hipótese de a integração ser a condição sine qua non mesmo que insuficiente para o desenvolvimento da região. O objetivo é demonstrar as diversas iniciativas integracionistas na AO, os logros obtidos apesar da especificidade da região, assim como as adversidades e obstáculos encontrados. Conclui-se que apesar dos problemas e mesmo que essa integração não siga os padrões ocidentais, o estabelecimento de uma união monetária numa zona sem condições mínimas por si só, é um êxito, opondo desta forma as críticas da literatura ocidental que quase sempre catalogam de fracassadas as integrações africanas.
Keywords: Integração regional; Regional integration; Western Africa; Western Countries; desenvolvimento; development; ocidente; África Ocidental

Challenges to regional intergration in the SADC region : a legal perspective - Mwanawina, Ilyayambwa (North-West University, 2011)
The Southern African Development Community (SADC), formerly known as the Southern African Development Coordination Conference (SADCC), is an organization of Southern African states initially formed to reduce economic dependence on South Africa (then an Apartheid state) and to harmonize and coordinate development in the region. The vision and mission of SADC reach well beyond the harmonization of development within the region. It extends to fields that include political stability, peace building, the maintenance of security and justice as well as economic cooperation. The attainment of these goals requires well co-ordinated regional mechanisms; as such over the past decade member states have paid particular attention to the possibility of attaining these goals through regional integration. The transformation from SADCC to SADC indicated that the body would no longer be a loose association (conference) of states but rather a regional body that would have a legally binding effect on its member states. The question is, when the member states assembled in Windhoek, August 1992, did they create an institutional framework, and policies that would have enough legal force to ensure that the institutional agenda of integration is not defeated by member states? The argument of this dissertation is that the Treaty and the policies established afterwards contain principle imperfections that are self defeating for the pursuance of regional integration. The work will begin by discussing regional integration in general, highlighting the historical origins of SADC as well as the role of the African Union. The work will then discuss the dimensions and functioning of SADC, laying the foundation for a proper critique on how the institutional framework contains inherent weaknesses that eventually hinder the progression of SADC. The dissertation ultimately will discuss and benchmark the European Union against SADC, in an attempt to extract important lessons for the progression of SADC.
Accepted: 2016-01-10T22:52:56Z https://repository.nwu.ac.za/handle/10394/15788
Keywords: Africa; Interregionalism; Southern

A politico-legal framework for integration in Africa : exploring the attainability of a supranational African Union - Fagbayibo, Babatunde Olaitan (University of Pretoria, 2010)
The emergence of the African Union (AU) is seen as an effort to reposition Africa for the challenges of contemporary global realpolitik and, in particular, it provides a road map towards the attainment of a political union. The institutional architecture of the AU, modelled after the European Union (EU), indicates an intention on the part of the architects of the AU to endow the organisation with supranational attributes. However, none of its institutions has as yet started to exercise supranational powers. It is against this background that this thesis explores the feasibility of transforming the AU from a mere intergovernmental organisation into a supranational entity. In the course of the investigation, it was found that a major obstacle to realising this is the absence of shared democratic norms and standards, a consequence of the unconditional membership ideology of the AU. This thesis argues that the starting point of closer integration in Africa should be the cultivation and adoption of shared norms and values. To address this, the study proposes that the AU design an institutional mechanism for regulating its membership. Using the African Peer Review Mechanism (APRM) as a case study, this study shows that it is possible to establish a regulatory regime based on strict adherence to shared fundamental norms and values. A major recommendation is the transformation of the APRM into a legally binding instrument for setting continental democratic standards, assessing whether member states fulfil these standards and ultimately determining which member states are qualified, based on objective standards, to be part of a democratic AU.
https://repository.up.ac.za/handle/2263/28573
Keywords: African Union; African peer review mechanism; Regional economic communities (RECs); Regional integration

L'harmonisation du droit des affaires en Afrique par l'OHADA : Synthèse des travaux - Issa-Sayegh, Joseph (Revue juridique de l'Océan Indien, 2010)
Keywords: Extension des Actes Uniformes; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires Sécurité juridique; Uniformisation du droit des affaires; extension territoriale de l'OHADA; sécurité judiciaire

Le droit de l'OHADA : une source d'inspiration pour les législateurs nationaux ? - Ponsot, Dominique (Revue juridique de l'Océan Indien, 2010)
Keywords: Apport doctrinal; Apport universitaire; Droit OHADA; Droit commercial régional; Intégration; Membre de l'organisation; Organisation pour l'harmonisation en Afrique du droit des affaires actes uniformes; Pays non-membres; Pays tiers; Reprise du droit OHADA; Sources du droit

The New African Law: Beyond the Difference Between Common Law and Civil Law - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

Développement et intégration régionale en Afrique de l'Ouest : analyse des contributions de l'OHADA et de l'UEMOA - N'Guessan, Donald Jean-Marc (Université de Reims Champagne-Ardenne, 2010)
L'intégration juridique apparaît telle une prometteuse locomotive de l'intégration économique. La confiance que le droit OHADA devrait susciter chez les opérateurs économiques, en procédant progressivement à la sécurisation juridique et judiciaire du marché commun de I'UEMOA, devrait les inciter à y créer et développer des activités économiques. Ce, en quoi nous nous interrogeons de savoir si le droit des affaires OHADA peut être productif de dynamique économique par l'investissement privé direct étranger ou national, considéré au troisième millénaire comme le moteur de la croissance, dans l'espace UEMOA, libre de circulation. Dans l'optique de cette démarche sécuritaire et impulsive, I'OHADA et I'UEMOA vont participer à I'édification de ce cadre juridique communautaire au travers d'un dispositif conçu autour de quatre axes, à savoir : un dispositif de sécurité organisationnelle capable de garantir la solidité et le fonctionnement autonome et pérenne des institutions communautaires chargées de conduire le projet d' intégration à sa réalisation ; la consécration d'une intégration juridique relative aux affaires, comme outil fondamental de consolidation de l'intégration économique : l'édification de structures communautaires chargées de défendre ce droit dont l'application est déterminante à la sécurité dans les relations d'affaires ; enfin, I'instauration d'une liberté de circulation dans tout I'espace communautaire afin de favoriser les échanges intracommunautaires, indispensables à la dynamique juridico-économique régionale , et dont l'analyse devrait permettre d'apprécier le niveau de réalisation et la fonctionnalité de cette plateforme OHADA-UEMOA.
Keywords: Afrique occidentale; Intégration économique; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; UEMOA; Unification internationale; Union économique et monétaire Ouest africaine; WAEMU

The Role of South Africa in SADC Regional Integration: the Making or Braking of the Organization - Amos, Saurombe (Journal of International Commercial Law and Technology, 2010)
Read on Neliti

Rhapsodie sur la forme et le fond de l’harmonisation juridique - Leckey, Robert (Les Cahiers de droit, 2010)
L’auteur soutient dans le texte qui suit que les aspects par lesquels l’harmonisation du droit fédéral avec les droits communs provinciaux, qui a été entreprise par le gouvernement fédéral, diffère de son éponyme, l’harmonie musicale, soulèvent de cruciales controverses relatives aux théories du fédéralisme canadien et à la philosophie du droit. Tandis que le projet d’harmonisation juridique, tel qu’il a été conçu par ses architectes, peut être caractérisé comme une approche par le haut (top-down), approche conforme avec le positivisme juridique, l’harmonie musicale est mieux décrite comme une approche par le bas (bottom-up), approche plus conforme au pluralisme juridique. Si elle atteignait ses objectifs, l’initiative d’harmonisation juridique fédérale aurait comme effet d’enchâsser une vision selon laquelle le droit civil appartient exclusivement au gouvernement québécois. Or, malgré les ambitions de ses architectes, l’initiative d’harmonisation, dans sa mise en oeuvre, se révèle indisciplinée, soulevant de nombreux débats et interrogations. D’ailleurs, loin d’être un signe négatif, les débats et les désaccords font eux-mêmes partie de la pratique de l’harmonisation.

Directive sur l'harmonisation des principes directeurs et des politiques dans le secteur minier - Communauté Economique des Etats de l'Afrique de l'Ouest (2009)
Keywords: CEDEAO; ECOWAS; Mines; Politique minière

L'OHADA : vers un droit unifié des échanges dans la zone Océan Indien ? - Ponsot, Dominique (Revue juridique de l'Océan Indien, 2009)
Actes des journées d'étude sur le thème “ les échanges économiques dans la région Océan Indien ”, colloque organisé par l'Association Henri Capitant, avec le concours des Facultés de Droit et d'Economie de la Réunion et d'Antananarivo et de l'Ambassade de France à Madagascar, Tananarive, 13 et 14 mars 2008
Keywords: Acte uniforme; Comores; Droit du commerce régional; Droit français; Madagascar; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; Zone Océan indien

Traité révisé de la Communauté Economique et Monétaire de l'Afrique Centrale (C.E.M.A.C.) - Communauté Economique et Monétaire de l'Afrique Centrale (2009)

Future Directions of Legal Harmonisation and Law Reform : Stormy Seas or Prosperous Voyage ? - Faria, José Angelo Estrella (Uniform Law Review, 2009)

The need to harmonise trade-related laws within countries of the African Union: an introduction to the problems posed by legal divergence - Dlagnekova, Polina (Fundamina : A Journal of Legal History, 2009)
It is widely accepted that inter-state relationships have entered an era of globalisation. The economic theory of convergence explains that it is this phenomenon which has spearheaded, amongst others, the development of international rules in the field of trade, finance and taxation.

Le droit commun des contrats face à l’émergence des droits communautaires africains - Watcho née Keugong Ngueken, Rolande Saurelle (Université de Dschang, 2009)
L’émergence des espaces d’intégration devant aider au renforcement des structures d’intégration économique et politique créées en Afrique au lendemain des indépendances a eu pour conséquence, l’apparition d’un droit matériel essentiellement économique. L’objectif affiché par les différents législateurs communautaires est de moderniser les règles juridiques applicables dans le domaine économique afin de les rendre conformes aux exigences du commerce international et favoriser la sécurité juridique propice au développement des investissements. Or, parce que les contrats constituent les mécanismes juridiques par excellence de l’organisation de la vie économique, ces nouvelles réglementations ne pouvaient manquer d’influencer directement ou indirectement le droit des contrats. L’influence du droit communautaire sur le droit des contrats s’observe en premier lieu dans les réglementations éparses, adoptées aussi bien dans le cadre de l’OHADA, de la CEMAC que de la CIMA. Ces institutions harmonisent en les modernisant les contrats spéciaux dont la plupart ont été hérités du législateur colonial par les Etats membres. C’est ainsi que les perturbations à la théorie générale des contrats relevées dans ces contrats étaient déjà connues dans les Etats membres bien avant l’avènement du droit communautaire. Cependant, cette réaction face aux insuffisances de la théorie générale des contrats ne pouvait s’éterniser au risque de voir celle-ci se vider de sa substance. C’est pourquoi, en second lieu, par un avant-projet d’Acte uniforme, le législateur OHADA offre de s’aligner sur la voie déjà tracée depuis les années 1990 par de nombreux pays ayant adopté le code civil de 1804, en révisant sa partie réservée au droit des contrats. Sans toutefois remettre en cause les principes fondamentaux de la théorie générale des contrats, l’auteur de ce avant-projet propose d’offrir un droit des contrats moderne, moins antagoniste, intégrant les principes de transparence et d’équilibre. Il est question d’apporter des correctifs nécessaires à la rigueur à laquelle a abouti l’interprétation libérale des règles du code civil à l’aune de la théorie de l’autonomie de la volonté. Prenant en compte la diversité du droit communautaire applicable au Cameroun, ce travail met en exergue les transformations que connaît le droit des contrats actuellement applicable et propose les voies et moyens par lesquels la théorie générale du droit des contrats peut évoluer grâce à l’avènement des nouvelles réglementations.
https://dicames.online/jspui/handle/20.500.12177/2203
Keywords: CEMAC; CIMA; Droit commun; Droit communautaire africain; Droit des contrats; OHADA

Vision du marché commun des investissements de la CEDEAO - Communauté Economique des Etats de l'Afrique de l'Ouest (CEDEAO, 2009)
Keywords: CEDEAO; Common market; ECOWAS; Investissements; Investments; Marché commun

Unified Business Laws for Africa: Common Law Perspectives on OHADA - Dickerson, Claire Moore (GMB Publishing Ltd, 2009)

The Role of International Economic Law in Africa - Obale, Offah Ako (Social Science Research Network, 2008)
International Economic law (IEL) has a specific role to play in a complex modern Africa. The underdeveloped state of trade law regimes in Africa is arguably a reflection and product of the low level of commercial activity. The reverse is equally true in that underdevelopment in commercial activity on the continent is a reflection and product of the minimal role played thus far by international economic law.
Keywords: AEC; Africa; African; African Economic Community (AEC); Doha; Globilisation; International Economic Law; OHADA; Trade law; WTO

Reforming Legal Reform in Francophone Africa: World Bank' Project Experience - Wabnitz, Hans-Werner (Islamic Law and Law of the Muslim World Paper, 2008)
You don't plant water lilies in the desert - The keystone of civilized society is justice. Without justice, neither peace nor development. A prerequisite is the populations' trust in legal institutions: the law and the courts. The alienation of the people with imposed legal institutions is the reason for Francophone Africa's lack of justice. To remedy the situation, this paper proposes to reconnect the people with the law through: (1) respecting local values in Village tribunals; (2) reforming lawmaking to comply with custom, accessible (also) in vernacular languages; (3) accessibility of law through the Internet. It is argued that the people, as client of justice, need to regain control over their law in order to respect it. Only then the necessary change of traditions and values is feasible. Women lawyer associations are identified as agents for such change. To redress modern courts, the paper suggests a concentration of tribunals, a tightening of procedure and rigorous control, in order to foster peer pressure for professionalism. The constitutional values are to serve as common bond.
Keywords: ACCESS TO JUSTICE; Africa; Colonial law; Corruption; Court administration; Culture; Customary law; Drafting; Equality; Fatwa; Gender; Honor; Human rights; Institutions; Justice; Law; Legal reform; OHADA; Paralegals; Participation; Reform; Tradition; Uniform Act; Village courts; Worldbank

L’OHADA : défis, problèmes et tentatives de solutions - Issa-Sayegh, Joseph; Pougoué, Paul-Gérard (Uniform Law Review, 2008)

Some preliminary thoughts on a comparative law model for harmonisation of laws in Africa - Nicholson, Caroline (Fundamina : A Journal of Legal History, 2008)
This paper is premised upon acceptance of the view that some form of harmonisation of laws in Africa is a desirable objective and that comparative legal research is a tool that might effectively be applied in order to further the objective of harmonisation. That said, the time has come for comparatists in Africa to think afresh on the issues of globalisation and the need for harmonisation of laws in Africa, with a view to promoting peace, stability and scope for increased development in the region through greater regional economic co-operation.

Le droit de l’OHADA dans les États anglophones et ses problématiques linguistiques - Dickerson, Claire Moore (Revue internationale de droit comparé, 2008)
La décision d’un gouvernement d’adopter ou non un nouveau droit dépendra des réalités politiques. Le droit des affaires de l’OHADA, d’inspiration civiliste, est uniforme sur une espace comprenant 16 pays de l’Afrique de l’Ouest et l’Afrique Centrale. Ces pays ne peuvent pas directement influencer la politique interne de leurs voisins, mais ils peuvent modifier le droit de l’OHADA afin de le rendre plus facilement adoptable par leurs voisins habitués à la common law. Sur le fond, les différences entre les deux systèmes dans le domaine du droit des affaires ne sont pas très marquées, car tous les deux ont des aspects déductifs. Néanmoins, il y a des difficultés de traduction. Il y a également des difficultés culturelles, car l’equity qui agit en parallèle avec la common law apporte une flexibilité au système anglo-saxon, tandis que le système civiliste tel que l’OHADA agit par des règles et des structures. La simplicité de celles-ci peut être un avantage, mais afin de faciliter la politique d’une adhésion éventuelle, il serait utile que l’OHADA accepte de retravailler les traductions avec des juristes anglophones et aussi d’adopter certains concepts juridiques d’origine anglo-saxonne.
Keywords: Anglais; Droit OHADA; Langues

Le voisinage en Afrique : plaidoyer pour la construction d’un droit africain du voisinage - Fometeu, Joseph (Revue internationale de droit comparé, 2008)
En Afrique, le voisin est, en règle générale, un véritable « frère de service », même si, à la faveur d’une urbanisation plus que galopante, il est parfois un gêneur. Pourtant, à l’observation, peu de procès sont intentés dans le cadre du voisinage. On peut alors penser que cette carence est de nature à couver les conflits et à prédisposer les uns et les autres à se réconcilier, comme à l’intérieur d’une communauté. Comme corollaire, le droit du voisinage tel qu’il ressort des textes hérités de la colonisation et qui sont encore en vigueur dans la plupart des États africains n’est pas entièrement adapté aux réalités de la vie dans les quartiers africains. D’où, sans doute, la nécessité pour ce continent, de développer son propre droit du voisinage. Ce développement orienté vers un assouplissement de certaines règles juridiques régissant la matière prendrait d’abord appui sur le fait que le droit positif lui-même a conservé des règles amiables dans les rapports de voisinage, notamment en matière de copropriété, de servitude et de mitoyenneté. Il s’appuierait ensuite sur l’inadaptation de la catégorie de règles qui tendent à exacerber les droits individuels dans le voisinage. Enfin, il s’appuierait sur la tendance des législations contemporaines à promouvoir la conciliation comme préalable aux procédures contentieuses.

L’intégration juridique dans l’Union économique et monétaire ouest africaine (UEMOA) et dans l’organisation pour l’harmonisation du droit des affaires en Afriques (OHADA) - Sarr, Amadou Yaya (Presses universitaires d’Aix-Marseille, 2008)
Docteur en droit, Amadou Yaya SARR, est actuellement chef du Département des Ressources Humaines du Port Autonome de Dakar et Enseignant Vacataire à l’Université Cheikh Anta DIOP de Dakar. Pourtant rien ne lui laissait présager un tel parcours. En effet, Monsieur SARR, a été embauché dans cette entreprise le 11 Octobre 1972 comme ouvrier mécanicien. Ainsi, pendant 36 ans, il a gravi tous les échelons de la vie professionnelle dans cet établissement. Avec la volonté et l’abnégation il a, parallèlement à ses activités professionnelles, entrepris des études de droit à l’Université Cheikh Anta DIOP de Dakar, de la Capacité au DEA et au DESS. Il s’est par la suite inscrit en Thèse de Doctorat à l’Université d’Aix Marseille III, diplôme qu’il a soutenu avec brio en Juin 2006. Cette brillante Thèse a obtenu le 1er Prix du Droit International Public. L’auteur est médaillé dans l’Ordre National du Mérite de la République du Sénégal. Le présent ouvrage est issu d’une Thèse de Doctorat en Droit, soutenu le 30 Juin 2006 à l’Université d’Aix Marseille III en France. En effet, l’auteur, en observateur averti, a, dans une analyse minutieuse des traités de l’UEMOA et de l’OHADA, procédé à l’étude de la coexistence de ces Organisations dans les espaces économiques de leurs différents Etats-membres. Il a ainsi démontré dans un premier temps la réalité de cette coexistence, tant au niveau des sources du droit, qu’au niveau des systèmes institutionnels. Il a ensuite démontré les manifestations de cette coexistence par l’étude de la dualité des sources juridiques aussi bien originaires que dérivées. Cette dualité des systèmes institutionnels se manifeste également par la consécration d’organes de gestion ainsi que par les organes de contrôle démocratique ou juridictionnel. Dans la deuxième partie de cet ouvrage, Monsieur SARR a préconisé la nécessaire articulation des deux ordres juridiques. Ainsi, tout en reconnaissant qu’il existe une cohérence actuelle dans le fonctionnement des deux ordres juridiques, il n’en a pas moins démontré que cette cohérence est à parfaire en raison d’une certaine concurrence entre les deux ordres juridiques. Il a alors préconisé des solutions idoines qui permettront aux deux Organisations de fonctionner correctement.
Code: L’intégration juridique dans l’Union économique et monétaire ouest africaine (UEMOA) et dans l’organisation pour l’harmonisation du droit des affaires en Afriques (OHADA) Publication Title: L’intégration juridique dans l’Union économique et monétaire ouest africaine (UEMOA) et dans l’organisation pour l’harmonisation du droit des affaires en Afriques (OHADA) Reporter: L’intégration juridique dans l’Union économique et monétaire ouest africaine (UEMOA) et dans l’organisation pour l’harmonisation du droit des affaires en Afriques (OHADA) Series Title: Horizons africains
Keywords: Intégration juridique; Organisation pour l’harmonisation du droit des affaires en Afriques (OHADA); Union économique et monétaire ouest africaine (UEMOA); États-membres

NEPAD and African Development: Towards a New Partnership between Development Actors in Africa - Tawfik, Rawia M. (African Journal of International Affairs, 2008)
The model required to drive socio-economic development in Africa, and the relationship between the state and the private sector based on that model, have sparked much controversy among African analysts. Some question the relevance of other successful models of development, such as in the liberal West or in East-Asia, to the African context. Others criticise all models of development that are “alien” to African cultures and conditions hence rejecting the NEPAD model on this basis. This paper argues that although NEPAD does not present a detailed model of the relationship between the state, the private sector and civil society in Africa, some of its theoretical underpinnings suggest a balanced framework that should prompt African scholars to search for new models that do not necessarily imitate already successful ones but respect the particularities of each African state

The Harmonization of Business Law in Africa: Is Article 42 of the OHADA Treaty a Problem? - Enonchong, Nelson (Journal of African Law, 2007)
OpenAlex: https://openalex.org/W2023472476
Keywords: Harmonization; Investment; Member state

CEDEAO : Cadre régional de la politique de la concurrence - Communauté Economique des Etats de l'Afrique de l'Ouest (CEDEAO, 2007)

CEDEAO : Cadre régional de politique des investissements - Communauté Economique des Etats de l'Afrique de l'Ouest (CEDEAO, 2007)

Marché commun d'investissement de la CEDEAO : directives opérationnelles relatives à l'harmonisation des lois nationales régissant l'invesstissement - Communauté Economique des Etats de l'Afrique de l'Ouest (CEDEAO, 2007)

Re-Imagining International Law: An Examination of Recent Trends in the Reception of International Law Into National Legal Systems in Africa - Oppong, Richard (Fordham International Law Journal, 2006)
This article suggests that the trend of accepting the supremacy and direct application of international law represents a rethinking of the relationship between international and national law, and that its full implications are yet to be explored. The Article seeks to build on current writings on the subject by analyzing certain regional arrangements and judicial approaches relevant to, but often ignored in the discussion. It attempts not to situate these arrangements or approaches within or outside of the monist/dualist paradigm, but to assess the practical significance of these arrangements for international law, national law, and their respective subjects.

A nova parceria para o desenvolvimento da África : NEPAD, paradigma para o desenvolvimento - Diallo, Alfa Oumar (Universidade Federal do Rio Grande do Sul, 2006)
Os chefes de Estado africanos, após a transformação da Organização da Unidade Africana em União Africana, propuseram a Nova Parceria para o Desenvolvimento da África (NEPAD), como um quadro para uma nova relação de parceria entre a África e a comunidade internacional. Neste sentido de nova parceria, os dirigentes africanos se engajaram em promover nos seus países, na sua região e no Continente, a paz, a segurança, a democracia, a boa governança, o respeito dos direitos humanos e uma saudável gestão econômica, como uma estratégia para orientar o desenvolvimento da África no século XXI. A NEPAD suscitou uma reação positiva na comunidade internacional. A NEPAD repousa sobre fundamentos de desenvolvimento duradouro no Continente, sem os quais tornam-se impossíveis resultados concretos. Entre esses fundamentos podemos citar: a democracia, a boa governança, a governança econômica e a governança das empresas. Para alcançar o objetivo, a NEPAD propõe reformas institucionais como a utilização de meios de avaliação que permitem instaurar definitivamente a boa governança nas estruturas do Estado. Les chefs d'Etats Africains, après avoir mué l'Organisation de l'Unité Africaine en Union Africaine, ont proposé le Nouveau Partenariat pour le Développement de l'Afrique (NEPAD), comme cadre pour une nouvelle relation de partenariat entre l'Afrique et la communauté internationale. Dans le cadre de ce nouveau partenariat, les dirigeants africains s'engagent à promouvoir dans leurs pays, leur région et dans le continent, la paix, la sécurité, la démocratie, le bonne gouvernance, le respect des droits de l'homme et une saine gestion économique, comme une stratégie pour guider le développement de l’Afrique au 21è Siècle. Le NEPAD a suscité une réaction positive dans la communauté internationale. Le NEPAD repose sur des fondements du développement durable sur le continent, sans lesquels il sera impossible d'arriver à des résultats probants. Parmi ces fondements, on peut citer : la démocratie, la bonne gouvernance, la gouvernance économique et la gouvernance des entreprises. Pour atteindre cet objectif, le NEPAD propose des réformes institutionnelles comme l´utilisation d´outils d'évaluation qui permettront d'instaurer définitivement la bonne gouvernance dans les structures de l'Etat.
URI: https://lume.ufrgs.br/handle/10183/7484
Keywords: Bonne gouvernance; Direito internacional público; Droits fondamentaux; Développement; Intégration régionale; NEPAD

La Cour africaine des droits de l'homme et des peuples - Gros plan sur le premier organe judiciaire africain à vocation continentale - Ouguergouz, Fatsah (Annuaire Français de Droit International, 2006)

Integração Africana: da Organização da Unidade Africana à União Africana - Diallo, Alfa Oumar (Espaço Jurídico Journal of Law, 2005)
Desde Kwamé N´Krumah a unidade da África era um grande desejo. A Organização da Unidade Africana (OUA) servia aos olhares de alguns na pobreza moral e material do continente. Destaca-se, que dentro da OUA, alguns fundadores militavam em favor da instituição dos Estados Unidos da África enquanto que outros pregavam, ao contrário, pela fragmentação dos Estados-Nações sob uma forma organizacional. Os Estados Unidos da África certamente seriam limitados à exploração contínua deste continente, mas muitos não tinham esse entendimento. Felizmente, alguns chefes de Estados africanos conscientizaram-se dessa situação e como uma pandemia, esta tomada de consciência está se estendendo pouco a pouco. Em Syrte na Líbia, no dia 9 de setembro, os chefes de Estados e de governos da África, sob a iniciativa de Mouhammar El Kadhafi, resolveram criar a União Africana (UA). Assim, em 11 de julho de 2000, em Lomé (Togo), os Estados Africanos adotaram o Ato Constitutivo da União Africana. A assinatura desse ato foi tomada sem dificuldades, mas este não foi o caso para a sua ratificação, feita com muitas reservas. Nesse espírito, no dia 25 de maio de 2001, a União Africana foi criada política e juridicamente, marcando assim uma nova era para a África. Era preciso adaptar à África na nova ordem mundial.Palavras-chave: Organização da Unidade Africana. União Africana. Pan-Africanismo. Direitos Fundamentais.
© Espaço Jurídico: Journal of Law [EJJL] - Qualis A2 2015
Keywords: Direitos Fundamentais; Organização da Unidade Africana; Pan-Africanismo; União Africana

The Social Dimension of Regional Integration in ECOWAS - Robert, René (Social Science Research Network, 2004)
Regional economic integration arrangements have their own purpose, legal framework, institutional set-up, history, and trajectory, and this paper aims to study these factors in relation to the Economic Community of West African States (ECOWAS). When dealing with regional integration, it is important to consider governance, trade liberalization, and its social impact. The paper focuses on the West African Economic and Monetary Union (WAEMU) and the Organization for the Harmonization of Business Law in Africa (OHADA) to analyze labour law harmonization, poverty reduction strategies for development, gender empowerment, and democratic participation. Suggestions to strengthen socio-economic development include promoting social dialogue and how the International Labour Organization and other institutions' can help with better integration in Western Africa. Ultimately, identifying and understanding the unique economic integration arrangements of certain communities can help develop their paths towards a fairer globalization for all.
10.2139/ssrn.908485
Keywords: ECOWAS; Integration; Regional; Social dimension; WAEMU

Droit matériel et intégration sous-régionale en Afrique centrale : contribution à l'études des mutations récentes du marché intérieur et du droit de la concurrence CEMAC - Gnimpieba Tonnang, Édouard (Université de Nice Sophia-Antipolis, 2004)
L'échec de l'UDEAC et des politiques communes destinées à réaliser l'union douanière entre les Etats de l'Afrique centrale a poussé ces derniers à remettre en question toutes les politiques d'intégration économique engagées depuis leur accession à la souveraineté internationale. L'analyse des causes de cet échec les a ainsi conduit non à abandonner l'idéal communautaire, mais à relancer ce dernier sur de nouvelles bases, dans l'objectif de mettre en place, à moyen terme, un marché commun au sein duquel la libre circulation des facteurs de production ainsi qu'une saine et loyale concurrence entre acteurs économiques étaient garanties. Cet objectif ambitieux d'unification, loin de construire ses fondations sur des instruments purement économiques - lesquels ont montré toutes leurs limites avec l'UDEAC - a décidé de faire du droit l'instrument principal devant garantir son succès. Cette nouvelle approche s'inscrit en fait dans la droite ligne du nouveau régionalisme juridique ayant cours au niveau planétaire depuis quelques années. Ainsi, en quelques années, parallèlement aux règles institutionnelles, un droit matériel a été mis en place, dans l'objectif de faciliter la mise en œuvre des objectifs poursuivis par les pays membres de la CEMAC. Les règles destinées à décloisonner les marchés nationaux et devant aboutir à la mise en place d'un marché intérieur de dimension plus importante et la garantie d'une saine et loyale concurrence entre les acteurs de ce marché, grâce aux techniques juridiques d'harmonisation et de coordination législatives, sont logiquement apparues comme urgentes dans l'ambition de sécurisation sous-régionale des affaires engagée dans le cadre de l'uniformisation du droit économique sous-régional portée depuis 1993 par l'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA). L'adoption des règles régissant le fonctionnement de ce marché intérieur, notamment celles garantissant la libre circulation des biens, des personnes, des services et des capitaux ainsi que la consécration d'un droit communautaire de la concurrence apparaissent donc comme les prémisses du renouveau d'un régionalisme porteur de développement et de bien-être en Afrique centrale. La juridictionnalisation amorcée de cette entreprise commune apparaît également comme annonciatrice d'une nouvelle ère dans la sous-région.
Keywords: Afrique centrale; Competencia; Competition law; Concurrence (droit); Droit comparé; Droit des affaires; Droit public

L'harmonisation du droit des affaires en Afrique : L'expérience de l'ohada à l'épreuve de sa première décennie - Cissé, Abdoullah (Revue internationale de droit économique, 2004)

Schéma de libéralisation des échanges de la CEDEAO: protocoles et règlements - Communauté Economique des Etats de l'Afrique de l'Ouest (Secrétariat Exécutif de la CEDEAO, 2004)

Worldwide Harmonisation of Private Law and Regional Economic Integration - General Report - Basedow, Jürgen (Uniform Law Review, 2003)

L'Organisation de l'Unité Africaine / Union Africaine et le règlement des conflits territoriaux et frontaliers : Contribution à l'étude de l'uti possidetis en Droit international public - Kamara, Mactar (Université Paris 1, 2002)

Embedding liberalism : diritti sociali e mercato nell'integrazione comunitaria - Giubboni, Stefano (European University Institute, 2002)

Business Law in Africa: OHADA and the Harmonization Process - Martor, Boris; Pilkington, Nanette; Sellers, David S.; Thouvenot, Sébastien (GMB Publishing, 2002)
Accepted: 2019-04-10T07:48:19Z Journal Abbreviation: OHADA and the Harmonization Process

African Legal Developments in the United States and Sub-Saharan Africa - Eisenfeld, Jamie; Serres, Francois (The International Lawyer, 2001)
https://scholar.smu.edu/til/vol35/iss3/3

Les garanties procédurales en droit communautaire : recherches sur la procédure et le bon gouvernement - Azoulai, Loic (European University Institute, 2000)
Keywords: Procedure (Law)

Un recueil de la CEDEAO sur la libre circulation des personnes, le droit de résidence et d'établissement - Communauté Economique des Etats de l'Afrique de l'Ouest (CEDEAO, 2000)